Role of chaihu yujin decoction in cholecystitis: a systematic investigation integrating multi-omics and experimental validation - Feng Xu; Jia-Han Xu; Xiao-Min Chen; Kai-Li Mao; Jie Hu; Hong-Liang Zheng; Huan-Huan Xia; Zhi-Hui Zhang; Qiu-Ting Lin (Functional & Integrative Genomics, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

A synergistic enzymatic strategy for comprehensive improvement of bread quality and digestibility using a novel maltohexaose-forming amylase and a 4,6-α-glucanotransferase - Yu-chuan Wang; Hong Liu; Li-xiao Fu; Meng-jun Han; Qiao-juan Yan; Zheng-qiang Jiang; Yan-xiao Li (Food Hydrocolloids, 2026)

Water environmental carrying capacity and driving factors in Yangtze estuary: PCA-copula and Shapley value with salinity zoning - Haibiao Zhu; Jinjie Li; Xu Zhao; Qi Wu; Yuan Fang; Ruobing Han; Yonglu Feng; Ying Tang; Hong Huang (Estuarine, Coastal and Shelf Science, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Novel bacterial hosts and mobile genetic structure of tet(X) variants in tetracycline-contaminated aquatic environment uncovered by culture and long-read metagenomics - Ziming Han; Hong Zhang; Hanzhou Li; Xiao Luan; Shashika Kumudumali Guruge; Chengzhi Hu; Min Yang; Yu Zhang (Water Research, 2026)

Patterns and mechanisms of cross-media antimicrobial resistance development in a typical reclaimed water-receiving urban river - Bang-Ze Li; Shu-Hao Du; Han-Lin Cui; Xin-Xin Gao; Jia-Hao Wu; Bei-Ying Li; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2026)

A Shenling Baizhu San polysaccharide fraction (SLP-2)-based synbiotic alleviates lactose-induced gut dysfunction via a microbiota-metabolite-barrier axis - Li-Li Han; Chun-Feng Mei; Mengxiong Lu; Hong Xue (Food Research International, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Ten questions on digital twins of buildings for transforming building operations - Tianzhen Hong; Han Li; Yimin Zhu; Bing Dong; Liang Zhang; Ruchi Choudhary (Building and Environment, 2026)

Semiconducting polymer-based ratiometric fluorescent nanoprobe for highly accurate imaging of H2S in inflammatory and tumor cells - Chen Han; Xing Wang; Yating He; Rong Wang; Hong-Min Meng; Lin Zhang; Zhaohui Li (Analytica Chimica Acta, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Technological strategies and land-use dynamics during the Middle Holocene at the Dongguotan site, Northeastern Qinghai-Tibet Plateau - He Honglin; Han Fang; Du Zhanwei; Lü Hongliang; Qiao Hong; Li Jiyuan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Fumarate-based copolyesters with long-term stability and temperature-gated enzymatic degradation - Peng Liang; Han Hu; Hanxu Zhu; Xiaokun Hong; Dong-Qing Wei; Jiayi Li; Jinggang Wang; Jin Zhu (Journal of Hazardous Materials, 2026)

Rare earth elements as emerging contaminants: Multi-source release, geochemical tracing, and implications for environmental monitoring and management - Yong-He Han; Ming-Zhu Zou; Dong-Xing Guan; Yi-Xi Li; Ping Xiang; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Environmental Management, 2026)

How geographical indications shape consumer purchase responses: The role of trust and social interaction in Chinese tea markets - Ruiqi Chen; Haobin Wang; Hanhui Hong; Yanbing Zhang; Li Han; Yaoming Liang (International Journal of Gastronomy and Food Science, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

High-density Tegillarca granosa improves water quality and reduces greenhouse gas emissions in sulfamethoxazole-exposed mangrove microcosms - Kairong Zheng; Hong Jin; Xingmin Jin; Junjie Lai; Jiayu Qian; Guangqian Kuang; Huize Li; Yiming Hu; Min Zhao; Xiangyong Zheng; Wenjuan Han (Environmental Research, 2026)

Trophic dynamics of parrotfish in a degraded coral reef ecosystem in the Xisha Islands, South China sea - Jinfa Zhao; Teng Wang; Yu Liu; Hong Li; Huaxue Liu; Hongyu Xie; Jianzhong Shen; Yayuan Xiao; Xuefu Ao; Hai Huang; Yong Liu; Qiuying Han (Environmental Research, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

Photochemically corrected machine learning framework for real-time VOCs source apportionment in support of air quality management - Yu Han; Xing Peng; Yi Hong; Jiang-Yao Tan; Jiang Wu; Li He; Xiao-Feng Huang; Guang-He Yu; Ke Du (Atmospheric Environment, 2026)

Dolomite characteristics and genetic mechanisms of Member 1, Sanya Formation in Well Xike 1, South China Sea - Chao Han; Yazeng Ma; Hong Xu; Zuozhen Han; Jinxiong Luo; Qiang Li; Yuetong Zhang (Journal of Oceanology and Limnology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Numerical investigation with viscosity of nonlinear wave forces on a dual-tube submerged floating tunnel - Hong-fei Mao; Kai-lin Chen; Long Han; Zhong-bing Zhou; Yan-li He; Li-min Wang; Jing Xie (Ocean Engineering, 2026)

Mining rare earth elements with ammonium sulfate as a leaching agent provokes a significant perturbation in soil microbial function - Yong-He Han; Ming-Zhu Zou; Xue-Mei Wei; Xian Chen; Li-Chao Tong; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2026)

Indium enrichment in VMS deposits: insights from sphalerite geochemistry and thermodynamic modeling of the Tiemurt Pb-Zn-Cu deposit, NW China - Min Luo; Peng-Peng Yu; Yi Zheng; Jie-Jun Lei; Xi Chen; Yi-Han Wu; Hong-Xiang Shan; Quan-Jie Li; Zhuo-Xiong Shi (Journal of Geochemical Exploration, 2026)

Arsenic induces chicken liver injury by inhibiting endoplasmic reticulum-lysosomal calcium ion transport and lysosomal autophagy activity via the IP3R/TRPML1 pathway - Baoxin Qiao; Panjing Hong; Ying He; Yumeng Li; Xudong Han; Yanli You; Gaolong Zhong; Zhaoxin Tang; Lianmei Hu (Journal of Environmental Sciences, 2026)

A daily-weekly-resolved δ18O record derived from a modern giant clam shell in the northern South China Sea: Implications for paleoclimate and paleoweather reconstruction - Chengcheng Liu; Nanyu Zhao; Guozhen Wang; Fan Luo; Shan Liu; Qiuju Yang; Murong Qi; Tao Han; Gang Xue; Miaohong He; Qiuli Li; Guoqiang Tang; et al. (Chemical Geology, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Assessing the impact of four tillage methods on soil and water conservation in karst areas of Southwest China: Evidence from a 10-year field study - Quanzhong Sun; Ruyi Zi; Fayong Fang; Bin Yang; Minghai Hong; Yuanze Xu; Lang Peng; Li Qin; Tao Song; Jiaojiao Du; Zhongxian Liu; Zhen Han; et al. (Agriculture, Ecosystems & Environment, 2026)

Numerical examination of hydrodynamic forces on a submerged forced rotating circular cylinder under wave action - Hong-Fei Mao; Long Han; Kai-Lin Chen; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Hui Yang; Dong-Bin He; Li-Min Wang (Ocean Engineering, 2026)

Pulse electric field-assisted preparation of soy protein isolate-based films with excellent mechanical strength and UV barrier performance - Ying Li; Xiu-Er Luo; Yu-Huan Geng; Wen-Hong Gao; Shuai Zhang; Zhong Han (Innovative Food Science & Emerging Technologies, 2026)

Short anti-aging peptides from edible microalgae using a multi-targets virtual screening strategy combined with Caenorhabditis elegans model - Yan-yan Yuan; Xin Li; Ming-hui Han; Xue An; Yong-Qiang Lin; Hong-Bing Liu (Food Research International, 2026)

Combined bearing capacity of spudcan considering installation effect in clay - Ye Tian; Jiang Tao Yi; Si Yu Li; Hong Yu Tang; Xiao Han; Jing Nian Ran (Computers and Geotechnics, 2026)

Ultraviolet-ozone tuned organic-inorganic interface for high-performance PbS quantum dot short-wave infrared photodetectors - Jun Han; Ning Feng; Chuan Wei; Li Yan; Chengrun Shu; Jiatong Liu; Zhouying Wu; Hao Yan; Meili Xu; Yaowu He; Xiaomin Xu; Hong Meng (Chemical Engineering Journal, 2026)

The eastern branch fault model of the Tanlu Fault zone and its controlling effect on hydrocarbon accumulation: A case study of southern section of Bohai Sea - Ji-mei Deng; Shi-qiang Xia; Wen-hui Huang; Peng Wu; Gang Han; Hong Li (Applied Geophysics, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Extracting cropping patterns from remotely sensed images in a mixed single-, double-, and triple-cropping region of Southern China - Yifan Li; Chen Cheng; Xiaoming Shi; Hong Chi; Yifei Han; Fei Zhao; Jinliang Huang; Feng Ling (Environmental Monitoring and Assessment, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Structure–function relationships in chitosan films containing ZIF-8-confined Ligusticum jeholense essential oil: pH-triggered release and apple ring rot control - Xiao-Yi Tong; Yun-Feng Liu; Zhi-Hong Xu; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An; Fei Cao (Food Chemistry, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

The health threat of wild animals by Rank I ARGs from habitat soils: Metagenomic and metabolomic evidence - Jiaying Ma; Han Zhang; Sumei Liang; Xinxin Feng; Zhaoyang Xia; Hong Li; Shuzhen Zou; Dayong Li (Environmental Pollution, 2026)

Controlled synthesis of micro-flexible fluorine-neodymium nanosheets for separation membranes with enhanced properties - Shurui Han; Hui Ye; Jing Lv; Xiaojian Fu; Hong Li; Yuzhong Zhang (Chemical Engineering Journal, 2026)

Allelopathy enhancement of an invasive potassium-rich plant Alternanthera Philoxeroides by potassium fertilization is caused by the increase of allelochemicals and potassium concentrations - Bing-Yao Li; Yu-Han Xiao; Wen-Qi Duan; Hong-Yu Xiao; Yan-Hong Wang; Mohamed Abdelaziz Balah; Ai-Ping Wu (Plant Ecology, 2026)

Development and Evaluation of a Novel 3D Variational Assimilation Framework for Regional Chemistry–Weather Forecasting - Zhaorong Zhuang; Weihong Tian; Liping Huang; Xueshun Shen; Wei Han; Hong Wang; Xingliang Li; Xiaoye Zhang (Journal of Meteorological Research, 2026)

A mechanistic machine learning framework to decode reverse osmosis membrane retention mechanism for neutral low-molecular-weight organics - Han-Ying Cai; Yin-Hu Wu; Bai-Wen Ma; Hui Li; Pei-Hua Li; Qian-Yuan Wu; Wen-Long Wang; Zhuo Chen; Hong-Ying Hu (Journal of Cleaner Production, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Hydrogen sulfide maintains banana postharvest quality by antagonizing ethylene and enhancing antioxidant properties in Musa nana Lour - Xue-Ting Cheng; Yan-Hong Li; Yun Ge; Zhuo Han; Yi-Ang Feng; Ying-Zhi Zhang; Kang-Di Hu; Gai-Fang Yao; Pedro García-Caparros; Hua Zhang (Food Control, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Prediction of Sound Speed Profiles Under Disturbance of Strong Internal Solitary Waves Using Bidirectional Long Short-Term Memory Network - Hong Yin; Ke Qu; Han Wang; Guangming Li (Journal of Marine Science and Engineering, 2026)
Time-series machine learning models represented by long short-term memory (LSTM) networks provide an effective way to obtain high-precision sound speed profiles (SSPs) quickly and at low cost, which can meet the practical application requirements of underwater sonar systems. However, in sea areas with frequent strong internal solitary waves, the large-amplitude sound speed anomalies caused by them will seriously interfere with model learning in the form of strong outlier features, resulting in a sharp drop in SSP prediction accuracy and significant degradation of the generalization stability and robustness of the model. To address this problem, this paper proposes a time-series SSP prediction method based on a bidirectional long short-term memory (Bi-LSTM) network. First, Empirical Orthogonal Function (EOF) decomposition is used to realize the low-dimensional feature representation of SSPs, and then the bidirectional time-series feature capture capability of Bi-LSTM is used to predict the SSP sequence with large disturbances caused by strong internal solitary waves. Multiple groups of comparative experiments based on the measured temperature chain data in the continental slope area of the South China Sea show that the Bi-LSTM model has a significant improvement in prediction accuracy and robustness compared with the classical LSTM model. Among them, the Bi-LSTM model with EOF decomposition achieves a correlation coefficient of 0.995 and an average Root Mean Square Error (RMSE) as low as 0.387 m/s. Under the condition of internal solitary wave disturbance, the classical LSTM is difficult to effectively capture the large abrupt change in sound speed, while the proposed Bi-LSTM model can still achieve accurate prediction of the SSP in the disturbance section, and has both the feature recognition and evolution prediction capabilities for the strongly nonlinear internal solitary wave process. This method provides effective technical support for the rapid and large-scale reconstruction of the sound speed field under the disturbance of strong internal solitary waves.

Structural optimization of natural plant products: Construction and insecticidal activities study of eugenol's derivatives - Wen Zhang; Xiao-Han Zhang; Li-Hong Sun; Cheng-Yuan Liu; Wen-Hui Zhang; Yi-Wen Huang; Jun-Long Wang; Ji Zhang; Jun-Yu Liang (Pesticide Biochemistry and Physiology, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Why Does Braising Enhance the Aroma Profile of Xinjiang Braised–Roasted Chicken? Insights into Precursor Conversion and Aroma Formation Pathways - Ke Bi; Yue Liu; Dong Han; Xinwei Li; Yinfeng Lei; Hong Pan; Ping Yang; Chunhui Zhang; Marie-laure Fauconnier (Food Research International, 2026)

Bacillus velezensis-derived methylmalonic acid inhibits Aspergillus flavus growth and aflatoxin biosynthesis by interfering with tryptophan metabolism - Ming Li; Qin Han; Xiulan Zhao; Yuxuan Hong; Ye Zhu; Can Liu; Jinyan Chai; Ling Cheng; Xiaofeng Yue; Xiaoqian Tang; Jing Mao; Qi Zhang; et al. (Chemical Engineering Journal, 2026)

Genetic diversity of Theileria species identified from questing and parasitic ticks in selected areas in Qinghai, China - Yuan Han; Zhi Li; Yong Fu; Junlong Liu; Dan Jia; Chunhua Li; Hong Yin; Mengtong Lei (Veterinary Research Communications, 2026)

Identification and validation of a QTL, QSNS.caas-3D.1, for spikelet number per spike in wheat - Xuezhong Liang; Junli Yang; Ze Liu; Fuping Zhang; Haiming Han; Shenghui Zhou; Jinpeng Zhang; Bing Han; Yida Lin; Hong-Qing Ling; Li Zheng; Junbo Yang; et al. (Theoretical and Applied Genetics, 2026)

Differential responses of soil microbial community structure and function to conventional and biodegradable microplastics - Yuhan Liu; Xue Bei; Chuanwei Zheng; Hong Lou; Huimei Tian; Wenjing Han; Wenxiao Sun; Songyan Jiao; Shuo Li; Bing Li; Lusheng Zhu; Zhongkun Du; et al. (Applied Soil Ecology, 2026)

Pyroptosis as a double-edged sword in colorectal cancer: Molecular mechanisms and therapeutic opportunities - Han-Xi Zhang; Wen-Jing Xu; Yi-Xin Jiang; Lu Li; Bai-Yu Chen; Meng-Yao Cheng; Meng-Yuan Hao; Hang-Shen Han; Hong-Jie Li; Yan-Ge Li; Dong-Dong Wu (Apoptosis, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Characterization of two virulent Proteus mirabilis phages and application of phage cocktail in raw chicken safety - Shilin Zhang; Ruibing Yang; Yaru Hong; Han Niu; Jiansong You; Jianguang Li; Huili Zhang; Bilal Murtaza; Chenyang Yi; Xiaoyu Li; Yongping Xu; Lili Wang (Food Microbiology, 2026)

Good practices for documenting AI-based studies on energy and buildings - Tianzhen Hong; Han Li (Energy and Buildings, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

A Geographic-Dependent Coupled Parameter Optimization Scheme Based on A-4DEnVar - Jianxin He; Lige Cao; Wei Li; Guijun Han; Xuan Wang; Hong Li; Kangzhuang Liang; Gongfu Zhou; Haowen Wu; Qingyu Zheng; Yang Zhang; Yicong Tong (Journal of Marine Science and Engineering, 2026)
Coupled climate models integrate atmospheric, oceanic, and land submodels, while the uncertainty of model parameters from different parameterization schemes or empirically derived parameters inevitably introduces systematic biases. Coupled parameter optimization (CPO) can reduce these biases to improve weather forecast and climate prediction, but must address strong nonlinearities inherent in coupled models. The analytical four-dimensional ensemble variational (A-4DEnVar) data assimilation method retains the nonlinear processing capability of the four-dimensional variational (4D-Var) data assimilation method but gets rid of the dependence on the adjoint model. In this study, a novel dynamic independent point (DIP) scheme is introduced to the improved A-4DEnVar, which reduces computational dimensionality and further explores a broader parameter space of dimensionality reduction through the outer loop. Based on the improved A-4DEnVar, a series of geographic-dependent CPO experiments with an idealized 2D coupled model are carried out. Results show that A-4DEnVar accurately captures the geographical characteristics of parameters and effectively optimizes cross-component parameters despite strong nonlinearity. Additionally, the DIP scheme presents significant advantages compared to the static independent point scheme, especially with fewer independent points. This work is offering a new perspective for parameter optimization in coupled general circulation models used for climate estimation and prediction.

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Generating unseen nonlinear evolution in the ocean using deep learning-based latent space data assimilation model - Qingyu Zheng; Qi Shao; Guijun Han; Wei Li; Hong Li; Xuan Wang (Ocean Modelling, 2026)

Prenatal organophosphate esters exposure impacts placental structure and inflammatory markers in a trimester-specific manner - Yuan Liu; Ping Lv; Xing Wang; Mengqian Zhang; Yifan Wang; Sheng Wang; Mengjuan Lu; Han Li; Hong Gan; Juan Tong; Hui Gao; Fangbiao Tao (Environmental Research, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Interpenetrated hierarchical polyzwitterionic hydrogels promote decellularized small-diameter vascular grafts regeneration - Qi-Ying Wu; Chun-Yang Chen; Jin-Chang Li; Ze-Guo Chen; Si-Cheng Chen; Chao Xie; Si-Xi Liu; Zi-Han Liu; Zhong-Shi Wu; Yu-Hong Liu (Chemical Engineering Journal, 2026)

Robotics for HVAC applications: A critical review and future perspectives - Yilin Jiang; Han Li; Payam Delgoshaei; Zhangding Liu; Tianzhen Hong (Building and Environment, 2026)

Whole-grain black rice diet rewires the single-cell transcriptomic landscape of age-related ovarian decline in mice - Yi-Xuan Tu; Dan-Yang Wang; Jun Ma; Ke-Chun Yu; Sheng-Hui Li; Bo-Han Li; Xin-Yin Deng; Shan Li; Hong-Kai Wang; Tailang Yin; Ling Wang; Zhen-Xia Chen (Science China Life Sciences, 2026)

High-latitude species with temperature-dependent sex determination will face an elevated risk from climate change - Jun Zhong; Shan Li; Ming-Shen Hong; Mei-Lian Song; Han-Yi Lan; Xiang Ji (Biodiversity and Conservation, 2026)

A Hybrid CUBE-IForest Approach for Outlier Detection in Multibeam Bathymetry - Rui Han; Yukai Hong; Xibin Han; Yi Zhang; Shunming Hu; Yuan Huan; Xiaodong Cui; Xiaohu Li (Journal of Marine Science and Engineering, 2026)
With the rapid development and widespread application of multibeam echo-sounding systems, large-scale and high-resolution seafloor topography can be efficiently acquired, enabling precise mapping of seabed terrain. However, due to complex oceanographic conditions, instrumental noise, and acoustic interferences, the acquired multibeam data often contain outliers that deviate from the true seafloor surface. These outliers can distort the representation of seafloor topography, adversely affecting subsequent geological analysis and engineering applications. To address this issue, a hybrid outlier detection method combining CUBE filtering with the Isolation Forest (IForest) algorithm, termed CUBE-IForest, is proposed. The method first employs CUBE filtering to remove gross outliers based on local uncertainty estimation, followed by the application of IForest to identify subtle anomalies in the refined data, achieving hierarchical detection of outliers. Experimental results based on in situ multibeam bathymetric data from the northeastern Pacific demonstrate that compared with traditional filtering methods the CUBE-IForest approach significantly improves detection accuracy and reduces both false positive and false negative rates by approximately 30%, confirming its efficiency and reliability in seafloor mapping and analysis.

Fused Geophysical–Contrastive Learning Model for CYGNSS-Based Sea Surface Wind Speed Retrieval in Typhoon Regions - Yun Zhang; Zelong Teng; Shuhu Yang; Qingjing Shi; Jiaying Li; Fei Guo; Bo Peng; Yanling Han; Zhonghua Hong (Journal of Marine Science and Engineering, 2026)
Global Navigation Satellite System Reflectometry (GNSS-R) provides a vital means for sea surface wind speed retrieval, yet its application under extreme typhoon conditions remains challenging. Conventional geophysical models (GMFs) saturate in high wind speed regimes (>20 m/s), and deep learning models (e.g., CNNs) are constrained by data sparsity and feature complexity in typhoon environments. To address these issues, we propose a Comparative Learning method of CNN-Transformer with GMF fusion (CLCTG). The CNN branch extracts local coupling patterns, the Transformer branch models global dependencies, and Kullback–Leibler (KL) divergence loss is used for contrastive learning to heighten sensitivity to complex typhoon wind fields. The GMF branch serves as a physical reference/anchor in the low- to moderate-wind-speed range ( 30 m/s range. To further improve high-wind-speed predictions, we introduce environmental features based on their correlation with wind speed; ablation experiments demonstrate that the combined use of environmental parameters and CYGNSS features maximizes overall accuracy. Testing on five typhoons from the Eastern and Western Hemispheres confirms CLCTG’s generalization across diverse geographic contexts, and branch-wise comparisons validate its structural advantages. Buoy observations show peripheral errors below 3 m/s and physically consistent wind speed gradients in the core region. These results indicate that multi-source fusion of CYGNSS and environmental data, coupled with contrastive learning and physical reference, offers a reliable and efficient solution for typhoon wind speed retrieval.

Spatiotemporal Characteristics and Long-Term Variability of Large-Wave Frequency in the Northwest Pacific - Zhen-Yu Zhao; Hong-Ze Leng; Yu-Han Wei; Jin-Hui Yang; Xuan Zhou; Ze-Zheng Zhao; Hui-Peng Wang; Bao-Xu Li; Wu-Xin Wang; Jun-Qiang Song (Journal of Marine Science and Engineering, 2026)
This study provides a systematic analysis of the spatiotemporal distribution and trends in the frequency of significant wave height (SWH) exceeding level 5 (SWH > 2.5 m) and level 7 (SWH > 6 m) in the Northwest Pacific (NWP) for 1993–2024, which are defined as f5 and f7, respectively, as well as their correlations with major climate indexes. Our results indicate that (1) the high-value zones for the annual mean f5 and f7 are both located in the south waters of the Aleutian Islands, with maximum values of 58.0% and 6.4%, respectively. Winter’s contribution is greatest (maximum values of 96.9% and 16.8% per year), while summer’s is the smallest. (2) f5 exhibits a significant decline trend across the entire NWP basin (of −0.15 to −0.30%/yr), with the steepest decline occurring in autumn (−0.69%/yr) and the shallowest in summer. f7 exhibits a significant linear decrease in the open ocean east of Japan (−0.08%/yr) while showing a significant linear increase in the waters east of the Kamchatka Peninsula (0.08%/yr). Both variations peak in winter (maximum values of −0.27% and 0.30% per year) and are smallest in summer. (3) Seasonal and regional variations in climate index–f5 and f7 relationships reflect large-scale atmospheric modulation of waves. For example, the Oceanic Niño Index shows a predominantly negative correlation with f5 in winter (maximum correlation coefficient rm = −0.70) around the Luzon Strait, shifting to a significant positive correlation in summer (rm = 0.70) across the extensive region east of Taiwan Island and the Philippines. The Pacific Decadal Oscillation index shows a significant positive correlation with f7 in summer and autumn (rm = 0.69) east of Taiwan Island and a strong negative correlation in winter (rm = −0.77) to the east of Kamchatka Peninsula.

Mechanistic insights into gas capture and diffusion during the CO2 separation of mixed matrix membranes using ZIF materials as nanofillers - Han-chong Liu; Hong-li Chen; Li-guang Wu; Ting Wang; Hua-li Chen; Cheng Hu (Process Safety and Environmental Protection, 2026)

SfFPPS genes mediate reproduction and insecticide-induced resurgence in Sogatella furcifera - Cao Zhou; Zi-Han Xu; Jiang-Ling Chen; Xin Li; Shi-Yan Zhang; Hong Yang; Dao-Chao Jin (Pesticide Biochemistry and Physiology, 2026)

Caseazins R−Y, cytotoxic podocarpane diterpenoids from Casearia kurzii - Xue-Wen Wu; Qiong Wei; Xia Pu; Chun-Mei Cha; Rui Li; Yin-Qiao Huang; Rui-Han Zhang; Xiao-Li Li; Hong-Liang Li; Wei-Lie Xiao (Phytochemistry, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Consolidated combined V-H-M-T capacity of a suction caisson in clay - Hao Ran Li; Xiu Zhe Wang; Jiang Tao Yi; Hong Yu Tang; Xiao Han (Ocean Engineering, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

Corrigendum to ‘Metabolic flexibility of rhizobacteria drives soil nutrient cycling and enhances rare earth elements hyperaccumulation in ferns colonizing degraded mine ecosystems’ [J. Environ. Manag. 395 (2025) 128013] - Yong-He Han; Xi-Wen Cui; Hai-Bin Han; Yang-Long Jiang; Li-Chao Tong; Jian-Fei Chen; Hong Zhang; Yong Zhang; Zhibiao Chen (Journal of Environmental Management, 2026)

EAME: Element-Aware Multi-UAV distributed autonomous exploration for efficient and complete under-canopy measurements - Yuquan Zhou; Li Yan; Yinghao Zhao; Shaungwei Shu; Yaxi Han; Hong Xie (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Associations of urinary environmental phenols with obesity and lipid metabolism in children and adolescents: The expanded Chinese National Human Biomonitoring (CNHBM) project - Nan Jiang; Qi Chen; Beijing Cheng; Ke Meng; Jia Wang; Tianlin Li; Han Chen; Yinghao Liao; Hong Sun; Ran Liu (Environmental Research, 2026)

Dual-functional La/Fe-MOFs-NH2 for real-time visual removal of fluoride in dynamic environments - Jian Wei; Rui Sun; Han Ma; Junyong He; Dandan Yang; Jiandong Lu; Peidong Hong; Yulian Li; Yahui Li; Chao Xie; Zijian Wu; Lingtao Kong (Chemical Engineering Journal, 2026)

Ultrasound-sensitized gas vesicles enable spatiotemporal therapeutics of solid tumors - Juanjuan Li; Yong Liu; Xiaoli Jiang; Jiani Han; Yanqiong Tang; Hong Li; Xiang Ma; Xue Chi; Min Lin; Zhu Liu (Chemical Engineering Journal, 2026)

Adsorption of Methylene Blue using Poly(N-vinylpyrrolidone)-Graphene Oxide Composite: Kinetics, Equilibrium, Thermodynamics, and Mechanisms - Xiaoya Li; Ru Zheng; Guangyu Duan; Zhanfang Cao; Kai Han; Hong Zhong; Xin Ma; Shuai Wang (Water, Air, & Soil Pollution, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

RAD-seq reveals Cenozoic shifts in the palaeogeographic distribution of Trigonobalanus verticillata across the Indochina Peninsula and Malay Archipelago - Ling Hu; Pei-Han Huang; Yi-Gang Song; Shook Ling Low; Guo-Xiong Hu; Shi-Shun Zhou; Lang Li; Yun-Hong Tan; Hong-Hu Meng; Yu-Peng Cun; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Dermal bioaccessibility of organophosphate esters in indoor dust: Influencing factors, release kinetics, and health risk assessment - Zijia Hong; Yu Bon Man; Yue Li; Linying Xiao; Shitong Han; Zhuoyao Chen; Bingyan Lan; Xiaomin Yan; Jiwen Luo; Lixuan Zeng; Yuan Kang (Journal of Hazardous Materials, 2025)

Natural Fe-bearing clay mineral enhanced Fe reduction, pollution attenuation and biotic-abiotic linkage in sediments - Hong Qin; Ying Zeng; Piao Xu; Zhen Wei; Fuqi Wu; Ziwei Wang; Han Wang; Jing Gao; Jiaqi Li; Zhibang Zou (Journal of Hazardous Materials, 2025)

Metabolic flexibility of rhizobacteria drives soil nutrient cycling and enhances rare earth elements hyperaccumulation in ferns colonizing degraded mine ecosystems - Yong-He Han; Xi-Wen Cui; Hai-Bin Han; Yang-Long Jiang; Li-Chao Tong; Jian-Fei Chen; Hong Zhang; Yong Zhang; Zhibiao Chen (Journal of Environmental Management, 2025)

Imidazolium-functionalized cationic covalent organic framework for ultrafast and selective perchlorate removal via anion exchange - Fuqi Wu; Hong Qin; Fuqiang Zhao; Ying Zeng; Aoran Liu; Bingquan Zhu; Zhibang Zou; Shengyi Wu; Jiaqi Li; Han Wang; Piao Xu (Chemical Engineering Journal, 2025)

Nano-TiO2 modified carbon binder framework to enhance electrochemistry and safety performance of LiCoO2 at high charging voltage - Shuangshuang Han; Luyu Gan; Junjie Song; Haichen Li; Bowei Cao; Jiangang Li; Xiqian Yu; Hong Li; Yan Li (Chemical Engineering Journal, 2025)

Predicting and interpreting nitrogen removal performance and functional microbial abundance of single-stage partial nitrification and anammox system using machine learning methods - Xiulin Mu; Fangxu Jia; Shengming Qiu; Yiran Li; Ning Mei; Xingcheng Zhao; Baohong Han; Xiangyu Han; Jingjing Zhang; Hong Yao (Bioresource Technology, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Uncovering the gut microbiome and antibiotic resistome of mammals on the Tibetan Plateau - Chen Tian; Zecheng Tang; Xiaoyu Zhang; Xueqin Yao; Yitian Li; Daohua Zhuang; Yu Luo; Teng Li; Liyan Bai; Fangfang Zhao; Lei Zhu; Guolin Shi; et al. (Science China Life Sciences, 2025)

Enhanced production of eicosapentaenoic acid and fucoxanthin in Phaeodactylum tricornutum via a two-stage strategy with multifactorial synergistic effects - Xin Dong; Meng-Han Zhao; Chen-Xi Li; Xiao Lin; Ning Ma; Hong-Jin Qiao; Dian-Feng Han; Ying-Jiang Xu (Journal of Applied Phycology, 2025)

Integrated Geology-Geophysics Exploration of Rare Metal Deposits in the Yidun Island Arc Collisional Orogen - Rong Yang; Yu Peng; Li Qing; Qian-kun Liu; Xue-feng Hao; Han Wu; Jun-bo Fan; Hong-juan Chen; Tao Yang (Applied Geophysics, 2025)

Robust Relative Space Motion Control of Underwater Vehicles Using Time Delay Estimation - Gun Rae Cho; Hyungjoo Kang; Min-Gyu Kim; Sungho Park; Chulhee Bae; Han-Sol Jin; Seongho Jin; Ji-Hong Li (Journal of Marine Science and Engineering, 2025)
This paper presents a robust trajectory-tracking control framework for underwater vehicles operating in a relative coordinate system. Unlike conventional methods that define trajectories in the world frame, the proposed approach formulates the control problem directly in a moving reference frame, enabling accurate motion control with respect to dynamic and drifting objects affected by environmental disturbances such as ocean currents and waves. This relative-space formulation is particularly advantageous for tasks including diver guidance, floating-object inspection, and docking, where the reference itself is nonstationary. A coordinate transformation is introduced to consistently express the vehicle dynamics in the relative frame. Based on the transformed dynamics, a Time Delay Control (TDC) law is applied to estimate unmodeled dynamics and external disturbances without requiring precise system parameters. Theoretical stability analysis shows that the stability condition of the proposed controller is consistent with that of conventional TDC, allowing similar gain-tuning procedures. Simulation results demonstrate that the proposed controller achieves robust and smooth trajectory tracking even when the reference frame undergoes motion induced by ocean currents.

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Cyanoalanine Synthase encoding gene SlCAS1 regulates tomato fruit ripening by modulating pigment metabolism and ethylene biosynthesis - Song-Li Han; Yu-Qi Zhao; Li-Xia Li; Pedro Garcia-Caparros; Yan-Hong Li; Zhen Wang; Yi-Ang Feng; Kang-Di Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

Evolution of water-carrying capacity and response law of land space pattern in the Three Gorges Reservoir Area - Feng Zhou; Wanshun Zhang; Xin Liu; Hong Peng; Han Xia; Ao Li; Gang Chen; Hao Wang (Land Use Policy, 2025)

Unveiling regulatory network of porcine oocyte IVM using integrated multi-omics - Yufen Jiang; Helin Li; Na Cheng; Yuchen Han; Qiue Xu; Mingjin Li; Muhammad Ameen Jamal; Jianxiong Guo; Honghui Li; Hong-Jiang Wei; Wenmin Cheng (Livestock Science, 2025)

Achieving partial nitritation-anammox in membrane-aerated biofilm reactor by hydroxylamine addition - Ning Mei; Fangxu Jia; Ying Liu; Yiran Li; Xin Qi; Baohong Han; Xu Zhang; Tao Liu; Hong Yao (Journal of Environmental Management, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Inhibitory effect of licochalcone A on dual-species biofilms of Listeria monocytogenes and Staphylococcus aureus: mechanism involved in quorum sensing and application in beef - Ling Jiang; Yilin Han; Xianxuan Li; Kai Zhong; Yanping Wu; Hong Gao (International Journal of Food Microbiology, 2025)

Morphology-Controlled Alumina-Supported MoS2 catalysts for enhancing hydrogenation and hydrodenitrogenation via metal clusters - Chenxi Li; Aiguo Zheng; Hong Nie; Wei Han; Mingfeng Li; Anpeng Hu; Le Zhang; Huifeng Li (Fuel, 2025)

Metabolomic insights into pigment and bioactive metabolite alterations in Eucommia ulmoides leaves: A comparison between new variety and wild-type varieties - Tiannuo Hong; Jiayu Gu; Lu Chen; Xiaolu Wang; Libin Zhou; Xuehu Li; Wenke Bai; Linqi Gao; Xiaodong Li; Guangming Zhao; Juan Han; Luxiang Liu (Food Chemistry, 2025)

Apios americana Medikus tuber starch alleviates diphenoxylate-induced constipation by modulating neurotransmitters and gut microbiota in mice - Tao Li; Min Jiang; Wenhua Ji; Pengjie Han; Jingguo Xu; Hong Liu; Xiao Wang (Food Bioscience, 2025)

Fe(III)-sulfonate complexes as autocatalytic engines: enabling long-lasting peroxydisulfate activation for refractory sulfonic azo compounds elimination - Xin Yu; Tiao Zhang; Hong Chen; Yanlin Han; Shiyi Zhao; Qiancheng Wang; Luying Yu; Yajie Qian; Yanbiao Liu; Xiaoming Zou; Xianying Li; Gang Xue (Environmental Research, 2025)

Cell membrane-inspired controllably degradable polyesters: High barrier and tailored oxidation responsiveness - Qingyang Luan; Xiaolin Duan; Han Hu; Jiayi Li; Kai Lu; Qi Gao; Xiaokun Hong; Dong-Qing Wei; Juan Li; Jinggang Wang; Jin Zhu (Chemical Engineering Journal, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

Biodegradable and non-biodegradable microplastics affect greenhouse gas emissions through chemical diversity and microbial biodiversity - Ying Guo; Yajuan Tang; Yi Xing; Chen Hong; Wei Su; Wei Wen; Haobo Ya; Jiayu Chen; Han Zhang; Duo Zhang; Wenxin Li; Yixiang Chen; et al. (Journal of Hazardous Materials, 2025)

The potential of Cupriavidus sp. DF5525 degrading high concentrations of p-dichlorobenzene - Hong-Lin Ma; Ze-Shen Liu; Qun Han; Yi Yang; De-Feng Li (Journal of Hazardous Materials, 2025)

Short-term high-temperature pretreatment to reduce gaseous emissions and accelerate humification in food waste digestate composting: Performance and mechanisms - Yun Xu; Peng Xu; Haoyu Teng; Shenju Yang; Hong Lang; Linpei Han; Xuya Peng; Ying Wang; Lei Li (Journal of Environmental Chemical Engineering, 2025)

Tailoring molecular structure of coal tar for monolithic phenolic aerogels to reduce enthalpy for solar desalination - Yu Han; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; Lun-Jing Yan (Journal of Environmental Chemical Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Exploring the quality changes of carp roes: perspective from flavor characteristics and microstructure - Gaomin Han; Qiqi Li; Hui Hong; Juan You; Tao Yin; Shanbai Xiong; Ru Liu (Food Research International, 2025)

A cross-dimensional analysis of data-driven short-term load forecasting methods with large-scale smart meter data - Han Li; Miguel Heleno; Wanni Zhang; Kaiyu Sun; Luis Rodriguez Garcia; Tianzhen Hong (Energy and Buildings, 2025)

Laser-engineered carbon hierarchies with multiscale attenuation mechanisms for ultrabroadband microwave absorption - Zhao Li; Nian Li; Yanping Song; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Shudong Zhang; Cui Liu; Min Xi; Congfa Song; et al. (Chemical Engineering Journal, 2025)

Biomimetic hybrid vesicle nanoplatform with Pt-BaTiO3 for sonodynamic-immunotherapy of glioblastoma - Boyan Li; Lili Zhao; Zhe Han; Zhenfei Tang; Jiawei Qiu; Rongrong Zhao; Bowen Feng; Qinran Zhang; Daiyan Wang; Zijie Gao; Ziwen Pan; Yanhua Qi; et al. (Chemical Engineering Journal, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

Seasonal growth and biomass production of cold-tolerant Napier Grass line L2201 - Swee-Suak Ko; Tzu-Rung Li; Jo-Chi Hung; Hsien-Chang Kuo; Min-Jeng Li; Jeng-Bin Lin; Ping-Han Chung; Lin-Hsiang Lee; Yueh-Hua Lin; Hong-Ping Lin; Charles C.-K Chou; Kuo-Chen Yeh (Biomass and Bioenergy, 2025)

Unlocking the power of sesquiterpenoids: phytochemistry and bioactivities in Artemisia (2017–2023) - Li Ping Tang; Tao Liu; Xiao Yu Han; Bin Li; Hong Dong Liu; Xue Mei Gao (Phytochemistry Reviews, 2025)

Integrated source apportionment and risk assessment prioritizes heavy metal control at an abandoned antimony smelter - Xiao-Hong Ma; Zhuan-Ling Shao; Yu-Han Wang; Wei-Di Tu; Li-Bang Ma; Jiao Wang (Environmental Geochemistry and Health, 2025)

Pseudomonas bambusae sp.nov., an Aniline Blue-Decolorizing Bacterium Isolated from Decaying Round Bamboo Culms - Xiao-Long He; Jia-Yan Wang; Jin-Jia Liang; Cheng-Jing Ren; Xin-Yi Guo; Wen-Jie Ke; Min Wu; Hong-Zheng Liu; Min Jin; Fang-Li Sun; Shuai-Bo Han (Current Microbiology, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Dietary purines and health: Metabolism, impact, and regulation - Yuan Song; Qiang Li; Jianfeng Lu; Mengying Ren; Qingli Han; Zhicheng Cai; Hong Wang; Lin Lin; Bin Zheng; Changhu Xue (Trends in Food Science & Technology, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Eremophilane sesquiterpenes from agarwood of Aquilaria agallocha with neuroprotective effect - Yanqiao Xie; Siyu Zhang; Tianqi Chen; Chunge Li; Ruonan Tong; Hong Xu; Yingbo Yang; Zhuzhen Han; Zhengtao Wang; Li Yang (Phytochemistry, 2025)

Flotation performance and characterization evolution of bastnaesite in hydrogen mineral phase transformation process - Shaokai Cheng; Wenbo Li; Hong Peng; Yuexin Han; Peng Gao; Yongsheng Sun (Minerals Engineering, 2025)

Prenatal bisphenol analogues exposure, metabolites in breast milk and offspring anthropometric growth during infancy: The Wuhan twin birth cohort study - Hong Mei; Liqin Hu; Haoshuang Liu; Neng Li; Yunxia Li; Jiali Xu; Hailin Gu; Feiyan Xiang; Meng Yang; Pan Yang; Jianduan Zhang; Han Xiao; et al. (International Journal of Hygiene and Environmental Health, 2025)

Environmental and metabolic influences on daily to hourly element/Cashell of Tridacna derasa cultured under elevated Ba2+ background concentration conditions - Haotian Yang; Hong Yan; Chengcheng Liu; Nanyu Zhao; Shan Liu; Pengchao Zhou; Guozhen Wang; Hanfeng Wen; Tao Han; Jun Li; Jialong Hao; Ruiying Li; et al. (Global and Planetary Change, 2025)

Diaporthein B/ZnO/chitosan biodegradable film for postharvest preservation of apples: Characterization and application - Hui-Fang Du; Fei Cao; Zhi-Hong Xu; Ya-Xian Gao; Ya-Hui Zhang; Sen Pang; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An (Food Packaging and Shelf Life, 2025)

Efficient zinc extraction from industrial wastewater with novel phenyl phosphate for saline wastewater net-zero emission - Shuai Li; Jianguang Yang; Hong Liu; Jia Ning; Bo Han; Shenghai Yang; Hai Yu; Fang Hu; Hongliang Zhang; Yongming Chen (Desalination, 2025)

Two-step cascade upgrading of Caragana korshinskii into bio-oil and biofuel by solvent-mediated selective hydroconversion over a MOF-based Ni@C - Han Wang; Guang-Hui Liu; Xiao-Xue Wang; Xiao-Qi Zhang; Yu-Hong Kang; Yun-Yan Gao; Lu-Yuan Chen; Xia-Long Li; Xian-Yong Wei (Biomass and Bioenergy, 2025)

Cucurbitacin B alleviates DSS-induced experimental colitis by targeting ZNF70 to suppress the NLRP3/STAT3 signaling axis - Shen Cao; Yuhan Wang; Yi Tai; Jing Han; Yanjin Zheng; Can Wang; Hong Xiang Zuo; Ming Yue Li; Yue Xing; Xuejun Jin; Juan Ma (Inflammopharmacology, 2025)

CAFM: a freeware for geochemical data processing and concentration–area fractal modeling and its application for identifying uranium anomalies of different genesis - Jun-Ting Qiu; Jiang-Kun Li; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Applied Geochemistry, 2025)

Estimation of surface duct parameters using AIS data based on Bayesian inversion method - Hong-Guang Wang; Li-Jun Zhang; Jie Han; Li-Feng Huang; Qing-Lin Zhu (Frontiers in Marine Science, 2025)
Automatic Identification System (AIS) operates within a very high frequency (VHF) maritime mobile band, which could be impacted by surface duct seriously. Utilizing AIS signals for atmospheric duct inversion is a relatively new technique in passive remote sensing. This study employs the Bayesian method to conduct inversion of maritime surface ducts based on AIS signals, categorizing surface ducts into surface-based and elevated-surface ducts. Initially, preliminary data on surface-based duct and elevated-surface duct parameters are acquired from historical sounding data, followed by correlation analysis and probability density distribution fitting of these surface duct parameters. Subsequently, the inversion method steps are provided, and using the same measured AIS data, the likelihood function and posterior probability are calculated by directly employing historical samples and samples generated using Latin Hypercube Sampling (LHS), to accomplish the estimation of surface duct parameters. Directly utilizing historical samples and LHS-generated samples for Bayesian inversion can consistently and accurately yield results with an elevated-surface duct, with the latter being slightly more accurate than the former. The root mean square errors for the AIS path loss, calculated using the inverted elevated-surface duct parameters, are 5.9 dB and 4.4 dB when compared with the measured data. In contrast, the error calculated from the inverted surface-based duct parameters is 21.9 dB.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A new fossil record of Adiantum (Pteridaceae) from Oligocene of Qaidam Basin, Northwest China and its palaeoenvironmental implications - Hong-Yu Chen; Tao Yang; Ya Li; Dieter Uhl; Lei Han; Jia-Hao Cai; Li Zhang; Yong-Dong Wang; De-Fei Yan (Palaeoworld, 2025)

Mechanistic insights into ozone-induced asthma exacerbation: role of oxidative stress and IL-33 - Xinyi Fang; Bin Pan; Yuanting Xie; Wenpu Shao; Jingyu Li; Dongyang Han; Xiaoqing Hong; Wenyue Tu; Yifan Zhao; Jiaojiao Wu; Yaning Zhu; Yubin Zhang; et al. (Journal of Hazardous Materials, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Sex-and stage-specific effect of prenatal exposure to organophosphate esters with children's physical growth patterns and adiposity rebound timing: Modification by breastfeeding - Xing Wang; Juan Tong; Han Li; Mengjuan Lu; Yuan Liu; Hong Gan; Yifan Wang; Menglong Geng; Xuejiao Qie; Xiulong Wu; Hui Gao; Beibei Zhu; et al. (Journal of Hazardous Materials, 2025)

Seawater intrusion causes substantial release of dissolved organic carbon in coastal paddy soils - Wenting Chi; Yang Yang; Pei Wang; Chao Guo; Zebin Hong; Shiwen Hu; Kuan Cheng; Shan Wang; Han Li; Qi Wang; Ying Li; Yang Wu; et al. (Geochimica et Cosmochimica Acta, 2025)

Non-allergenic mixed T cell epitope peptides for preventing Scy p 9 allergic reactions - Xinrong He; Xinyu Han; Yang Yang; Fajie Li; Dongxiao Li; Lianzhong Luo; Hong Liu; Guixia Chen; Xiaomei Chen; Guangming Liu (Food and Chemical Toxicology, 2025)

Constructing entwined TiN@CNT hybrid network via hydrogen bonding self-assembly towards photothermal and durable superhydrophobic anti-/de-icing - Lingtong Li; Zhiheng Zhao; Xiaoying Ji; Dong Han; Hong Wu; Dongliang Li; Shaoyun Guo (Chemical Engineering Journal, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

SGLT2i continuously prevents cardiac hypertrophy by reducing ferroptosis via AMPK up-regulation - Bing-bing Zhao; Jiao Wang; Lu-lu Zhang; Chao Li; Hong-hong Xue; Li Zhao; Qing-hua Han; Hong-tao Shi (Molecular and Cellular Biochemistry, 2025)

CO2 enrichment enhances biomass density and C:N:P ratios in phytoplankton assemblage in the coastal water of the Taiwan Strait - Yumeng Pan; Xiang Yang; Jinlong Shang; Xi Liu; Yinrui Wang; Junqin Cai; Yubin Hu; Kui Xu; Zhengke Li; Yonghe Han; Hong Zhang; Hun Xue; et al. (Journal of Applied Phycology, 2025)

Calcium-O-Sr-Nd isotope evidence for the origin of REE-bearing carbonatite from metasomatized lithospheric mantle without recycled carbonate - Xing-Hui Li; Ming-Cai Xie; Kui-Feng Yang; Kan Li; Chun-Ming Han; Hai-Dong She; Gai-Zhong Liang; Xiao-Chun Li; Hong-Rui Fan (Contributions to Mineralogy and Petrology, 2025)

Coupling soil bacterial and fungal community traits to multifunctionality in grassland ecosystem - Chenxiao Ding; Yaowei Liu; Marcela Hernández; Han Sun; Shuo Jiao; Hong Pan; Tida Ge; Kankan Zhao; Qichun Zhang; Jianming Xu; Yong Li (Agriculture, Ecosystems & Environment, 2025)

Analysis of the response mechanism in lipid degradation of key gene LDH1 knockout strains of Saccharomyces cerevisiae under levulinic acid stress - Yulei Chen; Jiaye Tang; Qian Li; Wenli Xin; Ximeng Xiao; Borui Mou; Jialian Li; Fujia Lu; Chun Fu; Wencong Long; Hong Liao; Xuebing Han; et al. (Archives of Microbiology, 2025)

Did Hainan Island (Southern China) Undergo Significant Cenozoic Tectonic Displacement, and Impact Its Biota's Sourcing and Evolution? - Pei‐Han Huang; Yi‐Gang Song; Jie Li; Hong‐Hu Meng (Journal of Biogeography, 2025)
Aim A significant Cenozoic tectonic displacement of Hainan Island has been proposed, suggesting that the island underwent southeastward movement from an Eocene connection with Vietnam and Guangxi to its current location. This hypothesis has been adopted in some studies to explain the biotic origin of Hainan Island. In this study, we aim to critically evaluate the validity of this hypothesis based on available evidence. Location Hainan Island and its nearby areas. Taxon No specific taxon. Methods We reviewed the relevant literature and examined the geological, palaeomagnetic, and biological evidence for the proposed tectonic displacement. Results We found that the proposed drift scenario primarily stemmed from palaeomagnetic estimates and simplified geological schematic diagrams, neither of which provided robust evidence or a comprehensive explanation for such movement. Our evaluation incorporating geological, palaeomagnetic, and biological data reveals no definitive evidence for large‐scale displacement. Main Conclusions Given the complex biogeographic patterns of Hainan Island, we argue that discussions on its origin and evolution should adopt a more cautious attitude, avoiding reliance on assumed drift mechanisms without substantial supporting evidence.

Valorization of marine crustacean shells waste via fermentation technology: A comprehensive review on derived value-added compounds and enhancing their industrial applications - Samad Tavakoli; Qing Li; Wenyu Han; Huijuan Zhang; Ma Hui; Luming Deng; Armin Mirzapour Kouhdasht; Yuqing Tan; Yongkang Luo; Hui Hong; Kefeng Wu (Waste Management, 2025)

Simultaneous high molecular weight PAHs degradation and chromate and arsenite detoxification by Altererythrobacter sp. H2 - Qun Han; Mei-Ling Yang; Ze-Shen Liu; Ying-Hao Zhao; Xue-Hui Liu; Guo-Min Ai; Wei-Hong Qin; Xing-Yu Liu; De-Feng Li (Journal of Hazardous Materials, 2025)

Two-step cascade degradation of Dongming lignite over Mo/N co-doped ZIF-67-based Co-Mo15@NC - Guang-Hui Liu; Hao-Dong An; Han Wang; Ya-Jun Ma; Yan-Jun Li; Yu-Hong Kang; Jie Kang; Wei Zhao; Sheng-Kang Wang; Xian-Yong Wei (Fuel, 2025)

IoT-based retrofit information diffusion in future smart communities - Lei Shu; Dong Zhao; Wanni Zhang; Han Li; Tianzhen Hong (Energy and Buildings, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Cytogenetic characterization of a novel wheat-rye 2R (2D) substitution line YT9 conferring powdery mildew resistance from the three-leaf stage and physical mapping of PmYT9 - Hanwen Yan; Guohao Han; Tiantian Gu; Zhipeng Shi; Lijun Cao; Jing Wang; Hong Liu; Chenlong Wang; Shiyu Zhuo; Lihui Li; Diaoguo An (Theoretical and Applied Genetics, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Air pollution of PM2.5-bound PAHs in urban Chongqing, China from 2015 to 2022: Concentration, source tracking and health risk - Bofei Fu; Shang Li; Shushu Lan; Xiaowei Peng; Chongjun Ran; Nanyan Li; Hong Li; Lun Xiao; Guohua Zhao; Junrui Chang; Jingxiu Han; Yunyun Wu; et al. (Urban Climate, 2025)

Newer wheat cultivars achieved greater yield and water productivity through root and canopy synergies in the North China Plain - Yehan Fu; Jiayue Dai; Han Yang; Biwei Gao; Yuzhao Ma; Yunzhou Qiao; Yongpeng Li; Hong Yang; Baodi Dong (Field Crops Research, 2025)

Freestanding vanadium oxides/carbon hybrid cathode with long-term cyclability at low current density for flexible aqueous zinc ion batteries - Zhouyang Qin; Gaoxu Han; Yilin Yang; Shengle Hao; Lingxiao Yu; Yuxiao Lin; Yunsong Li; Ruitao Lv; Wanci Shen; Feiyu Kang; Zheng-Hong Huang (Chemical Engineering Journal, 2025)

Butterfly-inspired structures on strong and tough metagel for enhanced passive radiative and evaporative cooling - Di Han; Jipeng Fei; Yongping Long; Yuanhang Yang; Anna Lushnikova; Hiba Mhiri; Christophe Ménézo; Man Pun Wan; Hong Li; Xuan Zhang; Bing Feng Ng (Chemical Engineering Journal, 2025)

Deciphering the contribution of algae-rich microbial communities to dissolved organic matter in a eutrophic lake with distinct rainy and dry seasons - Han Yan; Hong-Fa Guo; Jia-Xun Li; Zhuo Chen; Shi-Qi Yin; Mo-Yu Shen; Yi Tao; Yin-Hu Wu; Hong-Ying Hu (Algal Research, 2025)

Enhancing the coupling coordination of soil–crop systems by optimising soil properties and crop production via subsoiling - Jingyi Shao; Ling Liu; Jichao Cui; Hong Yang; Yecheng Zhang; Ruxin Li; Yi Lv; Yifei Ma; Qin Fang; Shengkai Sun; Siyu Chen; Huifang Han (Soil and Tillage Research, 2025)

Revealing the miscibility chemistry of ionic liquids in water-in-salt electrolytes toward high-voltage and high-temperature aqueous potassium-ion supercapacitors - Jianchao Chen; Guanghao Zhang; Hong Zhang; Shuxian Zhang; Qingyu Li; Chunyan Zhu; Xiaoge Man; Zhiwei Zhang; Yuanchang Shi; Tao Li; Ye Han; Mengqi Zhang; et al. (Science Bulletin, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Investigating the influence of insoluble pulp particles on flavor retention and characterization of freshly squeezed and pasteurized mandarin juice - Yujiao Cheng; Min Zhang; Leng Han; Guijie Li; Min Hong; Hua Wang; Houjiu Wu; Linhua Huang (Food Research International, 2025)

High level production of a β-fructofuranosidase in Aspergillus niger for the preperation of prebiotic bread using in situ enzymatic conversion - Susu Han; Hong Liu; Shusen Li; Ziwei Zheng; Qiaojuan Yan; Zhengqiang Jiang (Food Research International, 2025)

Prediction of the exposure profile of bisphenol A in Chinese population by physiologically-based pharmacokinetics modeling - Jun He; Li Zhang; Hong Jin; Daoyuan Yang; Li Jia; Bin Han; Haixia Sui; Jiabin Guo (Environmental Pollution, 2025)

Organic acid promoting the degradation of nonylphenol by persistent free radicals in biochar - Jie Ji; He Zhang; Feichao Zhang; Yao Wu; Han Zhang; Ziwei Mei; Wenxuan Zhou; Liang Li; Hong Tao; Meicheng Wen (Chemical Engineering Journal, 2025)

Mode transitions in Hall effect thrusters by Varying duty ratio under pulsating operation - Haochen Ma; He Zheng; Tiance Liang; Jiapeng Li; Liqiu Wei; Liang Han; Hong Li; Yongjie Ding (Advances in Space Research, 2025)

Bicyclic polyprenylated acylphloroglucinol-related meroterpenoids as potent DRAK2 inhibitors from Hypericum patulum - Jin-Chang Huang; Xin-Yu Jia; Yi-Fan Lv; Hong-Hong Xu; Ming Han; Qiang-Qiang Yu; Yu-Ting Lu; Hong-Xun Yang; Yang Yang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Impact of particle geometry and critical dimensionless parameters on hydraulic collection performance of near-wall particles - Xiu Li; Lixin Xu; Yajiao Liu; Peilin Dou; Zhichao Hong; Chaoshuai Han (Ocean Engineering, 2025)

Fertilization-recruited Actinomycetota enhances nutrient and energy metabolisms to favor plant growth and arsenic accumulation in Pteris vittata - Yong-He Han; Yi-Xi Li; Xi-Wen Cui; Ying Zhu; Hong Zhang; Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Surfactant-assisted spent fried oil for gasification slag flotation: An innovative approach for simultaneous waste oil utilization and slag separation - Rui Han; Shizhi Ruan; Anning Zhou; Zhen Li; Hong Wang; Ningning Zhang (Journal of Environmental Chemical Engineering, 2025)

Biodegradation of skatole by Bacillus subtilis GDAAS-A32 and its inhibition for odor emissions from swine manure - Jing-Yi Hu; Xue-Ying Han; Hong-Pin Chen; Jia-Zhou Li; Zhi-Lin Wang; Xiao-Chun Luo; Jun-Jin Deng (Journal of Environmental Chemical Engineering, 2025)

Widely targeted metabolomics analysis reveals dynamic changes in metabolites of 'Hass' avocado during postharvest ripening period - Ying Xin; Na Li; Hong-Tao Zhu; Ya-Zhi Li; Han-Zhang Xiang; Jia-Huan Shang; Man Zhang; Ying-Jun Zhang (Food Chemistry, 2025)

Preparation, characterization, and solubility enhancement of octenyl succinate anhydride debranched starch/1-Octacosanol nanocomplex - Meiru Ji; Baoxin Gu; Junqing Han; Lingjin Li; Yahui Gao; Li Cheng; Zhengbiao Gu; Yan Hong (Food Bioscience, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

Co-occurrence of mcr-9 and blaNDM-5 in Multidrug-Resistant Enterobacter hormaechei Strain Isolated from a Patient with Bloodstream Infection - Ru Li; Junfeng Wang; Weiting Zhang; Chenhao Zhao; Mingxiao Han; Hong Du; Haifang Zhang (Current Microbiology, 2025)

Recent advances in the role of gasotransmitters in necroptosis - Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Ti Chu; Yan-Wen Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Redox condition changes in the Ross Sea, Antarctica, since the last glacial maximum - Yizhuo Wang; Yi Zhang; Xibin Han; Li Lin; Yukai Hong; Rui Han; Yun Liu; Pengyun Ma; Qian Ge; Xiaohu Li (Acta Oceanologica Sinica, 2025)

Dietary supplementation of Litsea cubeba oil promotes growth and intestinal immunity in GIFT tilapia - Fu-Yan Chen; Ying Bai; Gan Yang; Han-Jing Yan; Liu-Yang Li; Zhi-Mou Liu; Ju-Ping Wen; Zhen-Bin Wang; Jun-Hong Xia; Meng-Ling He (Aquaculture, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

Assessing the effectiveness of green consumption policy in China: Evidence from social media data - Junling Liu; Ruyin Long; Hong Chen; Lu Qin; Han Huang; Qian Li; Xiangyang Ye (Journal of Environmental Management, 2025)

Late Quaternary vertical throw rates along the Gyaring Co fault in central Tibet - Duo Wang; Lichun Chen; Hong Chang; Shugang Kang; Yongshun Jia; Jinhua Du; Fei Han; Yanbao Li; Gongming Yin; Wenjun Zheng; Xulong Wang (Journal of Asian Earth Sciences, 2025)

Frabrication of carboxymethylchitin nanofibers and fish gelatin hybrid gels with robust gel performance - Rongqiang Chen; Shuai Zhang; Jiao Jiao Sun; Lijuan Xu; Yuan Duan; Fengchen Li; Yanhui Han; Xiao Fu; Meng Wang; Yong Hong Meng; Yurong Guo (Food Hydrocolloids, 2025)

Semi-sacrificial fabrication of binder-free lithium-aluminum layered double hydroxides adsorbents for lithium extraction - Jinqiang Gao; Mei Hong; Jiatao Zhong; Shengnan Na; Yuqing Su; Han Li; Mingyu Hu; Shihe Yang (Desalination, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Coplanar two-dimensional Cu-MOF with dual-Cu sites for electrocatalytic CO2 reduction to C2H4 - Yu-Peng Han; Zi-Rui Wang; Ya-Yu Yan; Qiao-Hong Li; Ping Shao; Hai-Xia Zhang; Li-Li Han; Fei Wang; Jian Zhang (Chemical Engineering Journal, 2025)

Dual physically crosslinked azobenzene liquid crystal elastomers programmable for multi-modal information encryption - Jia-Xin Yang; Xue-Li Zhang; Lu Yin; Jie Jiang; Ting Liu; Jing-Yu Liu; Zhi-Ting Xu; Hong-Yuan Bai; Hong-Wei Ma; Yue Zhao; Yang Li; Li Han (Chemical Engineering Journal, 2025)

Synthesis of furan-based cationic biopolyamides and their removal abilities for perfluoroalkyl and polyfluoroalkyl substances - Hong-Hui Shu; Liu-Qi Shi; Hui-Qin Zhang; Yun Liu; Sheng-Li Han; Jing-Yi Rao; Cheng-Mei Liu (Chemical Engineering Journal, 2025)

Corrigendum to “Maternal Zearalenone exposure impacted ovarian follicle formation and development of suckled offspring” [Sci. Total Environ. 788 (2021) 147792] - Li Kong; Ai-Hong Zhao; Qian-Wen Wang; Yan-Qin Feng; Zi-Hui Yan; Ming-Hao Li; Fa-Li Zhang; Han Wang; Kai-Yu Shen; Ying Liu; Yu-Jiang Sun; Wei Shen; et al. (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Intelligent sensing platform based on europium-doped carbon dots for dual-functional detection of ciprofloxacin/Ga3+ and its tracking in vivo - Le Liang; Su-qian Cai; Yan-li Leng; Chan Huang; Yong-qing Liu; Ye Wang; Li Luo; Mei Han; Xiao-hong Li; Xiao-hua Cai (Journal of Hazardous Materials, 2025)

Biogenic amines degradation ability of Saccharomyces cerevisiae I45 and Pichia sp. NW5 & LB60 and their application in beer fermentation - Kexin Hong; Chenyu Li; Jingya Ai; Xiaoyu Han; Bing Han; Qiuxing Qin; Huan Deng; Tianyang Wu; Xiaoxuan Zhao; Weidong Huang; Jicheng Zhan; Yilin You (Food Research International, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

Electrostatic repellent dispersion method for green and cost-effective aqueous radiative cooling paint - Jipeng Fei; Di Han; Kai Zhou; See Wee Koh; Junyu Ge; Jun Yan Tan; Bing Feng Ng; Zhong Chen; Lili Cai; Hong Li (Building and Environment, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Medium modification of Cynanchum wilfordii adventitious root culture for the production of C21 steroidal glycosides, polysaccharides, and polypeptides using orthogonal design methods - Han-Xi Li; Yu-Qing Guo; Wei-Qi Ye; Zhong-Yu Zhou; Ling-Hong Bai; Xuan-Chun Piao; Mei-Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2025)

Seipin Deficiency Impairs Motor Coordination in Mice by Compromising Spinal Cord Myelination - Hong Chen; Wenru Wang; Wenli Cui; Chuanyun Tu; Yuanyuan Han; Chengwu Zhang; Liu Yang; Xintao Huang; Qin Zhang; Li Lu (NeuroMolecular Medicine, 2025)

A new isoflavone from the stems of Derris eriocarpa How - Ying Liu; Zhen-Xin Zhu; Yue Lu; Cong Wang; Hong-Cun Liu; Juan Meng; Jin Qi; Xiao-Ning Huang; Xiao-Mei Lu; Wen-Sen Lu; Shu-Han Luo; Hai-Na Liang; et al. (Natural Product Research, 2025)

Microwave replacing traditional concentrating process to promote the synthesis of mumefural in Prunus mume extract - Teng Long Miao; Shan Qin; Xiao Hong Chen; Long Yun Chen; Yan Qing Han; Yan Li Yuan; Xin Rui; Wei Li; Qiu Qin Zhang (Food Research International, 2025)

Hypoglycemic peptide preparation from Bacillus subtilis fermented with Pyropia: Identification, molecular docking, and in vivo confirmation - Guixin Han; Yuxian Xu; Jiayu Li; Ke Li; Xinxing Xu; Xin Gao; Yuanhui Zhao; Hong Jiang; Xiangzhao Mao (Food Chemistry, 2025)

Zein film loaded with Fructus Ligustri Lucidi essential oil: Preparation, characterization and application in fresh-cut apple preservation - Hong Chen; Chengyan Yang; Xiangxun Zhuansun; Yao Li; Rui Han; Longgang Wang; Shengqing Ding; Qi Liu (Food Control, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

CoOx confined in layered montmorillonite serving as PMS activator for wastewater treatment - Piao Xu; Hong Qin; Quyang Tian; Ziwei Wang; Yangzhuo He; Fuqi Wu; Li Du; Guangfu Wang; Wenyang Li; Ying Zeng; Han Wang (Chemical Engineering Journal, 2025)

Responses of surface ozone under the tropical cyclone circulations: Case studies from Fujian Province, China - Keyue Wang; Rui Zhao; Qunyong Wu; Jun Li; Hong Wang; Han Lin (Atmospheric Pollution Research, 2025)

Anti-lung cancer synergy of low-dose doxorubicin and PD-L1 blocker co-delivered via mild photothermia-responsive black phosphorus - Hua-Zhen Xu; Fei-Xiang Chen; Ke Li; Quan Zhang; Ning Han; Tong-fei Li; Yong-Hong Xu; Yun Chen; Xiao Chen (Drug Delivery and Translational Research, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

Characterization of the complete genome of a novel allexivirus infecting Sauropus androgynus in China - Li-Juan Zhu; Lan-Yi Su; Xing Chen; Shifang Pan; Fagang Xia; Yan-Hong Han; Zhongtian Xu; Qian Xu (Archives of Virology, 2025)

Roseobacter sinensis sp. nov., a marine bacterium capable to synthesize arachidonic acid - Hong-Chuan Wang; Meng-Han Huang; Dan-Yuan Guo; Wen-Li Liu; Zi-Wen Yang; Dao-Feng Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

A high selective separation method for high-purity polysaccharides from dandelions by density-oriented deep eutectic solvent ultrasonic-assisted system - Han Zhang; Yu Lin; Yanan Bao; Wen-Jing Li; Bo Hong; Min Zhao (Sustainable Chemistry and Pharmacy, 2024)

Long-term PS micro/nano-plastic exposure: Particle size effects on hepatopancreas injury in Parasesarma pictum - Ji Liang; Anisah Lee Binti Abdullah; Yiming Li; Hong Wang; Sen Xiong; Mingming Han (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Tri-functional molecular junction photocatalyst for cascade synthesis of N-benzylideneaniline derivatives - Xiao-Xin Li; Xiao-Xuan Hong; Zi-Yi Liao; Lei Zhang; Run-Han Li; Ying Zeng; Yue Liu; Shun-Li Li; Ya-Qian Lan (Science Bulletin, 2024)

Mechanisms of selectivity for azadirachtin in honeybees (Apis cerana): A new strategy for avoiding thiamethoxam ingestion - Hao Wu; Sheng-nan Li; Rui-quan Hou; Peng-rui Du; Kun-yu Zhao; Muhammad Zeeshan; Han-hong Xu; Zhi-xiang Zhang; Pei-wen Zhang (Pesticide Biochemistry and Physiology, 2024)

Anti-photoaging activity of triterpenoids isolated from Centella asiatica - Yi-yun Dang; Tao Liu; Yu-die Liu; Jia-yi Li; Yi Jing; Miao-jie Yang; Han Zhang; Miao-miao Jiang; Hong-hua Wu; Wen-zhi Yang; Nan Li; Peng Zhang (Phytochemistry, 2024)

A novel approach for underwater acoustic signal denoising based on improved time-variant filtered empirical mode decomposition and weighted fusion filtering - Guohui Li; Yaoyu Han; Hong Yang (Ocean Engineering, 2024)

Design and optimization of an integrated UF-NF membrane process for treating rare earth refining wastewater - Yiwen Wang; Shuanglin Gui; Qinliang Jiang; Pei Han; Hong Wang; Jianping Deng; Tao Chen; Jianxin Li (Journal of Water Process Engineering, 2024)

The removal of tris(2-chloroethyl)phosphate by a composite biosorbent: Preparation, performance and mechanism - Yiyuan Li; Hong Huang; Long Han; Sixian Guo; Rongliang Qiu; Shuona Chen (Journal of Water Process Engineering, 2024)

Artemisia argyi leaf powder improves soil properties and recruits Sphingobium bacteria to promote the growth and yield of Pinellia ternata - Jinxin Li; Kaili Qu; Lu Wei; Hong Chen; Huixia Cai; Jingyi Zhang; Likun Mei; Bingsen Liu; Yifan Han; Yuhuan Miao; Dahui Liu (Journal of Environmental Management, 2024)

Insights into pore structure-activity relationships of iron catalysts supported on fluorine–cerium nanosheets for heterogeneous Fenton oxidation - Jing Lv; Hui Ye; Shurui Han; Jinli Zhao; Guodong Yang; Han Zhang; Xiaojian Fu; Jing Zhang; Qingping Xin; Lizhi Zhao; Hong Li; Ligang Lin; et al. (Journal of Environmental Chemical Engineering, 2024)

Enhanced flotation separation of coal gasification fine slag by composite collectors containing polar fatty acids - Ningning Zhang; Mengyan Cheng; Rui Han; Zhen Li; Anning Zhou; Hong Wang (Journal of Environmental Chemical Engineering, 2024)

Nitrogen and sulfur metabolism in anaerobic hydrogen-producing microbiome as a challenge for 2,4-DCP dechlorination - Jiunn-Jyi Lay; Shi-Hong Li; Chang-Lung Han; Wei-Zhen Zhong (Journal of Environmental Chemical Engineering, 2024)

Integrating a high-energy activation method for the sustainable treatment of iron smelting slag, phosphogypsum, and arsenic-contaminated water - Donghui Chen; Jie Tan; Hong Li; Yanmin Lin; Fangming Nan; Qingwen Han; Wei Zhan (Journal of Environmental Chemical Engineering, 2024)

The effect of carbon taxes and subsidies on forest carbon sequestration in China - Yizhu Long; Zhen Zhu; Yanzhen Hong; Zhiwen Gong; Hua Li; Han Zhang (Forest Policy and Economics, 2024)

Highly sensitive zinc oxide nanoparticle composite film with deep learning-assisted mobile technology for enhanced food freshness monitoring - Muhammad Waqas; Zhengjie Chen; Yawar Abbas; Ambar Farooq; Xiaoxue Han; Hong Zhong; Xianwen Ke; Houbin Li; Xinghai Liu (Food Bioscience, 2024)

Partitioned granular sludge coupling with membrane-aerated biofilm reactor for efficient autotrophic nitrogen removal - Ning Mei; Fangxu Jia; Hui Wang; Zhifeng Hu; Baohong Han; Yao Chen; Xingcheng Zhao; Xiangyu Han; Jingjing Zhang; Dongmei Li; Hong Yao; Jianhua Guo (Bioresource Technology, 2024)

Optimizing ABA-based chemically induced proximity for enhanced intracellular transcriptional activation and modification response to ABA - Zeng Zhou; Yue-Qi Wang; Xu-Nan Zheng; Xiao-Hong Zhang; Lu-Yao Ji; Jun-You Han; Ze-Cheng Zuo; Wei-Liang Mo; Li Zhang (Science China Life Sciences, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Thalassospira aquimaris sp. nov. and Winogradskyella marincola sp. nov. two marine bacteria isolated from an agar-degrading co-culture - Zi-Yue Fu; Dao-Feng Zhang; Meng-Han Huang; Hong-Chuan Wang; Xiao-Ye Chen; Yu-Fang Yao; Yang Yuan; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Mechanism study on the synergistic degradation of DMAC wastewater by electrocatalytic carbon membrane reactor coupled with persulfate dual catalysis - Hong Wang; Jing Han; Minghui Du; Zhaohui Yin; Qingqing Wang; Xiaolong Ge; Zhen Yin; Jianxin Li (Journal of Water Process Engineering, 2024)

A high-permeability method for extracting purple yam saponins based on ultrasonic-assisted natural deep eutectic solvent - Yu-Jiao Hou; Peng-wei Wang; Han Zhang; Ying-Ying Fan; Xu Cao; Yan-Qiong Luo; Qian Li; Mosesmanaanye Njolibimi; Wen-jing Li; Bo Hong; Chun-jie Zhao (Food Chemistry, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

Improving the removal rate of bisphenol A and Cu2+ from water using P/N coexisting β-cyclodextrin-based adsorbents by enhancing adsorbents-pollutants interactions - Xiuqin Fang; Chang Wang; Hong-Hui Shu; Sheng-Li Han; Cheng-Mei Liu (Carbohydrate Polymers, 2024)

Hohaiivirga grylli gen. nov., sp. nov., a New Member of the Family Methylobacteriaceae, Isolated from Cricket (Gryllus chinensis) - Hong-Chuan Wang; Meng-Han Huang; Dan-Yuan Guo; Wei He; Lu Wang; Zi-Yue Fu; Wen-Jun Li; Ai Hua Zhang; Dao-Feng Zhang (Current Microbiology, 2024)

From Skin to Gut: Understanding Microbial Diversity in Rana amurensis and R. dybowskii - Ming-he Yang; Hong Liu; Hao Wang; Zhao-ning Lu; Xiao-yun Han; Zhi-wen Luo; Li-gang Wu; Qing Tong (Current Microbiology, 2024)

A fire risk pre-warning framework for high-rise buildings based on unascertained method - Li-Ning Zhang; Xiang-Ming Wang; Jing An; Hong Xian Li; Jiao-Qian Guo; Guo-bo Han; Peng-Fei Gou (Environmental Science and Pollution Research, 2024)
The growing global interest in preventing and controlling fires in high-rise buildings reflects the increasing significance of this issue today. This research aims to establish an early warning framework for fire risk in high-rise buildings. Firstly, considering the importance of a scientific indicator system for the application of the model, this study combines the event analysis method with the building design fire code to identify 11 key risk factors that have a far-reaching impact on the prevention of fires in high-rise buildings. Based on identifying the risk factors, a high-rise building fire risk warning tree is also established, which scientifically solves the problem of the indicator system of the warning object. Subsequently, in response to the various complex issues arising from the uncertainty of fire occurrence in high-rise buildings, this study adopts the unascertained method to model the fire risk of high-rise buildings for early warning. In addition, the developed methodology was empirically validated through case studies and analyses of empirical data on fire risks in nine representative high-rise buildings. The results of the unascertained method were also compared with the results of the K-means method, from which it was concluded that the unascertained method can predict building fires more accurately. The research results provide a reliable decision support system for fire disaster prevention and control in high-rise buildings.

Multi-omics reveals the particle size effect of nanoplastics on the hepatopancreas and intestinal toxicity of crustacean model Neospoda palmata - Mingming Han; Tian Zhu; Zihan Zhou; Yiming Li; Cigang Yu; Ji Liang; Hong Wang; Qin Si; Qichen Jiang (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Associations of prenatal exposure to individual and mixed organophosphate esters with ADHD symptom trajectories in preschool children: The modifying effects of maternal Vitamin D - Han Li; Juan Tong; Xing Wang; Mengjuan Lu; Fengyu Yang; Hui Gao; Hong Gan; Shuangqin Yan; Guopeng Gao; Kun Huang; Yunxia Cao; Fangbiao Tao (Journal of Hazardous Materials, 2024)

Differential responses of soil phosphorus fractions to varied nitrogen compound additions in a meadow steppe - Heyong Liu; Chunbo Li; Jiayun Zhang; Hong Ji; Yinhong Liao; Xiaomeng Ma; Qiuhua Li; Yuxue Zhang; Liangchao Jiang; Ruzhen Wang; Xingguo Han; Yong Jiang (Journal of Environmental Management, 2024)

Dicranopteris pedata improves soil quality by enhancing nutrient deposition, decreasing metal concentration, and boosting microbial diversity on abandoned rare earth elements mining sites - Xi-Wen Cui; Zhen-An Xu; Xian Chen; Zhi-Biao Chen; Jia-Bing Li; Rong-Rong Xie; Hong Zhang; Yong Zhang; Yong-He Han (Journal of Environmental Chemical Engineering, 2024)

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

Passivating perovskite surface defects via bidentate chelation for high-performing solar cells - Mengting Han; Li’e Mo; Zhiqian Yang; Aiqing Sun; Hong Zhang; Bolin Li; Zhaoqian Li; Xianxi Zhang; Rahim Ghadari; Yang Huang; Linhua Hu (Chemical Engineering Journal, 2024)

Mechanically customizable lignin bio-elastomers based on tailorable multiscale microstructures - Dengfeng Wang; Mengyuan Diao; Yaotao Shan; Han Wu; Lin Liu; Zihan Li; Haojie Hong; Juming Yao (Chemical Engineering Journal, 2024)

Heterostructure-anchored 3D CNT-bridged graphene architecture via layer-by-layer structural engineering for thick electrodes of supercapacitors - Yanping Song; Nian Li; Jun Kang; Zhao Li; Na Hong; Shuai Han; Liqing Chen; Shudong Zhang; Cui Liu; Congfa Song; Jiakuan Zhang; Zhenyang Wang (Chemical Engineering Journal, 2024)

Genome Analysis and Safety Assessment of Achromobacter marplatensis Strain YKS2 Strain Isolated from the Rumen of Yaks in China - Dapeng Li; Songwei Han; Kang Zhang; Guowei Xu; Hong Zhang; Fubing Chen; Lei Wang; Qin Liu; Zhiting Guo; Jingyan Zhang; Jianxi Li (Probiotics and Antimicrobial Proteins, 2024)

Global risk dynamics of Borrelia miyamotoi in the context of climate change - Tian Tang; Hong‐Han Ge; Tian Ma; Meng‐meng Hao; Shuai Chen; Chen‐Long Lv; Yun‐Bo Qiu; Yan‐He Wang; Yao Tian; Jin‐Jin Chen; Shuai Yuan; Qian Wang; et al. (Environmental Microbiology, 2024)
The impact of Borrelia miyamotoi on human health, facilitated by the expanding geographical distribution and increasing population of Ixodes ticks, remains obscure in the context of global climate change. We employed multiple models to evaluate the effect of global climate change on the risk of B. miyamotoi worldwide across various scenarios. The habitat suitability index of four primary vector tick species for B. miyamotoi , including Ixodes persulcatus , Ixodes ricinus, Ixodes pacificus and Ixodes scapularis , was projected using a boosted regression tree model, considering multiple shared socio‐economic pathway scenarios over various time periods. The modelling analysis reveals that, apart from I. scapularis , future global warming will result in a northward shift in the other three vector tick species and a gradual reduction in suitable habitats. Random forest models indicate consistent changes in B. miyamotoi and its primary tick species, with potential risk areas shrinking and shifting northward, particularly in the eastern USA, northeastern and northern Europe and northeast Asia. These findings highlight the urgent need for enhanced active surveillance of B. miyamotoi infection in primary vector tick species across projected potential risk areas. The effect of climate change on B. miyamotoi distribution might have significant implications for public health decision‐making regarding tick‐borne pathogens.

Full Coverage Path Planning for Torpedo-Type AUVs’ Marine Survey Confined in Convex Polygon Area - Ji-Hong Li; Hyungjoo Kang; Min-Gyu Kim; Mun-Jik Lee; Han-Sol Jin (Journal of Marine Science and Engineering, 2024)
In this paper, we present a full coverage path planning (CPP) algorithm for the marine surveys conducted in the convex polygon shaped search area. The survey is supposed to carry out by torpedo-type AUVs (autonomous underwater vehicles). Due to their nonholonomic mechanical characteristics, these vehicles have nonzero minimum turning radius. For any given polygon shaped search area, it can always be partitioned into one or more convex polygons. With this in mind, this paper proposes a novel search algorithm called CbSPSA (Calculation based Shortest Path Search Algorithm) for full coverage of any given convex polygon shaped search area. By aligning the search inter-tracks alongside the edge with the minimum height, we can guarantee the minimum number of the vehicle’s turns. In addition, the proposed method can guarantee the planned path is strictly located inside the polygon area without overlapped or crossed path lines, and also has the total path length as short as possible. Considering the vehicle’s nonzero minimum turning radius, we also propose a sort of smoothing algorithm which can smooth the waypoint path searched by CbSPSA so that the vehicle can exactly follow it. The smoothed path is also guaranteed to be strictly located inside the polygon. Numerical simulation analyses are also carried out to verify the effectiveness of the proposed schemes.

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Efficacy of a new K3-specific bacteriophage for controlling Klebsiella pneumoniae in milk and its potential to disrupt biofilm formation - Pei Li; Yu Zhou; Genglin Guo; Xiayan Qin; Zimeng Hu; Min Li; Zhongming Tan; Yuqing Liu; Xiangan Han; Jiale Ma; Hong Du; Wei Zhang (Food Control, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

A lifelong meta-learning approach for learning deep grey-box representative thermal dynamics models for residential buildings - Jiajia Xie; Han Li; Tianzhen Hong (Energy and Buildings, 2024)

Novel overlapping constructed wetlands with water drops reoxygenation and lightweight fillers for decentralized wastewater treatment - Zhao Shuyuan; Li Guo; Shui Paipai; Nie Wenbo; Qu Han; Yan Jun; Li Hong; Wang Ruiling (Bioresource Technology, 2024)

In vivo EPID-based daily treatment error identification for volumetric-modulated arc therapy in head and neck cancers with a hierarchical convolutional neural network: a feasibility study - Yiling Zeng; Heng Li; Yu Chang; Yang Han; Hongyuan Liu; Bo Pang; Jun Han; Bin Hu; Junping Cheng; Sheng Zhang; Kunyu Yang; Hong Quan; et al. (Physical and Engineering Sciences in Medicine, 2024)

Detachable acoustofluidic droplet-sorter - Dhrubajyoti Das; Shih-Hong Huang; Choa-Li Weng; Chien-Hung Yu; Chao-Kai Hsu; Yung-Chun Lee; Hui-Ching Cheng; Han-Sheng Chuang (Analytica Chimica Acta, 2024)

Anisotropy measurements and characterization of the Qingshankou shale - Qing-feng Li; Xue-hong Yan; Wei-lin Yan; Li Ren; Peng Wang; Jian-qiang Han; Xue Xia; Hao Chen (Applied Geophysics, 2024)

Integrated whole genome sequencing and transcriptomic analysis reveal the biodegradation mechanism of vanillic acid in Herbaspirillum aquaticum KLS-1 - Yong-He Han; Yi-Xi Li; Wen-Qian Qiu; Xi-Wen Cui; Xian Chen; Yong Zhang; Hong Zhang; Shan-Shan Wang (Journal of Environmental Chemical Engineering, 2024)

Conformational transformation of activator strand directly regulates CRISPR/Cas12a system activity for live cell sensing of multiple biomolecules - Qing-Nan Li; Dong-Xia Wang; Zhi-Qi Dai; Shun-Li Wu; Gui-Mei Han; Sha Lu; Li-Na Zhu; Hong-Xin Jiang; De-Ming Kong (Chemical Engineering Journal, 2024)

Enhancing U(VI) removal from highly acidic wastewater through the synergistic effect of diethylenetriaminepenta(methylenephosphonic) acid and meso-SiO2 on nanosized γ-Fe2O3 - Hong Li; Diyun Chen; Weixing Han; Jun He; Gang Song; Lingjun Kong; Minhua Su (Chemical Engineering Journal, 2024)

Targeting GLUT1 degradation with assembling glycopeptide for cancer inhibition - Xia Wu; Jun Shen; Xingyue Jiang; Hong Han; Zenghui Li; Yatong Xiang; Dan Yuan; Junfeng Shi (Chemical Engineering Journal, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

New alkaloids from Polygonatum zanlanscianense Pamp - Xue-Ke Zhang; Zhu-Zhen Han; Li Yang; Peng-Fei Zhang; Hong Zhang; Shou-Jin Liu (Natural Product Research, 2024)

Molecular phylogeny and morphology reveal two new species of Conocybe (Bolbitiaceae, Agaricales) from southwest China - Wenhua Lu; Nakarin Suwannarach; Saisamorn Lumyong; Abdallah M. Elgorban; Dong-Qin Dai; Arun K. Dutta; Li-Hong Han; Saowaluck Tibpromma; Samantha C. Karunarathna (New Zealand Journal of Botany, 2024)

Regulating microbial redox reactions towards enhanced removal of refractory organic nitrogen from wastewater - Ke Shi; Bin Liang; Hao-Yi Cheng; Hong-Cheng Wang; Wen-Zong Liu; Zhi-Ling Li; Jing-Long Han; Shu-Hong Gao; Ai-Jie Wang (Water Research, 2024)

Quantitative reconstruction of a single super rainstorm using daily resolved δ18O of land snail shells - Guozhen Wang; Jibao Dong; Tao Han; Chengcheng Liu; Fan Luo; Haotian Yang; Miaohong He; Guoqiang Tang; Nanyu Zhao; Qian Zhang; Gang Xue; John Dodson; et al. (Science Bulletin, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Why pile-supported building settled continuously after water level was stabilized during dewatering: Clues from interaction between pile and multi aquifers - Xiu-Li Xue; Hai-Yu Sun; Chao-Feng Zeng; Hong-Bo Chen; Gang Zheng; Chang-Jie Xu; Lei Han (Journal of Hydrology, 2024)

Quality enhancement and time reduction in soaking green plum wine using pulsed electric field - Lang-Hong Wang; Bing Yan; Danli Tang; Zhong Han; Jian Li; Xin-An Zeng (Journal of Food Engineering, 2024)

Construction of multidimensional structure model of the Mesoproterozoic Xiamaling shale kerogen, northern North China - Chengbo Guo; Meijun Li; Xiaoqiang Liu; Hong Xiao; Qingyong Luo; Qiuya Han; Wenke Li; Junhao Ren (Fuel, 2024)

Catalytic hydroconversion of aryl ethers to polycyclic alkanes over Ni@MCM-41/β composite zeolite: Aromatic α-carbon activation and hydrogen transfer mechanisms - Guang-Hui Liu; Wen-Ao Shi; Jun Li; Han Wang; Ai-Min Wang; Yu-Hong Kang; Yong Gao; Ni Bai; Jie Kang; Chen Shi; Xian-Yong Wei (Fuel, 2024)

Overcoming genotypic dependency and bypassing immature embryos in wheat transformation by using morphogenic regulators - Ziru Zhou; Yawen Yang; Guo Ai; Miaomiao Zhao; Baozhu Han; Chunjie Zhao; Yiqian Chen; Yuwei Zhang; Hong Pan; Caixia Lan; Chao He; Qiang Li; et al. (Science China Life Sciences, 2024)

Estimating soil salinity in mulched cotton fields using UAV-based hyperspectral remote sensing and a Seagull Optimization Algorithm-Enhanced Random Forest Model - Jiao Tan; Jianli Ding; Zeyuan Wang; Lijing Han; Xiao Wang; Yongkang Li; Zhe Zhang; Shanshan Meng; Weijian Cai; Yanhong Hong (Computers and Electronics in Agriculture, 2024)

Antibiotic resistome in landfill leachate and impact on groundwater - Wei-Li Jia; Min Zhang; Fang-Zhou Gao; Hong Bai; Lu-Xi He; Liang-Ying He; Ting Liu; Yu Han; Guang-Guo Ying (Science of The Total Environment, 2024)

A new multi-template molecularly imprinted polymer for separation and purification of dioscin, protodioscin, and diosgenin from purple yam - Yu-Jiao Hou; Yan-Qiong Luo; Qian Li; Han Zhang; Mosesmanaanye Njolibimi; Wen-jing Li; Bo Hong; Chun-jie Zhao (Food Chemistry, 2024)

Condition assessment of stay cables using normalized sequence of vehicle-induced cable force peaks of stay cables on same side - Jin-Xin Li; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li; Qiang Han (Engineering Structures, 2024)

Silver nanoflake-mediated anode texture control enabling deep cycling of aqueous zinc-ion batteries - Anxin Li; Hongli Chen; Qinghua Tian; Ming Yang; Hong Ma; Minfeng Chen; Xiang Han; Jizhang Chen; Dingtao Ma; Peixin Zhang (Chemical Engineering Journal, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Consistent efficacy outcomes between phase 2 and phase 3 trials in Crohn’s disease or ulcerative colitis in adults: a meta-analysis - Ziqi Wan; Qingwei Jiang; Runing Zhou; Xiang Li; Wei Han; Bing Xu; Mingyue Guo; Gechong Ruan; Xiaoyin Bai; Guanqiao Li; Hong Yang (Inflammation Research, 2024)

The effects and mechanisms of deep straw incorporation and denitrifying bacterial agents on mitigating nitrate leaching and N2O emissions in four soil types in the North China Plain - Ya-Bo Zhang; Si-Yi Liu; Jun-Tao Wang; Hong J. Di; Li-Li Han; Pei-Pei Li; Ju-Pei Shen; Bing Han; Li-Mei Zhang (Agriculture, Ecosystems & Environment, 2024)

Responses of spring wheat yield and growth period to different future climate change models in the yellow river irrigation area based on CMIP6 and WOFOST models - Xinlong Li; Junli Tan; Xina Wang; Gengzhe Han; Zhijin Qian; Hong Li; Lili Wang; Guoli Niu (Agricultural and Forest Meteorology, 2024)

Identification of lignans as ATP citrate lyase (ACLY) inhibitors from the roots of Pouzolzia zeylanica - Jin-Long Li; Jia-Yi Jiang; Shan-Shan Gu; Lei Zhang; Yan Sun; Xue-Han Wang; Dan-Yu Li; Zhe-Yu Chen; Sheng-Shi Jiang; Wei-Zhong Zhu; Hao-Wen Jiang; Hong-Jie Zhang (Natural Product Research, 2024)

Morphological characteristics, genetic diversity, and ethnobotanical uses of Citrus hongheensis (Rutaceae), an endangered species - Feng-Juan Mou; Jian-Qin Li; Yu-Hong Gao; Yue-Yan Li; Ting-Yao Meng; Shun-Long Han (Plant Biosystems, 2024)

Arsenic-enhanced plant growth in As-hyperaccumulator Pteris vittata: Metabolomic investigations and molecular mechanisms - Yong-He Han; Yi-Xi Li; Xian Chen; Hong Zhang; Yong Zhang; Wei Li; Chen-Jing Liu; Yanshan Chen; Lena Q. Ma (Science of The Total Environment, 2024)

“A new underwater acoustic signal denoising method based on modified uniform phase empirical mode decomposition, hierarchical amplitude-aware permutation entropy, and optimized improved wavelet threshold denoising” [Ocean Eng. 293 (2024) 116629] - Guohui Li; Yaoyu Han; Hong Yang (Ocean Engineering, 2024)

Solution-processed nanoporous and faceted CuO electrocatalyst for enhanced solar-to-hydrogen and nitrate-to-ammonia production - Runfa Tan; Min Je Kang; Li Qu; Sung Won Hwang; Seo Yeong Hong; Yoo Jae Jeong; Hyun Soo Han; Dong Hoe Kim; Sangwook Lee; In Sun Cho (Journal of Water Process Engineering, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

Resistance of Alicyclobacillus acidoterrestris spores to atmospheric cold plasma: Insights from sporulation temperature and mechanism analysis - Lang-Hong Wang; Bing Yan; Gui-Feng Wei; Jian Li; Zhong Han; Junhu Cheng; Xin-An Zeng (Innovative Food Science & Emerging Technologies, 2024)

Condition monitoring for bridge cables using time-history area of cable forces under stochastic traffic flow - De-Long Li; Dong-Hui Yang; Ting-Hua Yi; Song-Han Zhang; Hong-Nan Li (Engineering Structures, 2024)

An electro-ferroptotic nanoammunition enables image-guided, spatiotemporally controlled cancer ferroptosis induction via irreversible electroporation - Jun-Hyeok Han; Hee Seung Seo; Jiyoung Lee; Zheng Chen; Qiyue Wang; Yun Young Lee; Na Kyeong Lee; Jeon Min Kang; Song Hee Kim; Hwichan Hong; Jung-Hoon Park; Yuanzhe Piao; et al. (Chemical Engineering Journal, 2024)

Efficient EVs separation and detection by an alumina-nanochannel-array-membrane integrated microfluidic chip and an antibody barcode biochip - Jiaoyan Qiu; Qindong Guo; Yujin Chu; Chunhua Wang; Hao Xue; Yu Zhang; Hong Liu; Gang Li; Lin Han (Analytica Chimica Acta, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

Flavonoids in vegetables: improvement of dietary flavonoids by metabolic engineering to promote health - Han Tao; Linying Li; Yuqing He; Xueying Zhang; Yao Zhao; Qiaomei Wang; Gaojie Hong (Critical Reviews in Food Science and Nutrition, 2024)

Tunable vortex bound states in multiband CsV3Sb5-derived kagome superconductors - Zihao Huang; Xianghe Han; Zhen Zhao; Jinjin Liu; Pengfei Li; Hengxin Tan; Zhiwei Wang; Yugui Yao; Haitao Yang; Binghai Yan; Kun Jiang; Jiangping Hu; et al. (Science Bulletin, 2024)

Resources recovery from coal gasification residue by combined hydrocyclone and vibrating screen and characterization of separated products - Ningning Zhang; Fuqiang Zhao; Rui Han; Zhen Li; Zhanglei Zhu; Jinzhou Qu; Hong Wang; Anning Zhou (Process Safety and Environmental Protection, 2024)

Detection of adulteration of cumin powder by front-face synchronous fluorescence spectroscopy: The influence of the natural variation of adulterants - Jin Tan; Jia-Yuan Liu; Hong Su; Xiao-Han Yang; Hui-Fen Li (Food Control, 2024)

Demethoxylation of curcumin enhances its inhibition on human and rat 17β-hydroxysteroid dehydrogenase 3: QSAR structure-activity relationship and in silico docking analysis - Zhongyao Ji; Jianmin Sang; Hong Wang; Miaomiao Xia; Ting Hao; Liping Chen; Han Lu; Shaowei Wang; Ming Yao; Linxi Li; Ren-shan Ge (Food and Chemical Toxicology, 2024)

Incorporating etched ZnO nanoparticles to fabricate positively charged composite membrane for heavy metal removal - Hong-Fei Yan; Li-Han Luo; Zhen-Liang Xu; Yin-Xin Fang; Dibakar Pandaya; Jia-Yue Dai; Jing Liang; Sun-Jie Xu (Desalination, 2024)

WOX2 functions redundantly with WOX1 and WOX4 to positively regulate seed germination in Arabidopsis - Yue Yang; Ziyun Ren; Lei Li; Yu Li; Yi Han; Yongxiu Liu; Hong Cao (Planta, 2024)

Hsa-miR-877-5p Expression in Acute Ischemic Stroke Based on Bioinformatics Analysis and Clinical Validation - Si-Shuo Zhang; Ji-Wei Zhang; Kai-Xin Zhang; Wen-Qiang Cui; Hong-Wei Zhi; Hai-Tao Li; Hong-Yun Wu; Ya-Han Wang (Molecular Neurobiology, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Spatial and widely targeted metabolomics and anatomical analysis reveal the mechanisms associated with petal bicolor patterning of two Dendrobium species - Mei-Jing Ou; Hong-Yan Li; Han Liang; Zhen-Hai Deng; Zi-Bin Zhang; Jia-Wei Li (Brazilian Journal of Botany, 2024)

Chemical constituents from the aerial parts of Rubia cordifolia L. with their NO inhibitory activity - Hong Zhang; Wen-Tao Fang; Yan Li; Qing-Hua Kong; Cheng-Wu Fang; Han Luo; Shou-Jin Liu (Natural Product Research, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

Assessing the impact of pine wilt disease on aboveground carbon storage in planted Pinus massoniana Lamb. forests via remote sensing - Xuanye Wen; Yu Hong; Jinghui Zhong; Limei Li; Qiyue Ma; Xia Hu; Xiaohong Han; Wenhui Guo; Yunpeng Huang; Feiping Zhang (Science of The Total Environment, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Halogenated aliphatic and phenolic disinfection byproducts in chlorinated and chloraminated dairy wastewater: Occurrence and ecological risk evaluation - You-Wei Jiang; Gui-Jing Wang; Shuang Zang; Yue Qiao; Hong-Fei Tao; Qiao Li; Han Zhang; Xian-Shi Wang; Jun Ma (Journal of Hazardous Materials, 2024)

AOB Nitrosospira cluster 3a.2 (D11) dominates N2O emissions in fertilised agricultural soils - Na Deng; Cecile Gubry-Rangin; Xiao-Tong Song; Xiao-Tang Ju; Si-Yi Liu; Ju-Pei Shen; Hong-jie Di; Li-Li Han; Li-Mei Zhang (Journal of Environmental Management, 2024)

Prenatal exposure to poly- and perfluoroalkyl substances and postpartum depression in women with twin pregnancies - Liqin Hu; Hong Mei; Xiaonan Cai; Lulu Song; Qiao Xu; Wenqi Gao; Dan Zhang; Jieqiong Zhou; Chen Sun; Yi Li; Feiyan Xiang; Youjie Wang; et al. (International Journal of Hygiene and Environmental Health, 2024)

Advances in the study of protein folding and endoplasmic reticulum-associated degradation in mammal cells - Hong Cao; Xuchang Zhou; Bowen Xu; Han Hu; Jianming Guo; Yuwei Ma; Miao Wang; Nan Li; Jun Zou (Journal of Zhejiang University-SCIENCE B, 2024)

Advances in the study of mitophagy in osteoarthritis - Hong Cao; Xuchang Zhou; Bowen Xu; Han Hu; Jianming Guo; Miao Wang; Nan Li; Jun Zou (Journal of Zhejiang University-SCIENCE B, 2024)

Unraveling the threat: Microplastics and nano-plastics' impact on reproductive viability across ecosystems - Ji Liang; Feng Ji; Hong Wang; Tian Zhu; James Rubinstein; Richard Worthington; Anisah Lee Binti Abdullah; Yi Juin Tay; Chenxin Zhu; Andrew George; Yiming Li; Mingming Han (Science of The Total Environment, 2024)

A new underwater acoustic signal denoising method based on modified uniform phase empirical mode decomposition, hierarchical amplitude-aware permutation entropy, and optimized improved wavelet threshold denoising - Guohui Li; Yaoyu Han; Hong Yang (Ocean Engineering, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

Methylmercury-sensitized “turn on” SERS-active peroxidase-like activity of carbon dots/Au NPs nanozyme for selective detection of ochratoxin A in coffee - Qiulan Li; Qinqin Han; Dezhi Yang; Kexiang Li; Yijie Wang; Dan Chen; Yaling Yang; Hong Li (Food Chemistry, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

Partitioning eddy covariance CO2 fluxes into ecosystem respiration and gross primary productivity through a new hybrid four sub-deep neural network - Han Chen; Han Li; Yizhao Wei; Edward McBean; Hong Liang; Weimin Wang; Jinhui Jeanne Huang (Agriculture, Ecosystems & Environment, 2024)

Laccase-evoked removal of antibiotics: Reaction kinetics, conversion mechanisms, and ecotoxicity assessment - Kai Sun; Mei-Hua Chen; Xue-Min Qi; Dan Hong; Ling-Zhi Dai; Shun-Yao Li; Yi-Chen Lu; Han-Qing Yu (Critical Reviews in Environmental Science and Technology, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Study on the suppression characteristics and mechanism of ABC powder on pulverized coal explosion based on the analysis of thermal decomposition characteristics and reaction kinetics - Bingyou Jiang; Qi Yao; Mingqing Su; Jingjing Li; Kunlun Lu; Dawei Ding; Han Hong (Process Safety and Environmental Protection, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Speciation, distribution and relationship of zinc and cadmium in summer coastal seawater of northern China - Yan Liang; Dawei Pan; Hong Wei; Haitao Han; Ying Li; Tianzhuo Liu (Marine Chemistry, 2024)

Unveiling the metal mutation nexus: Exploring the genomic impacts of heavy metal exposure in lung adenocarcinoma and colorectal cancer - Mengyuan Liu; Yuting Hong; Xiaohong Duan; Qiming Zhou; Jing Chen; Siyao Liu; Junyan Su; Li Han; Jiali Zhang; Beifang Niu (Journal of Hazardous Materials, 2024)

Pseudorange characteristics of soil-transmitted GNSS signals and their application in soil moisture content retrieval - Jie Li; Dongkai Yang; Feng Wang; Xuebao Hong; Mutian Han (GPS Solutions, 2024)

Estrogen inhibits the differentiation of fibroblasts induced by high stiffness matrix by enhancing DNMT1 expression - Zhihan Zhao; Guotao Huang; Yong He; Xiaohu Zuo; Wuyue Han; Hong Li (Tissue and Cell, 2023)

Cephalopod-inspired polymer composites with mechanically tunable infrared properties - Bin Yao; Xinwei Xu; Zhubing Han; Wenhan Xu; Guang Yang; Jing Guo; Guixin Li; Qing Wang; Hong Wang (Science Bulletin, 2023)

Examining public attitudes and perceptions of waste sorting in China through an urban heterogeneity lens: A social media analysis - Han Huang; Ruyin Long; Hong Chen; Kun Sun; Qingqing Sun; Qianwen Li (Resources, Conservation and Recycling, 2023)

Distribution characteristics and ecological risk assessment of butyltins in sediments at typical dumping sites in China - Lingna Kong; Xiaomeng Wang; Qingxin Xiang; Yuxia Li; Jiayi Cheng; Hong Chen; Yan Liu; Jianbo Han; Naidong Zhang (Regional Studies in Marine Science, 2023)

Unveiling targeted spatial metabolome of rice seed at the dough stage using Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry imaging - Yao Zhao; Jitao Hu; Yilin Zhang; Han Tao; Linying Li; Yuqing He; Xueying Zhang; Chi Zhang; Gaojie Hong (Food Research International, 2023)

A comparison of milk fat globule membranes and whey proteomes: New insight into variation nutrient differences between Buffalo, Cow, Goat, and Yak - Lu Chen; Tiannuo Hong; Ziqi Li; Guohui Shen; Yanting Gu; Juan Han (Food Chemistry, 2023)

A co-twin control study of in utero exposure to poly- and perfluoroalkyl substances and associations with neonatal thyroid-stimulating hormone - Liqin Hu; Hong Mei; Xiaonan Cai; Feiyan Xiang; Na Li; Zhen Huang; Zhengrong Duan; Pan Yang; Han Xiao (Environmental Research, 2023)

Ecological restoration evaluation of afforestation in Gudao Oilfield based on multi-source remote sensing data - Xiuneng Li; Yongtao Li; Hong Wang; Shuhong Qin; Xin Wang; Han Yang; Wim Cornelis (Ecological Engineering, 2023)

Suppress moisture sensitivity of Ni-rich cathode materials by bioinspired self-assembly hydrophobic layer - Yingde Huang; Pei-Yao Li; Han-Xin Wei; Yu-Hong Luo; Lin-Bo Tang; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Understanding ecological civilization in China: From political context to science - Bing Xue; Bin Han; Hongqing Li; Xiaohua Gou; Hong Yang; Heiko Thomas; Stefan Stückrad (Ambio, 2023)

Projecting spatiotemporal dynamics of severe fever with thrombocytopenia syndrome in the mainland of China - Fang‐Yu Ding; Hong‐Han Ge; Tian Ma; Qian Wang; Meng‐Meng Hao; Hao Li; Xiao‐Ai Zhang; Richard James Maude; Li‐Ping Wang; Dong Jiang; Li‐Qun Fang; Wei Liu (Global Change Biology, 2023)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with increasing incidence and geographic extent. The extent to which global climate change affects the incidence of SFTS disease remains obscure. We use an integrated multi‐model, multi‐scenario framework to assess the impact of global climate change on SFTS disease in China. The spatial distribution of habitat suitability for the tick Haemaphysalis longicornis was predicted by applying a boosted regression tree model under four alternative climate change scenarios (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) for the periods 2030–2039, 2050–2059, and 2080–2089. We incorporate the SFTS cases in the mainland of China from 2010 to 2019 with environmental variables and the projected distribution of H. longicornis into a generalized additive model to explore the current and future spatiotemporal dynamics of SFTS. Our results demonstrate an expanded geographic distribution of H. longicornis toward Northern and Northwestern China, showing a more pronounced change under the RCP8.5 scenario. In contrast, the environmental suitability of H. longicornis is predicted to be reduced in Central and Eastern China. The SFTS incidence in three time periods (2030–2039, 2050–2059, and 2080–2089) is predicted to be increased as compared to the 2010s in the context of various RCPs. A heterogeneous trend across provinces, however, was observed, when an increased incidence in Liaoning and Shandong provinces, while decreased incidence in Henan province is predicted. Notably, we predict possible outbreaks in Xinjiang and Yunnan in the future, where only sporadic cases have been reported previously. These findings highlight the need for tick control and population awareness of SFTS in endemic regions, and enhanced monitoring in potential risk areas.

Enforcing energy consumption promotes microbial extracellular respiration for xenobiotic bioconversion - Zi‐Han Liang; Hong Sun; Yang Li; Anyi Hu; Qiang Tang; Han‐Qing Yu (Environmental Microbiology, 2023)
Extracellular electron transfer (EET) empowers electrogens to catalyse the bioconversion of a wide range of xenobiotics in the environment. Synthetic bioengineering has proven effective in promoting EET output. However, conventional strategies mainly focus on modifications of EET‐related genes or pathways, which leads to a bottleneck due to the intricate nature of electrogenic metabolic properties and intricate pathway regulation that remain unelucidated. Herein, we propose a novel EET pathway‐independent approach, from an energy manipulation perspective, to enhance microbial EET output. The Controlled Hydrolyzation of ATP to Enhance Extracellular Respiration (CHEER) strategy promotes energy utilization and persistently reduces the intracellular ATP level in Shewanella oneidensis , a representative electrogenic microbe. This approach leads to the accelerated consumption of carbon substrate, increased biomass accumulation and an expanded intracellular NADH pool. Both microbial electrolysis cell and microbial fuel cell tests exhibit that the CHEER strain substantially enhances EET capability. Analysis of transcriptome profiles reveals that the CHEER strain considerably bolsters biomass synthesis and metabolic activity. When applied to the bioconversion of model xenobiotics including methyl orange, Cr(VI) and U(VI), the CHEER strain consistently exhibits enhanced removal efficiencies. This work provides a new perspective and a feasible strategy to enhance microbial EET for efficient xenobiotic conversion.

Effect of soil spatial variability on characteristics of depth-varying multi-support seismic motions at offshore sites - Chao Li; Yu-Cheng Diao; Rou-Han Li; Hai-Yang Pan; Qiang Han; Hong-Nan Li (Soil Dynamics and Earthquake Engineering, 2023)

Effect of ocean warming on pigment and photosynthetic carbon fixation of plankton assemblage in Pingtan Island of Southeast China - Yong Zhang; Shuai Ma; Xiang Yang; Yingrui Wang; Yubin Hu; Rongrong Xie; Jiabing Li; Yonghe Han; Hong Zhang; Yong Zhang (Marine Environmental Research, 2023)

Synergistic transfer of active hydrogen in the catalytic hydroconversion of lignite-derived aryl ethers to cyclanes: A combined experimental and DFT study - Guang-Hui Liu; Yong-Chao Qi; Han Wang; Ai-Min Wang; Yu-Hong Kang; Yong Gao; Ni Bai; Zhan-Ku Li; Xian-Yong Wei (Fuel, 2023)

Corrigendum to “Comparative metabolomics of flavonoids in twenty vegetables reveal their nutritional diversity and potential health benefits” [Food Res. Int. 164 (2023) 112384] - Han Tao; Yao Zhao; Linying Li; Yuqing He; Xueying Zhang; Ying Zhu; Gaojie Hong (Food Research International, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

Perturbation indicator for Hall effect thruster operating state based on statistical characteristics of breathing oscillation time scale signals - Jingjing Li; Liqiu Wei; Yanlin Hu; Huibin Lian; Liwei Zhou; Xingyu Liu; Tianyuan Ji; Liang Han; Yongfeng He; Hong Li; Yongjie Ding (Advances in Space Research, 2023)

Inactivation of chlorine-resistant bacteria (CRB) via various disinfection methods: Resistance mechanism and relation with carbon source metabolism - Yu-Qing Xu; Yin-Hu Wu; Li-Wei Luo; Bang-Hao Huang; Zhuo Chen; Hao-Bin Wang; Han Liu; Nozomu Ikuno; Nakata Koji; Hong-Ying Hu (Water Research, 2023)

Towards effective recovery of humate as green fertilizer from landfill leachate concentrate by electro-neutral nanofiltration membrane - Wenyuan Ye; Mingqiu Hong; Xuan Huang; Tianci Chen; Ailiang Gu; Xiaocheng Lin; Xuewei Li; Xiangrong Chen; Dong Han Seo; Shuaifei Zhao; Xueming Chen; Bart Van der Bruggen; et al. (Science of The Total Environment, 2023)

Roles of high/low nucleic acid bacteria in flocs and probing their dynamic migrations with respirogram - Zheng-Hong Wen; Shuang-Shuang Zhang; Pian Zhao; Zhen-Yu Hang; Zhang-Wei He; Han-Qing Yu; Zhi-Hua Li (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Ent-eudesmane sesquiterpenoids from the Chinese liverwort Chiloscyphus polyanthus - Ming-Zhu Zhu; Yi Li; Jin-Chuan Zhou; Dong-Xue Lv; Xiao-Jie Fu; Zhen Liang; Shuang-Zhi Yuan; Jing-Jing Han; Jiao-Zhen Zhang; Ze-Jun Xu; Wen-Qiang Chang; Hong-Xiang Lou (Phytochemistry, 2023)

Exposure to per- and polyfluoroalkyl substances in women with twin pregnancies: Patterns and variability, transplacental transfer, and predictors - Songyi Huang; Xiaojie Li; Langjing Deng; Jinying Xie; Guangtong Huang; Chenyan Zeng; Nanxin Wu; Sui Zhu; Chaoqun Liu; Hong Mei; Han Xiao; Da Chen; et al. (Journal of Hazardous Materials, 2023)

Use of a compound modifier to retard the quality deterioration of frozen dough and its steamed bread - Jin-Ming Tan; Bing Li; Shuang-Yan Han; Hong Wu (Food Research International, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

On data-driven energy flexibility quantification: A framework and case study - Han Li; Tianzhen Hong (Energy and Buildings, 2023)

Chemical constituents from the leaves of Callicarpa arborea Roxb. and their chemotaxonomic significance - Tao-Li Zhang; Qiao-Qi Yi; Yu-Xiao Han; Lu Zhao; Shu-Qing Gui; Wen-Xia Liu; Hong-Gang Wang (Biochemical Systematics and Ecology, 2023)

Reduction potential of vehicular emission in Chengdu, China: A case study of COVID-19 - Xinping Yang; Hefeng Zhang; Wei Li; Hong Tian; Yongdong Wang; Jing Zhou; Ze Bao; Xiaorui Chen; Teng Xiao; Yunjing Wang; Mingliang Fu; Xian Wu; et al. (Urban Climate, 2023)

Corrigendum to “Maternal linuron exposure alters testicular development in male offspring rats at the whole genome level” [Toxicology 389 (2017) 13–20] - Jianwei Bai; Hua Han; Feng Wang; Liyu Su; Hongwei Ding; Xiyin Hu; Binli Hu; Hong Li; Wei Zheng; Yan Li (Toxicology, 2023)

C21 steroids from the roots of Marsdenia tenacissima - Jin-Ling Liu; Hong-Tao Xu; Dan-Dan Mu; Xiao Han; Ting-Ting Du; Yong-li Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

PxRdl2 dsRNA increased the insecticidal activities of GABAR-targeting compounds against Plutella xylostella - Ben-Jie Li; Kun-Kun Wang; Ye Yu; Jia-Qi Wei; Jian Zhu; Jia-Li Wang; Fei Lin; Han-Hong Xu (Pesticide Biochemistry and Physiology, 2023)

Self-purification of actual wastewater via microbial-synergy driving of catalyst-surface microelectronic field: A pilot-scale study - Xueci Xing; Lai Lyu; Zhen Yan; Han Zhang; Tong Li; Muen Han; Zesong Li; Fagen Zhang; Zhu Wang; Shuguang Wang; Yiguo Hong; Chun Hu (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Automatic registration framework for multi-platform point cloud data in natural forests - Xin Wang; Qiuji Chen; Hong Wang; Xiuneng Li; Han Yang (International Journal of Remote Sensing, 2023)

Distribution and characteristics of microplastics in sediment at representative dredged material ocean dumping sites, China - Yuying Yi; Lingna Kong; Xiaomeng Wang; Yuxia Li; Jiayi Cheng; Jianbo Han; Hong Chen; Naidong Zhang (Marine Pollution Bulletin, 2023)

Pallamins A–C, ent-labdane and pallavicinin based dimers from the Chinese liverwort Pallavicinia ambigua (mitt.) stephani - Yi Li; Xiao-Bin Li; Jin-Chuan Zhou; Ze-Jun Xu; Ming-Zhu Zhu; Yan Zong; Jiao-Zhen Zhang; Jing-Jing Han; Ya-Jie Tang; Hong-Xiang Lou (Phytochemistry, 2023)

Biodegradation of p-hydroxybenzoic acid in Herbaspirillum aquaticum KLS-1 isolated from tailing soil: Characterization and molecular mechanism - Yi-Xi Li; Wei Lin; Yong-He Han; Yao-Qiang Wang; Tao Wang; Hong Zhang; Yong Zhang; Shan-Shan Wang (Journal of Hazardous Materials, 2023)

Changes in physicochemical characteristics and metabolites in the fermentation of goji juice by Lactiplantibacillus plantarum - Han Xie; Pengyan Gao; Zhen-Ming Lu; Fang-Zhou Wang; Li-Juan Chai; Jin-Song Shi; Hui-Ling Zhang; Yan Geng; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2023)

The association between chemical constituents of ambient fine particulate matter and obesity in adults: A large population-based cohort study - Shaokun Yang; Feng Hong; Sicheng Li; Xinyu Han; Jiawei Li; Xing Wang; Lin Chen; Xuehui Zhang; Xi Tan; Jingru Xu; Zhuoma Duoji; Zhuoga Ciren; et al. (Environmental Research, 2023)

Measuring the route topography impact on real driving emissions based on neural network models - Hualong Xu; Li Zhang; Hong Chang; Jinlin Han; Dongmei Wu; Xiangkun Gong; Mingming Fu (Environmental Research, 2023)

Cation engineering in low-dimensional organic-inorganic copper halides for high color rendering index WLEDs - Hong Yin; Wenzhi Li; Zhongyi Wang; Pengyuan Wang; Xin Xu; Peigeng Han; Xin Mao; Feng Liu; Keli Han; Junsheng Chen; Ruiling Zhang (Chemical Engineering Journal, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Ten questions concerning reinforcement learning for building energy management - Zoltan Nagy; Gregor Henze; Sourav Dey; Javier Arroyo; Lieve Helsen; Xiangyu Zhang; Bingqing Chen; Kadir Amasyali; Kuldeep Kurte; Ahmed Zamzam; Helia Zandi; Ján Drgoňa; et al. (Building and Environment, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

A comprehensive performance evaluation methodology for sea-crossing cable-stayed bridges under wind and wave loads - Chao Li; Guo-Yi Wu; Lu-Xi Li; Chun-Guang Liu; Hong-Nan Li; Qiang Han (Ocean Engineering, 2023)

The domestication-associated L1 gene encodes a eucomic acid synthase pleiotropically modulating pod pigmentation and shattering in soybean - Xiangguang Lyu; Ying-hui Li; Yanfei Li; Delin Li; Chao Han; Huilong Hong; Yu Tian; Lida Han; Bin Liu; Li-juan Qiu (Molecular Plant, 2023)

Why don't more people engage in green practices in China? A policy-oriented approach to promoting green transformation in five consumption areas - Han Huang; Ruyin Long; Hong Chen; Kun Sun; Qingqing Sun; Qianwen Li (Environmental Impact Assessment Review, 2023)

In-doping induced resonant level and thermoelectric performance enhancement in n-type GeBi2Te4 single crystals with intrinsically low lattice thermal conductivity - Peng Chen; Bin Zhang; Hanjun Zou; Xiangnan Gong; Yanci Yan; Jingwei Li; Daliang Zhang; Guang Han; Xu Lu; Hong Wu; Yun Zhou; Xiaoyuan Zhou; et al. (Chemical Engineering Journal, 2023)

Network prediction of surgical complication clusters: a prospective multicenter cohort study - Xiaochu Yu; Peng Wu; Zixing Wang; Wei Han; Yuguang Huang; Shijie Xin; Qiang Zhang; Shengxiu Zhao; Hong Sun; Guanghua Lei; Taiping Zhang; Luwen Zhang; et al. (Science China Life Sciences, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

The driving force of biomass value-addition: Selective catalytic depolymerization of lignin to high-value chemicals - Quyang Tian; Piao Xu; Danlian Huang; Han Wang; Ziwei Wang; Hong Qin; Yangzhuo He; Ruijin Li; Lingshi Yin; Sha Chen; Yin Zhao (Journal of Environmental Chemical Engineering, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Effects of sericin on oxidative stress and PI3K/AKT/mTOR signal pathway in cryopreserved mice ovarian tissue - Wei Han Shu; Song He Yang; Meng Wei; Xiao Chao Liu; Zi Xuan Chen; Chen Yang Wei; Xin Zhang; Li Na Si; Zhi Hong Chen; Yue Bing Qiao; Dong Mei Li; Tie Cheng Sun; et al. (Cryobiology, 2023)

Electroconductive and mechano-competent PUCL@CNT nanohybrid scaffolds guiding neuronal specification of neural stem/progenitor cells - Yu-Meng Li; Kapil D. Patel; Yoon-Koo Han; Suk-Min Hong; Yu-Xuan Meng; Hae-Hyoung Lee; Jeong Hui Park; Jonathan C. Knowles; Jung Keun Hyun; Jung-Hwan Lee; Hae-Won Kim (Chemical Engineering Journal, 2023)

Engineered Bacillus subtilis alleviates intestinal oxidative injury through Nrf2-Keap1 pathway in enterotoxigenic Escherichia coli (ETEC) K88-infected piglet - Chaoyue Wen; Hong Zhang; Qiuping Guo; Yehui Duan; Sisi Chen; Mengmeng Han; Fengna Li; Mingliang Jin; Yizhen Wang (Journal of Zhejiang University-SCIENCE B, 2023)

NLRP7 participates in the human subcortical maternal complex and its variants cause female infertility characterized by early embryo arrest - Jian Han; Nana Zhang; Qiqi Cao; Xiaodan Shi; Congjing Wang; Ximan Rui; Jie Ding; Chun Zhao; Junqiang Zhang; Xiufeng Ling; Hong Li; Yichun Guan; et al. (Journal of Molecular Medicine, 2023)

Mechanisms controlling the transport and evaporation of human exhaled respiratory droplets containing the severe acute respiratory syndrome coronavirus: a review - Leslie Kojo Norvihoho; Jing Yin; Zhi-Fu Zhou; Jie Han; Bin Chen; Li-Hong Fan; Eric Lichtfouse (Environmental Chemistry Letters, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

A novel reduced graphene oxide/polypyrrole conductive ceramic membrane enhanced electric field membrane bioreactor: Mariculture wastewater treatment performance and membrane fouling mitigation - Rui Wang; Hong You; Zhipeng Li; Binghan Xie; Shaojie Qi; Jing Zhu; Qiqing Qin; Han Wang; Jinxu Sun; Yi Ding; Yuhong Jia; Feng Liu (Bioresource Technology, 2023)

The status of the global food waste mitigation policies: experience and inspiration for China - Guohui Shen; Ziqi Li; Tiannuo Hong; Xin Ru; Kunzhen Wang; Yanting Gu; Juan Han; Yanzhi Guo (Environment, Development and Sustainability, 2023)
Food waste has become a significant challenge faced by the community with a shared future for mankind, and it has also caused a considerable impact on China's food security. Scholars across disciplines, international organizations, and especially policymakers are increasingly interested in food waste. Policies are seen as a powerful factor in reducing food waste, but current research on related policies is more scattered. This paper summarizes and analyzes the experiences of food waste policy development and implementation by systematically reviewing the studies on food waste reduction policies. The results of this paper's analysis show that current global food waste policies are focused at the national strategic level, with approaches such as legislation, food donation, waste recycling, awareness and education, and data collection. At the same time, we find that the current experience of developed countries in policy formulation and implementation is beneficial for policy formulation in developing countries. And taking China as an example, we believe that developing countries can improve food waste policies in the future by improving legislation, guiding the development of food banks, promoting social governance, and strengthening scientific research projects. These policies will all contribute strongly to global environmental friendliness. In addition, we discuss some of the factors that influence the development of food waste policies and argue that in the future, more consideration needs to be given to the effects of policy implementation and that case studies should focus more on developing countries. This will contribute to the global sustainable development process.

Exposure to phthalate increases the risk of eczema in children: Findings from a systematic review and meta-analysis - Hong Zhang; Siyu Chen; Xinwang Chen; Yong Zhang; Yonghe Han; Jiabing Li; Xiangqi Chen (Chemosphere, 2023)

Genomic insights into the genetic basis of cotton breeding in China - Yiqian Li; Zhanfeng Si; Guoping Wang; Zhuolin Shi; Jinwen Chen; Guoan Qi; Shangkun Jin; Zegang Han; Wenhao Gao; Yue Tian; Yun Mao; Lei Fang; et al. (Molecular Plant, 2023)

On the extinction depth of freezing-induced groundwater migration - Xiao-Wei Jiang; Hong-Yu Xie; Shemin Ge; Han Tang; Shu-Cong Tan; Xu-Sheng Wang; Li Wan; Yijian Zeng (Journal of Hydrology, 2023)

Integration of flux footprint and physical mechanism into convolutional neural network model for enhanced simulation of urban evapotranspiration - Han Chen; Jinhui Jeanne Huang; Hong Liang; Weimin Wang; Han Li; Yizhao Wei; Albert Z. Jiang; Pengwei Zhang (Journal of Hydrology, 2023)

A general way to manipulate electrical conductivity of graphene - Liqing Chen; Nian Li; Xinling Yu; Shudong Zhang; Cui Liu; Yanping Song; Zhao Li; Shuai Han; Wenbo Wang; Pengzhan Yang; Na Hong; Sarmad Ali; et al. (Chemical Engineering Journal, 2023)

High-titer production of myo-inositol by a co-immobilized four-enzyme cocktail in biomimetic mineralized microcapsules - Pingping Han; Chun You; Yunjie Li; Ting Shi; Hong Wu; Yi-Heng P. Job Zhang (Chemical Engineering Journal, 2023)

Design, synthesis and fungicidal evaluation of novel psoralen derivatives containing sulfonohydrazide or acylthiourea moiety - Jingyue Dong; Kun Li; Zeyu Hong; Lei Chen; Liangfu Tang; Lijun Han; Lai Chen; Zhijin Fan (Molecular Diversity, 2023)

Large-scale mapping of new mixed rice cropping patterns in southern China with phenology-based algorithm and MODIS dataset - Qihui Shao; Rendong Li; Juan Qiu; Yifei Han; Dongfeng Han; MiaoMiao Chen; Hong Chi (Paddy and Water Environment, 2023)

Invasive weed optimization for multi-AGVs dispatching problem in a matrix manufacturing workshop - Zhong-Kai Li; Hong-Yan Sang; Jun-Qing Li; Yu-Yan Han; Kai-Zhou Gao; Zhi-Xin Zheng; Li-li Liu (Swarm and Evolutionary Computation, 2023)

Concomitant oxidation of fatty acids other than DHA and EPA plays a role in the characteristic off-odor of fish oil - Yun-Qi Wen; Chang-Hu Xue; Hong-Wei Zhang; Li-Li Xu; Xiao-Han Wang; Shi-Jie Bi; Qian-Qian Xue; Yong Xue; Zhao-Jie Li; Joaquín Velasco; Xiao-Ming Jiang (Food Chemistry, 2023)

Surface-modified liquid metal nanocapsules derived multiple triboelectric composites for efficient energy harvesting and wearable self-powered sensing - Zihua Li; Bingang Xu; Jing Han; Di Tan; Junxian Huang; Yuanyuan Gao; Hong Fu (Chemical Engineering Journal, 2023)

A review: structure–activity relationship between saponins and cellular immunity - Xuetao Cui; Xumin Ma; Chunhai Li; Hong Meng; Chunchao Han (Molecular Biology Reports, 2023)

Enhancing intercity transportation will improve the equitable distribution of high-quality health care in China - Han Zhang; Bing-Bing Zhou; Shuwen Liu; Guohua Hu; Xing Meng; Xiaojuan Liu; Hong Shi; Yukun Gao; Haiyan Hou; Xia Li (Applied Geography, 2023)

Host's P85α genotype restructures the gut microbiota and regulates fat metabolism in gibel carp - Tengba Fan; Ivan Jakovlić; Qiyong Lou; Dong Han; Wenxiang Li; Ming Li; Hong Zou; Guitang Wang; Shangong Wu (Aquaculture, 2023)

Divergent responses in the gut microbiome and liver metabolome to ammonia stress in three freshwater turtles - Qin-Yuan Meng; Dong-Mei Mo; Han Li; Wan-Ling Wang; Hong-Liang Lu (Science of The Total Environment, 2023)

Co-substrate promoting the biodegradation of refractory DOM in semi-coking wastewater: DOM evolution and microbial community - Min-Hui Cai; Ye-Chao Tian; Ai-Min Li; Yan Li; Yu-Ze Han; Jun Li; Hong-Fang Sun; Xin Wang; Qing Zhou; Wen-Tao Li (Journal of Environmental Chemical Engineering, 2023)

Comparative metabolomics of flavonoids in twenty vegetables reveal their nutritional diversity and potential health benefits - Han Tao; Yao Zhao; Linying Li; Yuqing He; Xueying Zhang; Ying Zhu; Gaojie Hong (Food Research International, 2023)

Perspective: Blinded by the bright—afforestation is affecting widespread sampling deficiency in plant collections - Yu Zhang; Meng-Ge Duan; Pei-Han Huang; Min Li; Hong-Hu Meng; Hui-Jie Qiao; Jie Li (Forest Ecology and Management, 2023)

Predicting ozone formation in petrochemical industrialized Lanzhou city by interpretable ensemble machine learning - Li Wang; Yuan Zhao; Jinsen Shi; Jianmin Ma; Xiaoyue Liu; Dongliang Han; Hong Gao; Tao Huang (Environmental Pollution, 2023)

Integrated adsorption and photodegradation of tetracycline by bismuth oxycarbonate/biochar nanocomposites - Yidan Luo; Aofeng Zheng; Junda Li; Yu Han; Mingshan Xue; Longshuai Zhang; Zuozhu Yin; Chan Xie; Zhi Chen; Li Ji; Zhen Hong; Xianchuan Xie (Chemical Engineering Journal, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

Perceptions of Oncology Nurses Regarding Fertility Preservation and Providing Oncofertility Services for Men of Childbearing Age with Cancer - Han-Feng Zhang; Qing-Hua Jiang; Ying-Hong Fang; Li Jin; Gui-Yu Huang; Jing Wang; Hong-Fang Bai; Mika Miyashita (Journal of Cancer Education, 2023)

Variation of lead bioaccessibility in soil reference materials: Intra- and inter-laboratory assessments - Xiaoyue Huang; Minghui Chang; Lei Han; Jie Li; Shi-Wei Li; Hong-Bo Li (Chemosphere, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Co-exposure to phenols and phthalates during pregnancy with the difference of body size in twins at one month old - Hong Mei; Langjing Deng; Jinying Xie; Xiaojie Li; Nanxin Wu; Liqin Hu; Guangtong Huang; Fanyu Mo; Da Chen; Han Xiao; Pan Yang (Chemosphere, 2023)

Multi-index assessment of heavy metal contamination in surface sediments of the Pearl River estuary intertidal zone - Rui-Ze Liang; Yang-Guang Gu; Hai-Song Li; Yan-Jie Han; Jie Niu; Hong Su; Richard W. Jordan; Xiang-Tian Man; Shi-Jun Jiang (Marine Pollution Bulletin, 2023)

E2F4 regulates cell cycle to mediate embryonic development in pigs - Wen-Jie Jiang; Ming-Hong Sun; Xiao-Han Li; Song-Hee Lee; Geun Heo; Dongjie Zhou; Xiang-Shun Cui (Theriogenology, 2023)

Landslide-impacted soils recover faster biologically than chemically or physically, though recovery also varies with forest type in subtropical China - Jian Li; Lan Xiao; Jonathan D. Bakker; Qinghu Luo; Hang Yu; Jianzhao Wu; Songyang Li; Loretta Pedersen; Can Chen; Tao Hong; Han Lin; Daojie Wang; et al. (Soil and Tillage Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

A maturation scale for molecular simulation of kerogen thermal degradation - Qiuya Han; Meijun Li; Xiaoqiang Liu; Hong Xiao; Junhao Ren; Chengbo Guo (Organic Geochemistry, 2023)

Can evaporation from urban impervious surfaces be ignored? - Han Chen; Jinhui Jeanne Huang; Hong Liang; Weimin Wang; Han Li; Yizhao Wei; Albert Z. Jiang; Pengwei Zhang (Journal of Hydrology, 2023)

Molting-related proteases in the brown planthopper, Nilaparvata lugens - Yu-Cheng Xie; Hou-Hong Zhang; Han-Jing Li; Xiao-Ya Zhang; Xu-Mei Luo; Ming-Xing Jiang; Chuan-Xi Zhang (Insect Biochemistry and Molecular Biology, 2023)

A chemometric study on the identification of 5-methylfurfural and 2-acetylfuran as particular volatile compounds of oxidized fish oil based on SHS-GC-IMS - Yun-Qi Wen; Hong-Wei Zhang; Chang-Hu Xue; Xiao-Han Wang; Shi-Jie Bi; Li-Li Xu; Qian-Qian Xue; Yong Xue; Zhao-Jie Li; Joaquín Velasco; Xiao-Ming Jiang (Food Chemistry, 2023)

Passivation of positively charged cationic defects in perovskite with nitrogen-donor crown ether enabling efficient perovskite solar cells - Yuxuan Yang; Tao Zhao; Ming-Hua Li; Xiaoxue Wu; Mingyue Han; Shih-Chi Yang; Qiaoling Xu; Lede Xian; Xiang Chi; Ning-Jiu Zhao; Hong Cui; Sihan Li; et al. (Chemical Engineering Journal, 2023)

The Nucleus Accumbens CRH–CRHR1 System Mediates Early-Life Stress-Induced Sleep Disturbance and Dendritic Atrophy in the Adult Mouse - Ting Wang; Yu-Nu Ma; Chen-Chen Zhang; Xiao Liu; Ya-Xin Sun; Hong-Li Wang; Han Wang; Yu-Heng Zhong; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2023)

Research on Maneuverability Prediction of Double Waterjet Propulsion High Speed Planing Craft - Hua-Wei Sun; Jing-Lei Yang; Bo Liu; Hong-Wei Li; Jia-Feng Xiao; Han-Bing Sun (Journal of Marine Science and Engineering, 2022)
A mathematical model for predicting the maneuvering motion of a ship is constructed, using a planing craft with dual waterjet propulsion as the object of study. This model is based on the standard approach of the MMG (Maneuvering Modeling Group) and uses the Runge–Kutta algorithm to solve the differential equations. For the simulation of the turning and Z-shape maneuvering motion, the RANS equation is first solved using the program STAR-CCM + and then the PMM motion of the hull is simulated using the overlapping grid approach to derive the hydrodynamic derivative. The established method for predicting the ship’s maneuverability is feasible, as shown by the calculated results, which agree well with those obtained using data from the sea trials. This method was used to simulate the rudder rotation and Z-shape motion of the planing craft at medium and high speeds to predict the maneuverability index.

Brevilaterin B from Brevibacillus laterosporus has selective antitumor activity and induces apoptosis in epidermal cancer - Zhou Chen; Lulu Wang; Yangliu Liu; Panpan Han; Dan Hong; Siting Li; Aijin Ma; Yingmin Jia (World Journal of Microbiology and Biotechnology, 2022)

Inhibition of cGAS in Paraventricular Nucleus Attenuates Hypertensive Heart Injury Via Regulating Microglial Autophagy - Chengzhi Han; Xinyi Qian; Xiaorong Ren; Shutian Zhang; Li Hu; Jingyao Li; Yijun Huang; Renhui Huang; Kokwin Ooi; Hong Lin; Chunmei Xia (Molecular Neurobiology, 2022)

Dongia deserti sp. nov., Isolated from the Gurbantunggut Desert Soil - Chun-Yan Lu; Lei Dong; Dong Wang; Shuai Li; Bao-Zhu Fang; Ming-Xian Han; Feng Liu; Hong-Chen Jiang; Iftikhar Ahmed; Wen-Jun Li (Current Microbiology, 2022)

Importance of surface charge of soot nanoparticles in determining inhalation toxicity in mice - Ta-Chih Hsiao; Chia-Li Han; Tzu-Ting Yang; Yueh-Lun Lee; Yu-Fang Shen; Yu-Teng Jheng; Chii-Hong Lee; Jer-Hwa Chang; Kian Fan Chung; Han-Pin Kuo; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)

The strigolactone receptor SlDWARF14 plays a role in photosynthetic pigment accumulation and photosynthesis in tomato - Zhifei Li; Ying Pi; Changsheng Zhai; Dong Xu; Wenyao Ma; Hong Chen; Yi Li; Han Wu (Plant Cell Reports, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Adaptive Formation Control of Multiple Underactuated Autonomous Underwater Vehicles - Ji-Hong Li; Hyungjoo Kang; Min-Gyu Kim; Mun-Jik Lee; Gun Rae Cho; Han-Sol Jin (Journal of Marine Science and Engineering, 2022)
In this paper, we present a 3D formation control scheme for a group of torpedo-type underactuated autonomous underwater vehicles (AUVs). These multiple AUVs combined with an unmanned surface vessel (USV) construct a sort of star-topology acoustic communication network where the USV is at the center point. Due to this kind of topological feature, this paper applies a virtual school concept. This is a geometric graph where each node is taken as a virtual leader for each specific AUV and assigned its own reference trajectory. For each individual vehicle, its formation strategy is simple: just follow the trajectory of its corresponding virtual leader so as for multiple AUVs to compose the given formation. As for the formation subject, this paper mainly focuses on the formation tracking problem rather than the formation producing. For the torpedo-type vehicle considered in this paper, there are only three control inputs (surge force, pitch, and yaw moments) available for its underwater 3D motion and therefore this is a typical underactuated system. For the following vehicle’s trajectory, a sort of potential field method is used for obstacle avoidance, and a neural network-based adaptive scheme is applied to on-line approximate the vehicle’s unknown nonlinear dynamics, and the uncertainty terms including modeling errors, measurement noises, and external disturbances are handled by the properly designed robust scheme. The proposed formation method can guarantee the uniform ultimate boundedness (UUB) of the closed-loop system. Numerical studies are also carried out to verify the effectiveness of the proposed scheme.

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Correction to: Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/ TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)

Characterization, heterologous expression and engineering of trehalase for biotechnological applications - Han Gao; Jin-Song Gong; Chang Su; Heng Li; Zheng-Hong Xu; Jin-Song Shi (Systems Microbiology and Biomanufacturing, 2022)

Ligustilide ameliorates cognitive impairment via AMPK/SIRT1 pathway in vascular dementia rat - Dong Peng; Han-Zi Qiao; Hong-Yu Tan; Yi-Xue Wang; Dan Luo; Li-Jun Qiao; Ye-Feng Cai; Shi-Jie Zhang; Qi Wang; Li Guan (Metabolic Brain Disease, 2022)

Knowledge domain and research progress in green consumption: a phase upgrade study - Han Huang; Ruyin Long; Hong Chen; Qianwen Li; Meifen Wu; Xin Gan (Environmental Science and Pollution Research, 2022)

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Sodium tanshinone IIA sulfonate improves cognitive impairment via regulating Aβ transportation in AD transgenic mouse model - Hui-Han Ma; Can Wan; Lu-Di Zhang; Rong-Rong Zhang; Dong Peng; Li-Jun Qiao; Shi-Jie Zhang; Ye-Feng Cai; Hong-Qiang Huang (Metabolic Brain Disease, 2022)

Correction to: Role of HMGB1 in TNF-α Combined with Z-VAD-fmk-Induced L929 Cells Necroptosis - Zhao Lei; Can Yu; Xia Li; Li-Hua Huang; Zhi-Qiang Li; Hong-Wei Zhu; Duo Han; Hui Huang; Xiao Yu (Biochemical Genetics, 2022)

Role of HMGB1 in TNF-α Combined with Z-VAD-fmk-Induced L929 Cells Necroptosis - Can Yu; Zhao Lei; Xia Li; Li-Hua Huang; Zhi-Qiang Li; Hong-Wei Zhu; Duo Han; Hui Huang; Xiao Yu (Biochemical Genetics, 2022)

Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)
Sepsis can cause sepsis-associated encephalopathy (SAE), but whether SAE was induced or exacerbated by ferroptosis remains unknown. In this study, the rat sepsis model was constructed using the cecal ligation and puncture method. The blood–brain barrier (BBB) permeability was measured by Evans blue dye (EBD) in vivo. The levels of ROS, Fe ion, MDA, GSH, and GPX4 were assessed by enzyme-linked immunosorbent assay (ELISA). The exosomes isolated from serum were cultured with bEnd.3 cells for the in vitro analysis. Moreover, bEnd.3 cells cultured with 100 μM FeCl3 (iron-rich) were to simulate ferroptosis stress. The cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. A dual-luciferase reporter gene assay was performed to confirm the relationship between miR-9-5p with NEAT1, TFRC , and GOT1 . In vivo, it is found that BBB permeability was damaged in model rats. Level of ROS, Fe ion, and MDA was increased, and level of GSH and GPX4 was decreased, which means ferroptosis was induced by sepsis. Exosome-packaged NEAT1 in serum was significantly upregulated in model rats. In vitro, it is found that NEAT1 functions as a ceRNA for miR-9-5p to facilitate TFRC and GOT1 expression. Overexpression of NEAT1 enhanced ferroptosis stress in bEnd.3 cells. Increased miR-9-5p alleviated sepsis-induced ferroptosis by suppressing the expression of TFRC and GOT1 both in vivo and in vitro. In conclusion, these findings suggest that sepsis induced high expression of serous exosome-derived NEAT1, and it might exacerbate SAE by promoting ferroptosis through regulating miR-9-5p/ TFRC and GOT1 axis.

Assessment of genetic diversity among Chinese high-oleic peanut genotypes using miniature inverted-repeat transposable element markers - Chuan Tang Wang; Guo Sheng Song; Zhi Wei Wang; Hong Ju Li; Hong Wei Han; Xiao Yuan Chi; Xiu Zhen Wang; Xiu Shan Sun (Genetic Resources and Crop Evolution, 2022)

Two new nor -lignans from Selaginella pulvinata (Hook. & Grev.) Maxim and their antihyperglycemic activities - Hua-Wei Lv; Yu-Xia Li; Meng Luo; Jia-Meng Qi; Ze-Fei Fu; Hong-Jian Zhang; Yuan-Qiang Guo; Chu Chu; Han-Bing Li; Ji-Zhong Yan (Natural Product Research, 2022)

Alteribacter salitolerans sp. nov., isolated from a saline-alkaline soil - Shuang Wang; Lei Sun; Manik Prabhu Narsing Rao; Guo-Hong Liu; Pin-Jiao Jin; Zhou-Yan Dong; Zheng-Han Lian; Xiao-Yu Hao; Ming-Yi Zhang; Wen-Jun Li (Archives of Microbiology, 2022)

Sigma-1 Receptor Activation Suppresses Microglia M1 Polarization via Regulating Endoplasmic Reticulum–Mitochondria Contact and Mitochondrial Functions in Stress-Induced Hypertension Rats - Kokwin Ooi; Li Hu; Yi Feng; Chenzhi Han; Xiaorong Ren; Xinyi Qian; Haofeng Huang; Sijia Chen; Qi Shi; Hong Lin; Jijiang Wang; Danian Zhu; et al. (Molecular Neurobiology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Three new diterpenoids from Euphorbia peplus - Yan-Ni Chen; Qing-Yun Lu; Dong-Mei Li; Ying-Yao Li; Xue-Xue Pu; Bo-Ting Li; Xiao-Han Tang; Hong-Yu Tang; Shuai Liu; Lei Yang; Yu Zhang; Ying-Tong Di; et al. (Natural Product Research, 2021)

TLR2 Potentiates SR-Marco-Mediated Neuroinflammation by Interacting with the SRCR Domain - Lu Wang; Han-Yu Yang; Cai-Xia Zang; Jun-Mei Shang; Hui Liu; Zi-Hong Zhang; Fang-Yu Yuan; Cheng Ju; Fang-Yuan Li; Xiu-Qi Bao; Dan Zhang (Molecular Neurobiology, 2021)

Mutation of the sixth amino acid of the Rep protein has no effect on porcine circovirus 2b but enhances porcine circovirus 2d replication in vitro - Xiaoyan Wu; Shuo Wang; Changxun Xin; Chen Li; Jianli Shi; Zhe Peng; Chang Liu; Hong Han; Ying Yang; Yao Tian; Jiaxin Li; Shaojian Xu; et al. (Archives of Virology, 2021)

Pleosporalins H and I, two new heptaketides from the endophytic fungus Pleosporales sp. F46 by using OSMAC strategy - Hong-Xia Yang; Xiao-Ping Peng; Han Gao; Hui-Min Zhang; Zi-Ru Wang; Gang Li; Hong-Xiang Lou (Natural Product Research, 2021)

Regional brain network and behavioral alterations in EGR3 gene transfected rat model of schizophrenia - Wenwen Gao; Guangfei Li; Xiaowei Han; Zeyu Song; Shuai Zhao; Feiyi Sun; Hong Ma; Ailing Cui; Yige Wang; Xiuxiu Liu; Yue Chen; Lu Zhang; et al. (Brain Imaging and Behavior, 2021)

Methane Concentration in the Heartwood of Living Trees and Estimated Methane Emission on Stems in Upland Forests - Zhi-Ping Wang; Huan-Long Li; Hong-Hui Wu; Shi-Jie Han; Jian-Hui Huang; Xi-Mei Zhang; Xing-Guo Han (Ecosystems, 2021)

Apigenin Improves Hypertension and Cardiac Hypertrophy Through Modulating NADPH Oxidase-Dependent ROS Generation and Cytokines in Hypothalamic Paraventricular Nucleus - Hong-Li Gao; Xiao-Jing Yu; Han-Bo Hu; Qian-Wen Yang; Kai-Li Liu; Yan-Mei Chen; Yan Zhang; Dong-Dong Zhang; Hua Tian; Guo-Qing Zhu; Jie Qi; Yu-Ming Kang (Cardiovascular Toxicology, 2021)

Correlation of CD38 expression with the progression of hemorrhagic fever with renal syndrome - Han-Dong Zhao; Yan-Ping Li; Wei-Wei Zhao; Peng Li; Hong-Li Liu (Archives of Virology, 2021)

Overexpression of Cell-Surface Marker SLC16A1 Shortened Survival in Human High-Grade Gliomas - Hong-Han Lin; Wen-Chiuan Tsai; Chia-Kuang Tsai; Ssu-Han Chen; Li-Chun Huang; Dueng-Yuan Hueng; Kuang-Chen Hung (Journal of Molecular Neuroscience, 2021)

A luminescent Zn(II)-Containing Complex: Selective Sensing of Cr(VI) Anion and Application Values on Tuberculosis Care Through Increasing the Antibacterial Response of Macrophages - Jin-Chao Mao; Jin-Jing Hong; Ming-Zheng Lin; Feng Han; Dong Li (Journal of Fluorescence, 2021)

Biological characteristics and salt-tolerant plant growth-promoting effects of an ACC deaminase-producing Burkholderia pyrrocinia strain isolated from the tea rhizosphere - Lizhen Han; Hong Zhang; Yu Xu; Ying Li; Jing Zhou (Archives of Microbiology, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Integrated Analysis of Coding Genes and Non-coding RNAs Associated with Shell Color in the Pacific Oyster (Crassostrea gigas) - Zhuanzhuan Li; Qi Li; Shikai Liu; Ziqiang Han; Lingfeng Kong; Hong Yu (Marine Biotechnology, 2021)

The Knowledge and Attitude Towards Advance Care Planning Among Chinese Patients with Advanced Cancer - Xiao-Ting Hou; Yu-Han Lu; Hong Yang; Ren-Xiu Guo; Yun Wang; Li-Hong Wen; Ya-Ru Zhang; Hong-Yu Sun (Journal of Cancer Education, 2021)

Occurrence, distribution, and partitioning of antibiotics in surface water and sediment in a typical tributary of Yellow River, China - Linfang Wang; Hua Li; Jinhua Dang; Hong Guo; Yu’en Zhu; Wenhui Han (Environmental Science and Pollution Research, 2021)

Taste Masking Study Based on an Electronic Tongue: the Formulation Design of 3D Printed Levetiracetam Instant-Dissolving Tablets - Zengming Wang; Jingru Li; Xiaoxuan Hong; Xiaolu Han; Boshi Liu; Xianfu Li; Hui Zhang; Jing Gao; Nan Liu; Xiang Gao; Aiping Zheng (Pharmaceutical Research, 2021)
Purpose Proper taste-masking formulation design is a critical issue for instant-dissolving tablets (IDTs). The purpose of this study is to use the electronic tongue to design the additives of the 3D printed IDTs to improve palatability. Methods A binder jet 3D printer was used to prepare IDTs of levetiracetam. A texture analyzer and dissolution apparatus were used to predict the oral dispersion time and in vitro drug release of IDTs, respectively. The palatability of different formulations was investigated using the ASTREE electronic tongue in combination with the design of experiment and a model for masking bitter taste. Human gustatory sensation tests were conducted to further evaluate the credibility of the results. Results The 3D printed tablets exhibited rapid dispersion (<30 s) and drug release (2.5 min > 90%). The electronic tongue had an excellent ability of taste discrimination, and levetiracetam had a good linear sensing performance based on a partial least square regression analysis. The principal component analysis was used to analyze the signal intensities of different formulations and showed that 2% sucralose and 0.5% spearmint flavoring masked the bitterness well and resembled the taste of corresponding placebo. The results of human gustatory sensation test were consistent with the trend of the electronic tongue evaluation. Conclusions Owing to its objectivity and reproducibility, this technique is suitable for the design and evaluation of palatability in 3D printed IDT development.

Sex Differences in Electrophysiological Properties of Mouse Medial Preoptic Area Neurons Revealed by In Vitro Whole-cell Recordings - Wen Zhang; Shuai-shuai Li; Ying Han; Xiao-Hong Xu (Neuroscience Bulletin, 2021)

Curcumin protects thymus against D-galactose-induced senescence in mice - Jie-han Li; Ting-ting Wei; Li Guo; Jia-hui Cao; Yuan-kang Feng; Shu-ning Guo; Guo-hong Liu; Yi Ding; Yu-rong Chai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

TRIP13 promotes the proliferation and invasion of lung cancer cells via the Wnt signaling pathway and epithelial–mesenchymal transition - Zhi-Han Li; Lei Lei; Liang-Ru Fei; Wen-Jing Huang; Yi-Wen Zheng; Mai-Qing Yang; Zhao Wang; Chen-Chen Liu; Hong-Tao Xu (Journal of Molecular Histology, 2021)

Wolbachia and Spiroplasma could influence bacterial communities of the spider mite Tetranychus truncatus - Kun Yang; Han Chen; Xiao-Li Bing; Xue Xia; Yu-Xi Zhu; Xiao-Yue Hong (Experimental and Applied Acarology, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Detection and genetic characteristics of porcine bocavirus in central China - Lan-Lan Zheng; Jian-Tao Cui; Han Qiao; Xin-Sheng Li; Xiao-Kang Li; Hong-Ying Chen (Archives of Virology, 2021)

A Clipless Pedal-Sensor System for Three Dimensional Kinetic Analysis During Cycling - Kai-Han Liang; Hong-Wen Wu; Li-Cheng Hsieh; Yi-Wen Chang (Journal of Medical and Biological Engineering, 2020)

Characterization of a Protease Hyper-Productive Mutant of Bacillus pumilus by Comparative Genomic and Transcriptomic Analysis - Yong-Cheng Liu; Lin-Li Han; Tian-Yu Chen; Yan-Bing Lu; Hong Feng (Current Microbiology, 2020)

What factors determine the mass elevation effect of the Tibetan Plateau? - Fang Han; Li Wan; Hong-zhi Wu; Bai-ping Zhang; Lan Gao; Ge Song (Journal of Mountain Science, 2020)

Creation of fertility-restored materials for Ogura CMS in Brassica oleracea by introducing Rfo gene from Brassica napus via an allotriploid strategy - Hai-long Yu; Zhi-yuan Li; Wen-jing Ren; Feng-qing Han; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Yu-mei Liu; Zhi-yuan Fang; Yang-yong Zhang (Theoretical and Applied Genetics, 2020)
Key message Ogura CMS fertility-restored materials, with 18 chromosomes, normal seed setting, stable fertility and closer genetic background to the parent Chinese kale, were successfully developed in B. oleracea via a triploid strategy for the first time. Abstract Ogura cytoplasmic male sterility (CMS) is the most widely used sterile type in seed production for commercial hybrids of Brassica oleracea vegetables. However, the natural Ogura CMS restorer line has not been found in B. oleracea crops. In this study, the triploid strategy was used with the aim to create euploid B. oleracea progenies with the Rfo gene. The allotriploid AAC hybrid YL2 was used as a male parent to backcross with Ogura CMS Chinese kale. After successive backcrosses, the BC 2 Rfo -positive individual 16CMSF2-11 and its BC 3 progenies, with 18 chromosomes, were developed, which were morphologically identical to the parent Chinese kale. Compared with F 1 and BC 1 plants, it showed stable fertility performance, and regular meiosis behavior and could produce seeds normally under natural pollination. The genomic composition analysis of Rfo -positive progenies by using molecular markers showed that more than 87% of the C-genome components of BC 3 Rfo -progenies recovered to the parent Chinese kale, while most or all of the A n -genome segments were lost in 16CMSF2-11 and its progenies. The results suggested that the genetic background of Rfo -positive individuals was closer to that of the parent Chinese kale along with backcrossing. Hereof, the Ogura CMS fertility-restored materials of Chinese kale were successfully created via triploid strategy for the first time, providing a bridge for utilizing the Ogura CMS B. oleracea germplasm in the future. Moreover, our study indicates that the triploid strategy is effective for transferring genes from B. napus into B. oleracea .

Pre-symptomatic local brain activity and functional connectivity alterations in nasopharyngeal carcinoma patients who developed radiation encephalopathy following radiotherapy - You-ming Zhang; Jian-ming Gao; Hong Zhou; Li Li; Li-zhi Liu; Zai-de Han; Xiao-ping Yi; Wei-hua Liao (Brain Imaging and Behavior, 2020)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Characteristics of the spike and ORF3 genes of porcine epidemic diarrhea virus in Henan and Shanxi provinces of China - Jian-tao Cui; Han Qiao; Cheng-yao Hou; Hui-Hua Zheng; Xin-Sheng Li; Lan-lan Zheng; Hong-Ying Chen (Archives of Virology, 2020)

Molecular epidemiology of enteroviruses associated with severe hand, foot and mouth disease in Shenzhen, China, 2014-2018 - Long Chen; Shao-Jian Xu; Xiang-Jie Yao; Hong Yang; Hai-Long Zhang; Jun Meng; Han-Ri Zeng; Xu-He Huang; Ren-Li Zhang; Ya-Qing He (Archives of Virology, 2020)

Combined effects of green manure returning and addition of sewage sludge compost on plant growth and microorganism communities in gold tailings - Yan-Jun Ai; Fu-Ping Li; Hai-Hong Gu; Xiao-Jie Chi; Xue-Tao Yuan; Dong-Yun Han (Environmental Science and Pollution Research, 2020)

Estimating purple-soil moisture content using Vis-NIR spectroscopy - Yu Gou; Jie Wei; Jin-lin Li; Chen Han; Qing-yan Tu; Chun-hong Liu (Journal of Mountain Science, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Privet golden leaves adapt unexpectedly well to light changes - Ming Yuan; Bo Huang; Li-Hua Dong; Qiao-Hong Han; Yong Yang; Chun-Bang Ding; Chao Hu; Yang-Er Chen; Zhong-Wei Zhang; Shu Yuan (Horticulture, Environment, and Biotechnology, 2020)

Long noncoding RNA LINC00520 accelerates the progression of colorectal cancer by serving as a competing endogenous RNA of microRNA-577 to increase HSP27 expression - Xi-Han Jin; Yong-Gang Hong; Peng Li; Li-Qiang Hao; Ming Chen (Human Cell, 2020)

Scutellarin Exerts Anti-Inflammatory Effects in Activated Microglia/Brain Macrophage in Cerebral Ischemia and in Activated BV-2 Microglia Through Regulation of MAPKs Signaling Pathway - Hao-Lun Chen; Wen-Ji Jia; Hong-E Li; Hong Han; Fan Li; Xiao-Li-Na Zhang; Juan-Juan Li; Yun Yuan; Chun-Yun Wu (NeuroMolecular Medicine, 2020)

Identification, characterization, and functional prediction of circular RNAs in maize - Yang Han; Xinxin Li; Yan Yan; Ming-Hua Duan; Jian-Hong Xu (Molecular Genetics and Genomics, 2020)

Sources and ore-forming fluid pathways of carbonate-hosted Pb–Zn deposits in Southwest China: implications of Pb–Zn–S–Cd isotopic compositions - Chong Xu; Hong Zhong; Rui-Zhong Hu; Han-Jie Wen; Wei-Guang Zhu; Zhong-Jie Bai; Hai-Feng Fan; Fang-Fang Li; Ting Zhou (Mineralium Deposita, 2020)

DNA stable isotope probing revealed no incorporation of 13CO2 into comammox Nitrospira but ammonia-oxidizing archaea in a subtropical acid soil - Zi-Yang He; Ju-Pei Shen; Li-Mei Zhang; Hua-Jing Tian; Bing Han; Hong-Jie Di; Ji-Zheng He (Journal of Soils and Sediments, 2020)

Fupyrones A and B, two new α -pyrones from an endophytic fungus, Fusarium sp. F20 - Han Gao; Gang Li; Xiao-Ping Peng; Hong-Xiang Lou (Natural Product Research, 2020)

Characterization of the immunological factors in turbot (Scophthalmus maximus) seminal plasma and their correlation with sperm quality - Ming Ming Han; Fu Hong Ding; Jun Li (Aquaculture International, 2019)

Molecular identification and detection of Wohlfahrtia magnifica in ovine vulvar myiasis in Gansu, China - Youquan Li; Xuan Li; Junlong Liu; Aihong Liu; Pengfei Guo; Yuan Han; Youjun Shang; Guiquan Guan; Zhijie Liu; Guangyuan Liu; Jianxun Luo; Hong Yin (Tropical Animal Health and Production, 2019)

Quantifying Flood Frequency Modification Caused by Multi-Reservoir Regulation - Yi-han Tang; Jie-feng Wu; Pei-yi Li; Li-juan Zhang; Xiao-hong Chen; Kai-rong Lin (Water Resources Management, 2019)

Potential of C1QTNF1-AS1 regulation in human hepatocellular carcinoma - Weijie Han; Guofeng Yu; Xianmei Meng; Hong Hong; Liansheng Zheng; Xiaobo Wu; Dongsheng Zhang; Boshi Yan; Yongqiang Ma; Xiaolong Li; Qiuhong Wang (Molecular and Cellular Biochemistry, 2019)

Using two contrasting methods with the same tracers to trace the main sediment source in a mountainous catchment - Han Wu; Dong-hong Xiong; Su Zhang; Yong Yuan; Wan-Xin Li; Lin Liu; Zheng-an Su; Xiao-ning Lu (Journal of Mountain Science, 2019)

Comparative analysis of a panel of biomarkers related to protein phosphatase 2A between laryngeal squamous cell carcinoma tissues and adjacent normal tissues - Han-ying Wang; Hui Yuan; Jing-hui Liu; Bei-lei Wang; Kai-lun Xu; Pu Huang; Zhi-hong Lin; Li-hong Xu (Journal of Zhejiang University-SCIENCE B, 2019)

Automatic sub-pixel coastline extraction based on spectral mixture analysis using EO-1 Hyperion data - Zhonghua Hong; Xuesu Li; Yanling Han; Yun Zhang; Jing Wang; Ruyan Zhou; Kening Hu (Frontiers of Earth Science, 2019)

Radiation-induced hippocampal atrophy in patients with nasopharyngeal carcinoma early after radiotherapy: a longitudinal MR-based hippocampal subfield analysis - Xiaofei Lv; Haoqiang He; Yadi Yang; Lujun Han; Zheng Guo; Hong Chen; Jing Li; Yingwei Qiu; Chuanmiao Xie (Brain Imaging and Behavior, 2019)

Anti-secretogranin III therapy of oxygen-induced retinopathy with optimal safety - Fen Tang; Michelle E. LeBlanc; Weiwen Wang; Dan Liang; Ping Chen; Tsung-Han Chou; Hong Tian; Wei Li (Angiogenesis, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Vildagliptin, an Anti-diabetic Drug of the DPP-4 Inhibitor, Induces Vasodilation via Kv Channel and SERCA Pump Activation in Aortic Smooth Muscle - Mi Seon Seo; Hongliang Li; Jin Ryeol An; In Duk Jung; Won-Kyo Jung; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Il-Whan Choi; Won Sun Park (Cardiovascular Toxicology, 2019)

Trace Elements in the Feathers of Waterfowl from Nanhaizi Wetland, Baotou, China - Li Liu; Xiao-Guang Liu; Yan Sun; Zi-Han Pu; Hong-Ying Xu; Wen-Xiu Li; Zhi-hong Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

Effect of Fluoride on Small Intestine Morphology and Serum Cytokine Contents in Rats - Hong-wei Wang; Jing Liu; Wen-peng Zhao; Zi-hao Zhang; Si-qi Li; Si-han Li; Shi-quan Zhu; Bian-hua Zhou (Biological Trace Element Research, 2019)

A Spatial Ecology Study of Keshan Disease and Hair Selenium - Xiao Zhang; Tong Wang; Shie Li; Chao Ye; Jie Hou; Qi Li; Hong Liang; Huihui Zhou; Zhongying Guo; Xiaomin Han; Zhe Wang; Huan Wu; et al. (Biological Trace Element Research, 2019)

BDNF-mediated mitophagy alleviates high-glucose-induced brain microvascular endothelial cell injury - Hong Jin; Yi Zhu; Yiping Li; Xiuyu Ding; Wenqi Ma; Xiqiong Han; Bilei Wang (Apoptosis, 2019)

Analysis of genetic variation of porcine circovirus type 2 within pig populations in central China - Peng-Li Xu; Yu Zhao; Hui-Hua Zheng; Run-Bo Tian; Hao-Ying Han; Hong-Ying Chen; Lan-Lan Zheng (Archives of Virology, 2019)

High-sensitivity neuroimaging biomarkers for the identification of amnestic mild cognitive impairment based on resting-state fMRI and a triple network model - Enyan Yu; Zhengluan Liao; Yunfei Tan; Yaju Qiu; Junpeng Zhu; Zhang Han; Jue Wang; Xinwei Wang; Hong Wang; Yan Chen; Qi Zhang; Yumei Li; et al. (Brain Imaging and Behavior, 2019)

Evaluation of a Potential Clinical Significant Drug-Drug Interaction between Digoxin and Bupropion in Cynomolgus Monkeys - Yang Shen; Yang Yu; Wei Lai; Shuai Li; Zixuan Xu; Jiejing Jin; Xia Yan; Han Xing; Xijing Chen; Aizhen Xiong; Chunhua Xia; Jiake He; et al. (Pharmaceutical Research, 2019)

Structure and fracture-cavity identification of epimetamorphic volcanic-sedimentary rock basement reservoir: a case study from central Hailar Basin, China - Juan Li; Guangpo Chen; Bin Zhang; Liang Hong; Qianfeng Han (Arabian Journal of Geosciences, 2019)

Evaluation of Calcium Oxide of Quicklime and Si–Ca–Mg Fertilizer for Remediation of Cd Uptake in Rice Plants and Cd Mobilization in Two Typical Cd-Polluted Paddy Soils - Xin-Yang Li; Jian Long; Pei-Qin Peng; Qi Chen; Xia Dong; Kai Jiang; Hong-Bo Hou; Bo-Han Liao (International Journal of Environmental Research, 2018)

Low root/shoot (R/S) biomass ratio can be an indicator of low cadmium accumulation in the shoot of Chinese flowering cabbage (Brassica campestris L. ssp. chinensis var. utilis Tsen et Lee) cultivars - Zhi-Min Xu; Xiu-Qin Mei; Ling Tan; Qu-Sheng Li; Li-Li Wang; Bao-Yan He; Shi-Hong Guo; Chu Zhou; Han-Jie Ye (Environmental Science and Pollution Research, 2018)

Alterations of ATP-sensitive K+ channels in human umbilical arterial smooth muscle during gestational diabetes mellitus - Hongliang Li; Sung Eun Shin; Mi Seon Seo; Jin Ryeol An; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Jeeyoung Kim; Mi-Jin Yim; Jeong Min Lee; Tae Gyu An; Jihan Jeon; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Combination of NAD+ and NADPH Offers Greater Neuroprotection in Ischemic Stroke Models by Relieving Metabolic Stress - Qiao Huang; Meiling Sun; Mei Li; Dingmei Zhang; Feng Han; Jun Chao Wu; Kohji Fukunaga; Zhong Chen; Zheng-Hong Qin (Molecular Neurobiology, 2018)

Exploring inhibition mechanism and nature of lipase by Ligupurpuroside A extracted from Ku-Ding tea - Yu Fan; Yang Xu; Qing-Guo Han; Liang-Liang Shen; Hong Xu; Zhi-Bing Wu; Xu Xu; Ming Ying; Zhen-Dan He; Zhang-Li Hu (Medicinal Chemistry Research, 2018)

Phthalate esters distribution in coastal mariculture of Hong Kong, China - Zhang Cheng; Han-Han Li; Lin Yu; Zhan-Biao Yang; Xiao-Xun Xu; Hong-Sheng Wang; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Inhibition of the Voltage-Dependent K+ Current by the Tricyclic Antidepressant Desipramine in Rabbit Coronary Arterial Smooth Muscle Cells - Sung Eun Shin; Hongliang Li; Jin Ryeol An; Mi Seon Seo; Sung Hun Na; Won-Kyo Jung; Amy L. Firth; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Il-Whan Choi; Won Sun Park (Cardiovascular Toxicology, 2018)

Cotton (Gossypium hirsutum) JAZ3 and SLR1 function in jasmonate and gibberellin mediated epidermal cell differentiation and elongation - Xiao-Cong Xia; Qian-Qian Hu; Wen Li; Yun Chen; Li-Hong Han; Miao Tao; Wen-Ying Wu; Xue-Bao Li; Geng-Qing Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Early diagnosis of acute kidney injury in aged patients undergoing percutaneous coronary intervention - Hong-hua Ye; Gen Shen; Qun Luo; Fang-fang Zhou; Xiao-ling Xie; Chun-yan Wang; Li-na Han (Journal of Zhejiang University-SCIENCE B, 2018)

A new DDA model for kinematic analyses of rockslides on complex 3-D terrain - Hong Zhang; Shu-guang Liu; Wei Wang; Lu Zheng; Ying-bin Zhang; Yan-qiang Wu; Zheng Han; Yan-ge Li; Guang-qi Chen (Bulletin of Engineering Geology and the Environment, 2018)

Yield enhancement strategies of rare pharmaceutical metabolites from endophytes - Fangxue Xu; Shiyuan Wang; Yujuan Li; Mengmeng Zheng; Xiaozhi Xi; Hui Cao; Xiaowei Cui; Hong Guo; Chunchao Han (Biotechnology Letters, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Complete nucleotide sequence of jasmine virus H, a new member of the family Tombusviridae - Tao Zhuo; Li-Juan Zhu; Cheng-Cong Lu; Chao-Yang Jiang; Zi-Yin Chen; Guangzhi Zhang; Zong-Hua Wang; Juan Jovel; Yan-Hong Han (Archives of Virology, 2018)

The persistent prevalence and evolution of cross-family recombinant coronavirus GCCDC1 among a bat population: a two-year follow-up - Joseph O. Obameso; Hong Li; Hao Jia; Min Han; Shiyan Zhu; Canping Huang; Yuhui Zhao; Min Zhao; Yu Bai; Fei Yuan; Honglan Zhao; Xia Peng; et al. (Science China Life Sciences, 2017)

Phylogenetic and genetic characterization of a 2017 clinical isolate of H7N9 virus in Guangzhou, China during the fifth epidemic wave - Yongqiang Deng; Chunlin Li; Jianfeng Han; Yingfen Wen; Jian Wang; Wenxing Hong; Xiaofeng Li; Zhongyu Liu; Qing Ye; Jing Li; Changshuai Zhou; Lei Yu; et al. (Science China Life Sciences, 2017)

Nanoparticle-encapsulated emodin decreases diabetic neuropathic pain probably via a mechanism involving P2X3 receptor in the dorsal root ganglia - Lin Li; Xuan Sheng; Shanhong Zhao; Lifang Zou; Xinyao Han; Yingxin Gong; Huilong Yuan; Liran Shi; Lili Guo; Tianyu Jia; Shuangmei Liu; Bing Wu; et al. (Purinergic Signalling, 2017)

Kinsenoside and polysaccharide production by rhizome culture of Anoectochilus roxburghii in continuous immersion bioreactor systems - Mei-Yu Jin; Lu Han; He Li; Hong-Qiu Wang; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Down-regulation of Noggin and miR-138 coordinately promote osteogenesis of mesenchymal stem cells - Xing-Kun Sun; Jin Zhou; Lei Zhang; Tian Ma; Yu-Han Wang; Yan-Mei Yang; Yan-Ting Tang; Hong Li; Li-Jun Wang (Journal of Molecular Histology, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Interannual variation in methane emissions from tropical wetlands triggered by repeated El Niño Southern Oscillation - Qiuan Zhu; Changhui Peng; Philippe Ciais; Hong Jiang; Jinxun Liu; Philippe Bousquet; Shiqin Li; Jie Chang; Xiuqin Fang; Xiaolu Zhou; Huai Chen; Shirong Liu; et al. (Global Change Biology, 2017)
Methane (CH 4 ) emissions from tropical wetlands contribute 60%–80% of global natural wetland CH 4 emissions. Decreased wetland CH 4 emissions can act as a negative feedback mechanism for future climate warming and vice versa. The impact of the El Niño–Southern Oscillation (ENSO) on CH 4 emissions from wetlands remains poorly quantified at both regional and global scales, and El Niño events are expected to become more severe based on climate models’ projections. We use a process‐based model of global wetland CH 4 emissions to investigate the impacts of the ENSO on CH 4 emissions in tropical wetlands for the period from 1950 to 2012. The results show that CH 4 emissions from tropical wetlands respond strongly to repeated ENSO events, with negative anomalies occurring during El Niño periods and with positive anomalies occurring during La Niña periods. An approximately 8‐month time lag was detected between tropical wetland CH 4 emissions and ENSO events, which was caused by the combined time lag effects of ENSO events on precipitation and temperature over tropical wetlands. The ENSO can explain 49% of interannual variations for tropical wetland CH 4 emissions. Furthermore, relative to neutral years, changes in temperature have much stronger effects on tropical wetland CH 4 emissions than the changes in precipitation during ENSO periods. The occurrence of several El Niño events contributed to a lower decadal mean growth rate in atmospheric CH 4 concentrations throughout the 1980s and 1990s and to stable atmospheric CH 4 concentrations from 1999 to 2006, resulting in negative feedback to global warming.

Two new cadinane-type sesquiterpenes from cultures of the basidiomycete Trichaptum pargamenum - Bin Tang; Xi Du; Han-An Long; Jun Du; Jian-Min Guo; Xin Hu; Hua Tu; Li Yang; Hong-Jin Liu (Natural Product Research, 2017)

Numerical simulation for run-out extent of debris flows using an improved cellular automaton model - Zheng Han; Yange Li; Jianling Huang; Guangqi Chen; Linrong Xu; Chuan Tang; Hong Zhang; Yonghui Shang (Bulletin of Engineering Geology and the Environment, 2017)

Life cycle environmental assessment of industrial hazardous waste incineration and landfilling in China - Jinglan Hong; Xiaofei Han; Yilu Chen; Meng Wang; Liping Ye; Congcong Qi; Xiangzhi Li (The International Journal of Life Cycle Assessment, 2017)

Analysis of diagnosis and treatment of lipoblastomatosis - Zhiqiang Mo; Xianghui Xie; Huanmin Wang; Hong Qin; Wei Han; Xiaosong Li (Science China Life Sciences, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Work stress, family stress and asthma: a cross-sectional study among women in China - Adrian Loerbroks; Hui Ding; Wei Han; Hong Wang; Jiang-Ping Wu; Liu Yang; Peter Angerer; Jian Li (International Archives of Occupational and Environmental Health, 2017)

Skarn mineralogy and its geological significance for the Tayuan (Cu–Mo)–Pb–Zn deposit, northern Daxinganling metallogenic belt - Chao Li; Tao Ren; Jian-Guo Huang; Run-Sheng Han; He-Jun Yin; Hong-Yang Zhou; Zhi-Hong Feng (Acta Geochimica, 2017)

Wind and salt spray alter tree shape and dry mass density in Casuarina equisetifolia L. - Yongming Lin; Jian Li; Jonathan D. Bakker; Han Lin; Can Chen; Wei Hong; Loretta Fisher; Chengzhen Wu; Tao Hong; Haojun Deng; Guangshuai Zhang; Kun Du (Trees, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

The class III anti-arrhythmic agent, amiodarone, inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Hongliang Li; Han Sol Kim; Hye Won Kim; Sung Eun Shin; Won-Kyo Jung; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Amy L. Firth; Young Min Bae; Il-Whan Choi; Won Sun Park (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Gene characterization and transcription analysis of two new ammonium transporters in pear rootstock (Pyrus betulaefolia) - Hui Li; Jin-Long Han; You-Hong Chang; Jing Lin; Qing-Song Yang (Journal of Plant Research, 2016)

A new cytotoxic biflavonoid from the rhizome of Wikstroemia indica - Meng Shao; Xiao-Jun Huang; Jun-Shan Liu; Wei-Li Han; Hong-Bing Cai; Qing-Fa Tang; Qin Fan (Natural Product Research, 2016)

Laboratory evaluation of Beauveria bassiana and Metarhizium anisopliae in the control of Haemaphysalis qinghaiensis in China - Qiaoyun Ren; Ze Chen; Jin Luo; Guangyuan Liu; Guiquan Guan; Zhijie Liu; Aihong Liu; Youquan Li; Qingli Niu; Junlong Liu; Jifei Yang; Xueqing Han; et al. (Experimental and Applied Acarology, 2016)

A Model for Simulating the Soil Organic Carbon Pool of Steppe Ecosystems - Li Guoqing; Li Xiaobing; Zhou Tao; Wang Hong; Li Ruihua; Wang Han; Wei Dandan (Environmental Modeling & Assessment, 2016)

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity - Da-Hong Li; Tong Han; Li-Ping Guan; Jiao Bai; Nan Zhao; Zhan-Lin Li; Xin Wu; Hui-Ming Hua (Natural Product Research, 2016)

Genetic variation in APE1 gene promoter is associated with noise-induced hearing loss in a Chinese population - Huanxi Shen; Jianrui Dou; Lei Han; Ying Bai; Qian Li; Zhiqiang Hong; Jian Shi; Hengdong Zhang; Feng Zhang; Cheng Du; Zhimin Tong; Baoli Zhu (International Archives of Occupational and Environmental Health, 2016)

Protection of Luteolin-7-O-Glucoside Against Doxorubicin-Induced Injury Through PTEN/Akt and ERK Pathway in H9c2 Cells - Hong Yao; Zhimei Shang; Penghong Wang; Shuixian Li; Qianyun Zhang; Huiqin Tian; Dongmei Ren; Xiuzhen Han (Cardiovascular Toxicology, 2016)

Characterization of the novel T4-like Salmonella enterica bacteriophage STP4-a and its endolysin - Meng Li; Mengzhe Li; Hong Lin; Jingxue Wang; Yanqiu Jin; Feng Han (Archives of Virology, 2016)

Myeloid-Specific Blockade of Notch Signaling by RBP-J Knockout Attenuates Spinal Cord Injury Accompanied by Compromised Inflammation Response in Mice - Bei-Yu Chen; Min-Hua Zheng; Yan Chen; Yan-Ling Du; Xiao-Long Sun; Xing Zhang; Li Duan; Fang Gao; Liang Liang; Hong-Yan Qin; Zhuo-Jing Luo; Hua Han (Molecular Neurobiology, 2015)

Radix ranunculus temate saponins induces apoptosis via the death receptor and mitochondrial pathways in SGC-7901 cells - Mao-lin Li; Han-min Gu; Hong-ya Hang; Yao-li Jiang; Jiao Jiang; Qian-na Gu; Wen-yan Wu (Molecular & Cellular Toxicology, 2015)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

Silicon improves salt tolerance by increasing root water uptake in Cucumis sativus L. - Yong-Xing Zhu; Xuan-Bin Xu; Yan-Hong Hu; Wei-Hua Han; Jun-Liang Yin; Huan-Li Li; Hai-Jun Gong (Plant Cell Reports, 2015)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Influence of meadow changes on net primary productivity: a case study in a typical steppe area of XilinGol of Inner Mongolia in China - Xiaobing Li; Guoqing Li; Hong Wang; Han Wang; Jingjing Yu (Geosciences Journal, 2015)

Detection of gas hydrate sediments using prestack seismic AVA inversion - Ru-Wei Zhang; Hong-Qi Li; Bao-Jin Zhang; Han-Dong Huang; Peng-Fei Wen (Applied Geophysics, 2015)

A γ-Glutamylcysteine Synthetase Gene from Pyrus calleryana Is Responsive to Ions and Osmotic Stresses - Hui Li; Jin-long Han; Jing Lin; Qing-song Yang; You-hong Chang (Plant Molecular Biology Reporter, 2015)

Distribution of Yeast Isolates from Invasive Infections and Their In Vitro Susceptibility to Antifungal Agents: Evidence from 299 Cases in a 3-Year (2010 to 2012) Surveillance Study - Wei Li; Yu-an Hu; Fang-qiu Li; Li-ning Shi; Hai-feng Shao; Mei Huang; Ying Wang; Dan-dan Han; Hong Liao; Chun-fang Ma; Guo-yong Zhang (Mycopathologia, 2015)

Potent CDC25B and PTP1B phosphatase inhibitors: 2′,4′,6′-trihydroxylchalcone derivatives - Shui-Lian Zhao; Zhou Peng; Xing-Hua Zhen; Hong-Guo Jin; Yan Han; You-Le Qu; Li-Ping Guan (Medicinal Chemistry Research, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Combined action of an antioxidant defence system and osmolytes on drought tolerance and post-drought recovery of Phoebe zhennan S. Lee saplings - Yi Hu; Bin Wang; Tingxing Hu; Hong Chen; Han Li; Wei Zhang; Yu Zhong; Hongling Hu (Acta Physiologiae Plantarum, 2015)

Does Haemaphysalis bispinosa (Acari: Ixodidae) really occur in China? - Ze Chen; Youquan Li; Qiaoyun Ren; Zhijie Liu; Jin Luo; Kai Li; Guiquan Guan; Jifei Yang; Xueqing Han; Guangyuan Liu; Jianxun Luo; Hong Yin (Experimental and Applied Acarology, 2015)

SOCS3 methylation in synergy with Reg3A overexpression promotes cell growth in pancreatic cancer - Jun Wang; Hong Zhou; Yong Han; Xiulan Liu; Min Wang; Xin Wang; Guoxiao Yin; Xu Li; Ming Xiang (Journal of Molecular Medicine, 2014)

Effects of calcium carbonate on the survival of Ralstonia solanacearum in soil and control of tobacco bacterial wilt - Kai He; Shui-Ying Yang; Hong Li; Han Wang; Zhen-Lun Li (European Journal of Plant Pathology, 2014)

Bone morphogenetic protein-4 induces upregulation of Cav3.1 Ca2+ channels in HL-1 atrial myocytes - Chao-Wei Hu; Qi Li; Ying Zhang; Yu-Hong Li; Hong-Chao Jiang; Ming-Yu Liu; Shan-Liang Li; Wei Han; De-Li Dong (Pflügers Archiv - European Journal of Physiology, 2014)

Association study of a common genetic variant in pre-miR-1596 with chicken performance traits - Hong Li; Yadong Tian; Guirong Sun; Xiaojun Liu; Ruirui Jiang; Ruili Han; Guoxi Li; Xiangtao Kang (Molecular Biology Reports, 2014)

Susceptibility of the tick Haemaphysalis qinghaiensis to isolates of the fungus Metarhizium anisopliae in China - Qiaoyun Ren; Ming Sun; Guiquan Guan; Zhijie Liu; Ze Chen; Aihong Liu; Youquan Li; Miling Ma; Jifei Yang; Qingli Niu; Junlong Liu; Xueqing Han; et al. (Experimental and Applied Acarology, 2014)

Two Chinese pedigrees for adenomatous polyposis coli: new mutations at codon 1309 and predisposition to phenotypic variations - Dai-Xiang Liao; Bing Li; Xue-Mei Du; Jun-Hui Yu; Hong Chang; Zhi-Qiang Wu; Hao-Jie Hao; You-Xin Wang; Wei-Dong Han; Shu-jun Cheng; Cheng-Hua Luo (Familial Cancer, 2014)

Dietary threonine requirement of juvenile Nile tilapia, Oreochromis niloticus - Yirong Yue; Zhiying Zou; Jinglin Zhu; Dayu Li; Wei Xiao; Jue Han; Hong Yang (Aquaculture International, 2014)

Degradation of oxalic acid by the mycoparasite C oniothyrium minitans plays an important role in interacting with S clerotinia sclerotiorum - Li‐Mei Zeng; Jing Zhang; Yong‐Chao Han; Long Yang; Ming‐de Wu; Dao‐Hong Jiang; Weidong Chen; Guo‐Qing Li (Environmental Microbiology, 2014)
Summary C oniothyrium minitans ( Cm ) is a mycoparasite of the phytopathogenic fungus S clerotinia sclerotiorum ( Ss ). Ss produces a virulence factor oxalic acid ( OA ) which is toxic to plants and also to Cm , and Cm detoxifies OA by degradation. In this study, two oxalate decarboxylase genes, Cmoxdc1 and Cmoxdc2 , were cloned from Cm strain Chy‐1. OA and low pH induced expression of Cmoxdc1 , but not Cmoxdc2 . Cmoxdc1 was partially responsible for OA degradation, whereas Cmoxdc2 had no effect on OA degradation. Disruption of Cmoxdc1 in Cm reduced its ability to infect Ss in dual cultures where OA accumulated. Compared with Chy ‐1, the Cmoxdc1 ‐disrupted mutants had reduced expression levels of two mycoparasitism‐related genes chitinase ( Cmch1 ) and β‐1,3‐glucanase ( Cmg1 ), and had no detectable activity of extracellular proteases in the presence of OA . On the other hand, the cultural filtrates of the Cmoxdc1 ‐disrupted mutants in OA ‐amended media showed enhanced antifungal activity, possibly because of increased production of antifungal substances under acidic pH condition resulted from reduced Cmoxdc1 ‐ mediated OA degradation. This study provides direct genetic evidence of OA degradation regulating mycoparasitism and antibiosis of Cm against Ss , and sheds light on the sophisticated strategies of Cm in interacting with metabolically active mycelia and dormant sclerotia of Ss .

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Retrieval of aerosol optical properties over a vegetation surface using multi-angular, multi-spectral, and polarized data - Han Wang; Xiaobing Sun; Bin Sun; Tianquan Liang; Cuili Li; Jin Hong (Advances in Atmospheric Sciences, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Streptomyces jiujiangensis sp. nov., isolated from soil in South China - Bing-Huo Zhang; Juan Cheng; Li Li; Yong-Guang Zhang; Hong-Fei Wang; Han-Quan Li; Jian-Yuan Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Regulation of synchronism by abscisic-acid-responsive small noncoding RNAs during somatic embryogenesis in larch (Larix leptolepis) - Jun-Hong Zhang; Shou-Gong Zhang; Shui-Gen Li; Su-Ying Han; Wan-Feng Li; Xin-Min Li; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Family-based association study of ZNF533, DOCK4 and IMMP2L gene polymorphisms linked to autism in a northeastern Chinese Han population - Shuang Liang; Xue-lai Wang; Ming-yang Zou; Han Wang; Xue Zhou; Cai-hong Sun; Wei Xia; Li-jie Wu; Takashi X. Fujisawa; Akemi Tomoda (Journal of Zhejiang University-SCIENCE B, 2014)

The post-transcriptional regulation of LaSCL6 by miR171 during maintenance of embryogenic potential in Larix kaempferi (Lamb.) Carr. - Wan-Feng Li; Shou-Gong Zhang; Su-Ying Han; Tao Wu; Jun-Hong Zhang; Li-Wang Qi (Tree Genetics & Genomes, 2014)

Proteomics to reveal metabolic network shifts towards lipid accumulation following nitrogen deprivation in the diatom Phaeodactylum tricornutum - Zhi-Kai Yang; Yu-Han Ma; Jian-Wei Zheng; Wei-Dong Yang; Jie-Sheng Liu; Hong-Ye Li (Journal of Applied Phycology, 2014)

E2F1-mediated DNA damage is implicated in 8-Cl-adenosine-induced chromosome missegregation and apoptosis in human lung cancer H1299 cells - Yu-Ying Han; Zhe Zhou; Ji-Xiang Cao; Ya-Qiong Jin; Shu-Yan Li; Ju-Hua Ni; Guo-Shun An; Yu-Xiang Zhang; Hong-Ti Jia (Molecular and Cellular Biochemistry, 2013)

β-Ionone arrests cell cycle of gastric carcinoma cancer cells by a MAPK pathway - Hong-Wei Dong; Shuang Zhang; Wen-Guang Sun; Qian Liu; Juan C. Ibla; Sulpicio G. Soriano; Xiao-Hui Han; Lian-Xin Liu; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

Antiarrhythmic effects and ionic mechanisms of allicin on myocardial injury of diabetic rats induced by streptozotocin - Wei Huang; Ye Wang; Yong-Gang Cao; Han-Ping Qi; Lei Li; Bing Bai; Yang Liu; Hong-Li Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Effects of Norepinephrine on Immune Functions of Cultured Splenic Lymphocytes Exposed to Aluminum Trichloride - Ji-Hong Zhang; Chong-Wei Hu; Yan-Zhu Zhu; Shi-Min Liu; Chong-Sheng Bai; Yan-Fei Han; Shi-Liang Xia; Yan-Fei Li (Biological Trace Element Research, 2013)

LPS induces cardiomyocyte injury through calcium-sensing receptor - Hong-yu Wang; Xue-yan Liu; Gan Han; Zhu-ying Wang; Xiao-xie Li; Zhi-mei Jiang; Chun-ming Jiang (Molecular and Cellular Biochemistry, 2013)

Maturation profile of inferior olivary neurons expressing ionotropic glutamate receptors in rats: role in coding linear accelerations - Chuan Li; Lei Han; Chun-Wai Ma; Suk-King Lai; Chun-Hong Lai; Daisy Kwok Yan Shum; Ying-Shing Chan (Brain Structure and Function, 2013)

Re-Examination of the Genotoxic Activity of Water Taken From the Songhua River in P. R. China - Jia Yu; Hong-Wei Dong; Li-Tian Shi; Hui-Ling Jiang; Jian-Wen Yu; Qian-Wen Zhao; Shi-Chun Cai; Dan Han; Xuan-Yue Tang; Jia-Ren Liu (Archives of Environmental Contamination and Toxicology, 2013)

High resource capture and use efficiency and prolonged growth season contribute to invasiveness of Eupatorium adenophorum - Wei-Bin Wang; Rui-Fang Wang; Yan-Bao Lei; Chao Liu; Li-Hong Han; Xiao-Dong Shi; Yu-Long Feng (Plant Ecology, 2013)

MicroRNAs-1614-3p gene seed region polymorphisms and association analysis with chicken production traits - Hong Li; Gui-Rong Sun; Ya-Dong Tian; Rui-Li Han; Guo-Xi Li; Xiang-Tao Kang (Journal of Applied Genetics, 2013)

Regulation of LaMYB33 by miR159 during maintenance of embryogenic potential and somatic embryo maturation in Larix kaempferi (Lamb.) Carr. - Wan-Feng Li; Shou-Gong Zhang; Su-Ying Han; Tao Wu; Jun-Hong Zhang; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

In vitro isolation and cultivation of rabbit tracheal epithelial cells using tissue explant technique - Hong-Can Shi; Dan Lu; Hai-Jia Li; Shi Han; Yan-Jun Zeng (In Vitro Cellular & Developmental Biology - Animal, 2013)

Disruption of the transcription factor RBP-J results in osteopenia attributable to attenuated osteoclast differentiation - Jing Ma; Ya-Li Liu; Yi-Yang Hu; Ya-Ning Wei; Xing-Cheng Zhao; Guang-Ying Dong; Hong-Yan Qin; Yin Ding; Hua Han (Molecular Biology Reports, 2013)

Endostatin inhibits hypertrophic scarring in a rabbit ear model - Hai-tao Ren; Hang Hu; Yuan Li; Hong-fei Jiang; Xin-lei Hu; Chun-mao Han (Journal of Zhejiang University-SCIENCE B, 2013)

Apoptosis initiation of β-ionone in SGC-7901 gastric carcinoma cancer cells via a PI3K-AKT pathway - Qian Liu; Hong-Wei Dong; Wen-Guang Sun; Ming Liu; Juan C. Ibla; Lian-Xin Liu; John W. Parry; Xiao-Hui Han; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

Deletion of RBP-J in dendritic cells compromises TLR-mediated DC activation accompanied by abnormal cytoskeleton reorganization - Yun-Ru Chen; Fan Feng; Li Wang; Shuo-Yao Qu; Zhen-Qiang Zhang; Li Liu; Hong-Yan Qin; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2013)

Metabolic Changes Detected by Ex Vivo High Resolution 1H NMR Spectroscopy in the Striatum of 6-OHDA-Induced Parkinson’s Rat - Hong-Chang Gao; Huan Zhu; Cai-Yong Song; Li Lin; Yun Xiang; Zhi-Han Yan; Guang-Hui Bai; Fa-Qing Ye; Xiao-Kun Li (Molecular Neurobiology, 2013)

Surgical Trauma Induces Iron Accumulation and Oxidative Stress in a Rodent Model of Postoperative Cognitive Dysfunction - Li-Na An; Yang Yue; Wen-Zhi Guo; Yu-Liang Miao; Wei-Dong Mi; Hong Zhang; Zhi-Li Lei; Shu-Jun Han; Lan Dong (Biological Trace Element Research, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Identification of QTLs associated with tissue culture response through sequencing-based genotyping of RILs derived from 93-11 × Nipponbare in rice (Oryza sativa) - Sujuan Li; Song Yan; A-hong Wang; Guihua Zou; Xuehui Huang; Bin Han; Qian Qian; Yuezhi Tao (Plant Cell Reports, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

The Diagnostic Value of Treadmill Exercise Test Parameters for Coronary Artery Disease - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

Polymorphisms of the interleukin-15 gene and their associations with fatness and muscle fiber traits in chickens - Shi-Jie Lv; Ling Su; Hong Li; Rui-Li Han; Gui-Rong Sun; Xiang-Tao Kang (Journal of Applied Genetics, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

The modulation of venlafaxine on cortical activation of language area in healthy subjects with fMRI study - Qi Xie; Yan Liu; Chun-Yong Li; Xue-Zhu Song; Jun Wang; Li-Xin Han; Hong-Min Bai (Psychopharmacology, 2012)

Effects of pH and low molecular weight organic acids on competitive adsorption and desorption of cadmium and lead in paddy soils - Hong Jiang; Tingqiang Li; Xuan Han; Xiaoe Yang; Zhenli He (Environmental Monitoring and Assessment, 2012)

Choline inhibits angiotensin II-induced cardiac hypertrophy by intracellular calcium signal and p38 MAPK pathway - Shu Wang; Hong-mei Han; Zhen-wei Pan; Peng-zhou Hang; Li-hua Sun; Ya-nan Jiang; Hao-xin Song; Zhi-min Du; Yan Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Migration of natural estrogens around a concentrated dairy-feeding operation - Yan-xia Li; Wei Han; Ming Yang; Cheng-hong Feng; Xiao-fei Lu; Feng-song Zhang (Environmental Monitoring and Assessment, 2012)

Isolation and characterization of a Chinese strain of human enterovirus 74 from a healthy child in the Tibet Autonomous Region of China - Jitao Wang; Yong Zhang; Mei Hong; Xiaolei Li; Shuangli Zhu; Dongmei Yan; Dongyan Wang; Hongqiu An; Tsewang; Jianrong Han; Wenbo Xu (Archives of Virology, 2012)

Polymorphisms of the pro-opiomelanocortin and agouti-related protein genes and their association with chicken production traits - Yichun Bai; Guirong Sun; Xiangtao Kang; Ruili Han; Yadong Tian; Hong Li; Yang Wei; Shikang Zhu (Molecular Biology Reports, 2012)

Molecular characterization of Antarctic actinobacteria and screening for antimicrobial metabolite production - Learn-Han Lee; Yoke-Kqueen Cheah; Shiran Mohd Sidik; Nurul-Syakima Ab Mutalib; Yi-Li Tang; Hai-Peng Lin; Kui Hong (World Journal of Microbiology and Biotechnology, 2012)

Monocyte to macrophage differentiation-associated (MMD) positively regulates ERK and Akt activation and TNF-α and NO production in macrophages - Qiang Liu; Jin Zheng; Dan-Dan Yin; Jie Xiang; Fei He; Yao-Chun Wang; Liang Liang; Hong-Yan Qin; Li Liu; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Novel SNPs in the PRDM16 gene and their associations with performance traits in chickens - Ruili Han; Yang Wei; Xiangtao Kang; Hong Chen; Guirong Sun; Guoxi Li; Yichun Bai; Yadong Tian; Yanqun Huang (Molecular Biology Reports, 2012)

Large-scale sequencing of normalized full-length cDNA library of soybean seed at different developmental stages and analysis of the gene expression profiles based on ESTs - Ai-Hua Sha; Chen Li; Xiao-Hong Yan; Zhi-Hui Shan; Xin-An Zhou; Mu-Lan Jiang; Han Mao; Bo Chen; Xia Wan; Wen-Hui Wei (Molecular Biology Reports, 2012)

Fusion of HSA influences TNF-α neutralizing activity of shTNFRs - Jia Zhan; Ying Chen; Han-Ying Yuan; Hai Li; Hong Lu (Biotechnology Letters, 2012)

Phylogenetic relationships between Leymus (Poaceae, Triticeae) and related diploid Triticeae species based on isozyme and genome-specific random amplified polymorphic DNA (RAPD) markers - Rui-Wu Yang; Min-Han Zhong; Xue-Mei Zou; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou (Plant Biosystems, 2012)

Mice Lacking Urea Transporter UT-B Display Depression-Like Behavior - Xin Li; Jianhua Ran; Hong Zhou; Tianluo Lei; Li Zhou; Jingyan Han; Baoxue Yang (Journal of Molecular Neuroscience, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Effect of long-term administration of dietary β-1,3-glucan on growth, physiological, and immune responses in Litopenaeus vannamei (Boone, 1931) - Hong-Xia Zhao; Jun-Ming Cao; An-Li Wang; Zhen-Yu Du; Chao-Xia Ye; Yan-Hua Huang; Han-Bing Lan; Ting-Ting Zhou; Guo-Li Li (Aquaculture International, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Possible roles of auxin and zeatin for initiating the dwarfing effect of M9 used as apple rootstock or interstock - Hong Li Li; He Zhang; Chi Yu; Li Ma; Yi Wang; Xin Zhong Zhang; Zhen Hai Han (Acta Physiologiae Plantarum, 2012)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Profile of Organochlorine Pesticides in Soil Cores from Some Hotspot Areas of Beijing, China - Hang-Xin Cheng; Xing-Hong Li; Ya-Ping Wang; Chuan-Dong Zhao; Ying-Han Liu; Hong-Han Chen; Xiao-Bai Xu (Bulletin of Environmental Contamination and Toxicology, 2011)

Effective Gene Delivery to Mesenchymal Stem Cells Based on the Reverse Transfection and Three-Dimensional Cell Culture System - Cai-Xia He; Ni Li; Yu-Lan Hu; Xiu-Mei Zhu; Hai-Jie Li; Min Han; Pei-Hong Miao; Zhong-Jie Hu; Gang Wang; Wen-Quan Liang; Yasuhiko Tabata; Jian-Qing Gao (Pharmaceutical Research, 2011)

The Mechanism of Liver Injury in Mice Caused by Lanthanoids - Min Fei; Na Li; Yuguan Ze; Jie Liu; Sisi Wang; Xiuaolan Gong; Yanmei Duan; Xiaoyang Zhao; Han Wang; Fashui Hong (Biological Trace Element Research, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

P38-Nrf-2 Signaling Pathway of Oxidative Stress in Mice Caused by Nanoparticulate TiO2 - Jue Wang; Na Li; Lei Zheng; Sisi Wang; Ying Wang; Xiaoyang Zhao; Yanmei Duan; Yaling Cui; Min Zhou; Jingwei Cai; Songjie Gong; Han Wang; et al. (Biological Trace Element Research, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Molecular cloning and characterization of Izumo1 gene from sheep and cashmere goat reveal alternative splicing - Wan-Jin Xing; Bao-Da Han; Qi Wu; Li Zhao; Xiao-Hong Bao; Shorgan Bou (Molecular Biology Reports, 2011)

Isolation and characterization of a new bacteriophage MMP17 from Meiothermus - Lianbing Lin; Jian Han; Xiuling Ji; Wei Hong; Li Huang; Yunlin Wei (Extremophiles, 2011)

Molecular cloning, characterization and expression analysis of a pacC homolog in the mycoparasite Coniothyrium minitans - Yong-Chao Han; Guo-Qing Li; Long Yang; Dao-Hong Jiang (World Journal of Microbiology and Biotechnology, 2011)

Polymorphism of prion protein gene in sheep of Inner Mongolian, China - Cai-Xia Han; Hong-Xiang Liu; Yi-Xin Lu; Ming-Xin Song; De-Ming Zhao; Xiang-Mei Zhou; Li-Feng Yang; Xiao-Yun Li (Virus Genes, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Oxidative Stress in the Liver of Mice Caused by Intraperitoneal Injection with Lanthanoides - Min Fei; Na Li; Yuguan Ze; Jie Liu; Xiaolan Gong; Yanmei Duan; Xiaoyang Zhao; Han Wang; Fashui Hong (Biological Trace Element Research, 2011)

Norovirus Gastroenteritis Outbreak is Associated with Contaminated Drinking Water in South China - Ya-Qing He; Han-Wu Ma; Xiang-Jie Yao; Qing-Lan Bu; Hong Yang; Wei Huang; Yong-Xiang Duan; Hai-Long Zhang; Chuan-Wen Dai; Wei-Ke Li; Shou-Yi Yu (Food and Environmental Virology, 2010)

β-catenin signaling involves HGF-enhanced HepG2 scattering through activating MMP-7 transcription - Fei-Yan Pan; Sheng-Zhou Zhang; Na Xu; Fan-Li Meng; Hong-Xia Zhang; Bin Xue; Xiao Han; Chao-Jun Li (Histochemistry and Cell Biology, 2010)

Interaction Between Nanoparticulate Anatase TiO2 and Lactate Dehydrogenase - Yanmei Duan; Na Li; Chao Liu; Huiting Liu; Yaling Cui; Han Wang; Fashui Hong (Biological Trace Element Research, 2010)

Two-stent strategy for renal artery stenosis with bifurcation lesion - Hong-bing Yan; Bin Zheng; Zheng Wu; Jian Wang; Han-jun Zhao; Li Song; Yun-peng Chi (Journal of Zhejiang University-SCIENCE B, 2010)

Spontaneous Rhythmic Inward Currents Recorded in Interstitial Cells of Rabbit Portal Vein - Xu Huang; Dan Zhao; Zuo-Yu Wang; Ming-Liang Zhang; Zhi-Qiang Yan; Yan-Fei Han; Hong-Li Lu; Wen-Xie Xu; Zong-Lai Jiang (Cell Biochemistry and Biophysics, 2010)

Ectopic Expression of the Tomato Mi-1 Gene Confers Resistance to Root Knot Nematodes in Lettuce (Lactuca sativa) - Li-Ying Zhang; Yu-Yang Zhang; Ru-Gang Chen; Jun-Hong Zhang; Tao-Tao Wang; Han-Xia Li; Zhi-Biao Ye (Plant Molecular Biology Reporter, 2010)

Inhibition of human lung adenocarcinoma growth using survivint34a by low-dose systematic administration - Yan Shan; Chunting Wang; Li Yang; Li Juan Chen; Hong Xin Deng; Han Shuo Yang; Zhimian Li; Zhiyong Li; Li Pan; Fei Leng; Yuquan Wei (Journal of Biosciences, 2010)

Actin Microfilament Involved in Regulation of Pacemaking Activity in Cultured Interstitial Cells of Cajal from Murine Intestine - Zuo Yu Wang; Yan Fei Han; Xu Huang; Hong Li Lu; Xin Guo; Yong Chul Kim; Wen Xie Xu (The Journal of Membrane Biology, 2010)

KCNQ1 loss-of-function mutation impairs gastric acid secretion in mice - Qin Pan; Jun Ma; Qinshu Zhou; Jun Li; Yongqing Tang; Yi Liu; Yiqing Yang; Junjie Xiao; Luying Peng; Pengjuan Li; Dandan Liang; Hong Zhang; et al. (Molecular Biology Reports, 2010)

Dissipation and Residues of Chlormequat in Wheat and Soil - Xing-li Guo; Chun-hong Jia; Er-cheng Zhao; Yan-jun Xu; Li-jun Han; Shu-ren Jiang (Bulletin of Environmental Contamination and Toxicology, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

QTL analysis of kernel shape and weight using recombinant inbred lines in wheat - Xian-Yin Sun; Ke Wu; Yan Zhao; Fan-Mei Kong; Guan-Zhu Han; Hong-Ming Jiang; Xing-Jiao Huang; Rui-Jun Li; Hong-Gang Wang; Si-Shen Li (Euphytica, 2009)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

Notch signaling regulates the FOXP3 promoter through RBP-J- and Hes1-dependent mechanisms - Hai-Feng Ou-Yang; Hong-Wei Zhang; Chang-Gui Wu; Ping Zhang; Jian Zhang; Jun-Chang Li; Li-Hong Hou; Fei He; Xin-Yu Ti; Li-Qiang Song; Su-Zhen Zhang; Lei Feng; et al. (Molecular and Cellular Biochemistry, 2009)

Involvement of P-glycoprotein, Multidrug Resistance Protein 2 and Breast Cancer Resistance Protein in the Transport of Belotecan and Topotecan in Caco-2 and MDCKII Cells - Hong Li; Hyo-Eon Jin; Wooyoung Kim; Yong-Hae Han; Dae-Duk Kim; Suk-Jae Chung; Chang-Koo Shim (Pharmaceutical Research, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Sesquilignans and dilignans from Campylotropis hirtella (Franch.) Schindl. - Hui-Ying Han; Hong-Wei Liu; Nai-Li Wang; Xin-Sheng Yao (Natural Product Research, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Effects and complications of placement of motility coupling post in porous polyethylene orbital implants - Hong-guang Cui; Rong-rong Hu; Hui-yan Li; Wei Han (Journal of Zhejiang University-SCIENCE B, 2008)

Molecular characterization of two Chinese isolates of Beet mosaic virus - Haiying Xiang; Yan-Hong Han; Chenggui Han; Dawei Li; Jialin Yu (Virus Genes, 2007)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Suppression of Sclerotinia sclerotiorum by antifungal substances produced by the mycoparasite Coniothyrium minitans - Rui Yang; Yong Chao Han; Guo Qing Li; Dao Hong Jiang; Hung Chang Huang (European Journal of Plant Pathology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Molecular cloning and overexpression of a novel UDP-glucosyltransferase elevating salidroside levels in Rhodiola sachalinensis - Lan-Qing Ma; Ben-Ye Liu; Dong-Yao Gao; Xiao-Bin Pang; Shi-You Lü; Han-Song Yu; Hong Wang; Fang Yan; Zhen-Qiu Li; Yan-Fang Li; He-Chun Ye (Plant Cell Reports, 2007)

Regulation of Antioxidants and Phase 2 Enzymes by Shear-Induced Reactive Oxygen Species in Endothelial Cells - Charles I. Jones; Hong Zhu; Sergio F. Martin; Zhaosheng Han; Yunbo Li; B. Rita Alevriadou (Annals of Biomedical Engineering, 2007)

N2O Emissions under Different Moisture and Temperature Regimes - Han Jian-gang; Zhu Yong-li; Bai Hong-ying; Qu Dong; Chu Jin-yu; Wu Chun-du (Bulletin of Environmental Contamination and Toxicology, 2007)

Human Homologue of Seta Binding Protein 1 Interacts with Cathepsin B and Participates in TNF-Induced Apoptosis in Ovarian Cancer Cells - Jian-Ping Liu; Nan-Song Liu; Han-Ying Yuan; Qian Guo; Hong Lu; Yu-Yang Li (Molecular and Cellular Biochemistry, 2006)

MHC-BPS: MHC-binder prediction server for identifying peptides of flexible lengths from sequence-derived physicochemical properties - Juan Cui; Lian Yi Han; Hong Huang Lin; Zhi Qun Tang; Li Jiang; Zhi Wei Cao; Yu Zong Chen (Immunogenetics, 2006)

Localization of putative stem cells and four cell populations with different differentiation degree in mouse mammary anlagen - Jianyong Han; Suying Cao; Hong Jin; Ying Liu; Meili Wang; Jiazhe Song; Ning Li (Histochemistry and Cell Biology, 2006)

Pharmacokinetic study with N-Ile1-Thr2-63-desulfato-r-hirudin in rabbits by means of bioassay - Guo-zhu Han; Hong-can Ren; Yong Lu; Ying Li; Shu Xiao; Hong-wei Ye; He-mu Wang (Journal of Zhejiang University-SCIENCE B, 2006)

Litterfall Dynamics of an Evergreen Broadleaf Forest and a Pine Forest in the Subtropical Region of China - Zhi An Li; Bi Zou; Han-ping Xia; Hai Ren; Jiang-ming Mo; Hong Weng (Forest Science, 2005)
Monthly litterfall was monitored over a 10-year period from an evergreen broadleaf forest (EBF) and a pine forest (PF) in subtropical South China. During this period, litter was also collected bimonthly from the forest floor for 2 years. Total annual litterfall in EBF fluctuated around 9 Mg ha−1 with leaves, branches, and miscellanea accounting for 52.5%, 22.2%, and 25.3%, respectively. Total annual litterfall alternated between high and low values in consecutive years. Storms and pest outbreaks were responsible for most of the peaks in both monthly and annual litterfall. Litter from each of 43 species was recorded, but 9 species contributed about 85% of total litterfall. Dominant species shed their leaves in a more regular pattern with peaks mainly from Jan. to Mar. Pine forest (Pinus massoniana) produced much less litterfall than EBF, with a mean of 2.7 Mg ha−1. Here, leaves accounted for 73.2% of total litterfall, branches only 11.4%, and miscellanea 15.4%. Litter on the ground amounted to 5.2 Mg ha−1 in EBF and 2.9 Mg ha−1 in PF. The results show that this climax forest has much higher litterfall and forest floor mass than the pine forest, and litterfall is rather stable with regard to annual variation. FOR. SCI. 51(6):608–615.

Different effects on ACC oxidase gene silencing triggered by RNA interference in transgenic tomato - Ai-Sheng Xiong; Quan-Hong Yao; Ri-He Peng; Xian Li; Pei-Lai Han; Hui-Qin Fan (Plant Cell Reports, 2005)

SYNTHESIS BIODISTRIBUTION AND QSAR STUDIES OF FIVE Tc-99M LABELED NOVEL N3S PSEUDO-PEPTIDE COMPLEXES - Hua-bei Zhang; Hai-hong Ye; Ya-ling Zhang; Xuefang Zheng; Jian-sheng Han; Hua Li; Chun-ping Liu (Medicinal Chemistry Research, 2005)

Delayed cardioprotection induced by nitroglycerin is mediated by alpha-calcitonin gene-related peptide - Zhi-Hong Zhou; Jun Peng; Feng Ye; Nian-Sheng Li; Han-Wu Deng; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Molecular characterization of germline mutations in the BRCA1 and BRCA2 genes from breast cancer families in Taiwan - Steven Shoei-Lung Li; H.-M. Tseng; Tsui-Ping Yang; Chia-Han Liu; Shiuh-Jen Teng; Hung-Wen Huang; L.-M. Chen; Hsiao-Wei Kao; Jimmy H. Chen; Jau-Neng Tseng; Angela Chen; Ming-Feng Hou; et al. (Human Genetics, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)